Positive electrode active material, positive electrode sheet, secondary battery, battery module, battery pack, and electric device
By doping elements in LiMnPO4, a new positive electrode active material was prepared, which solved the problems of Li/Mn reverse position defect and manganese dissolution during the charging and discharge process of lithium manganese phosphate positive electrode active material, and significantly improved the performance of the secondary battery.
Patent Information
- Application Number
- CN202411425797.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2021-12-22
- Filing Date
- 2022-10-21
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2042-10-21
AI Technical Summary
The existing lithium manganese phosphate positive electrode active materials are prone to Li/Mn reverse position defects and manganese dissolution during charging and discharging, resulting in low capacity, poor safety performance and circulation performance of the secondary battery.
A novel positive electrode active material, including the compound LiAxMn1-yByP1-zCzO4-nDn, was prepared by doping specific elements at the Mn position of the compound LiMnPO4 and optionally at the Li, P and/or O positions. This material improves the rate performance by doping elements, reduces the dissolution of Mn and Mn-position doped elements, improves cycling performance and high temperature stability, and improves the material's gram capacity and compaction density.
It significantly improves the rate performance, cycle performance and high temperature stability of the secondary battery, improves the material's gram capacity and compaction density, reduces Mn dissolution, and enhances the safety performance of the battery.
Smart Images

Figure CN119542374A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium batteries, and in particular to positive electrode active materials, positive electrode plates, secondary batteries, battery modules, battery packs and electrical devices. Background Art
[0002] With the rapid development of the new energy field, lithium-ion batteries are widely used in various large-scale power devices, energy storage systems and various consumer products due to their excellent electrochemical performance, no memory effect, and low environmental pollution. They are especially widely used in new energy vehicles such as pure electric vehicles and hybrid electric vehicles. Among them, lithium manganese phosphate positive electrode active material has the advantages of high working voltage, wide source of raw materials and low environmental pollution. It is considered to be a positive electrode active material that is expected to replace lithium iron phosphate and become a power lithium-ion battery.
[0003] However, in the prior art, the cycle performance, high temperature storage performance and safety performance of secondary batteries using lithium manganese phosphate positive electrode active materials have not been comprehensively improved, which greatly limits the wider application of lithium manganese phosphate batteries. Therefore, the industry is still looking forward to designing a lithium manganese phosphate positive electrode active material with high gram capacity, good cycle performance and safety performance. Summary of the invention
[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a positive electrode active material, a preparation method of the positive electrode active material, a positive electrode sheet, a secondary battery, a battery module, a battery pack and an electrical device to solve the problem that the existing lithium manganese phosphate positive electrode active material is prone to produce Li / Mn anti-site defects and manganese dissolution is serious during the charge and discharge process, thereby solving the problems of low capacity, poor safety performance and cycle performance of the secondary battery.
[0005] In order to achieve the above-mentioned object, the present application provides a first aspect of a positive electrode active material, comprising a compound represented by formula (I),
[0006] Li a A x Mn 1-y B y P 1-z C z O 4-n D n
[0007] (I)
[0008] in,
[0009] A includes one or more elements selected from Group IA, Group IIA, Group IIIA, Group IIB, Group VB and Group VIB;
[0010] B comprises one or more elements selected from Group IA, Group IIA, Group IIIA, Group IVA, Group VA, Group IIB, Group IVB, Group VB, Group VIB, and Group VIII;
[0011] C includes one or more elements selected from Group IIIA, Group IVA, Group VA and Group VIA;
[0012] D comprises one or more elements selected from Group VIA and Group VIIA;
[0013] a is selected from the range of 0.85 to 1.15;
[0014] x is selected from the range of 0 to 0.1;
[0015] y is selected from the range of 0.001 to 0.999;
[0016] z is selected from the range of 0 to 0.5;
[0017] n is selected from the range of 0 to 0.5.
[0018] Therefore, the present application can obtain significantly improved rate performance by doping a specific element in a specific amount at the Mn position of the compound LiMnPO4 and optionally at the Li position, P position and / or O position, while significantly reducing the dissolution of Mn and the doping element at the Mn position, obtaining significantly improved cycle performance and / or high temperature stability, and the gram capacity and compaction density of the material are also improved.
[0019] In any embodiment, A includes one or more elements selected from Rb, Cs, Be, Ca, Sr, Ba, Ga, In, Cd, V, Ta, Cr, Zn, Al, Na, K, Mg, Nb, Mo and W, and may optionally include one or more elements selected from Zn, Al, Na, K, Mg, Nb, Mo and W; and / or,
[0020] B includes one or more elements selected from Rb, Cs, Be, Ca, Sr, Ba, In, Pb, Bi, Cd, Hf, Ta, Cr, Ru, Rh, Pd, Os, Ir, Pt, Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and can optionally include one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge; and / or, C includes one or more elements selected from B (boron), S, Si and N; and / or, D includes one or more elements selected from S, F, Cl and Br.
[0021] As a result, the rate performance, gram capacity, compaction density, cycle performance and / or high temperature performance of the secondary battery can be further improved, and the dissolution of Mn and Mn-doping elements can be further reduced.
[0022] In any embodiment, A includes any one element selected from Zn, Al, Na, K, Mg, Nb, Mo and W, and may be any one element selected from Mg and Nb; and / or,
[0023] B comprises one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge, and may be selected from at least two elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge, and may be selected from at least two elements selected from Fe, Ti, V, Ni, Co and Mg, and may be further selected from at least two elements selected from Fe, Ti, V, Co and Mg, and may be further selected from Fe and one or more elements selected from Ti, V, Co and Mg; and / or,
[0024] C includes any one element selected from B (boron), S, Si and N, and may be S; and / or,
[0025] D includes any one element selected from S, F, Cl and Br, and may be F.
[0026] As a result, the rate performance of the secondary battery can be further improved, the dissolution of Mn and Mn-doped elements can be further reduced, the cycle performance and / or high temperature performance of the secondary battery can be improved, and the gram capacity and compaction density of the material can be further increased.
[0027] In any embodiment, a is selected from the range of 0.9 to 1.1, optionally selected from the range of 0.97 to 1.01; and / or,
[0028] The x is selected from the range of 0 to 0.005, optionally selected from the range of 0.001 to 0.1; and / or,
[0029] The y is selected from the range of 0.001 to 0.5, optionally selected from the range of 0.01 to 0.5, optionally selected from the range of 0.25 to 0.5; and / or,
[0030] The z is selected from the range of 0 to 0.5, optionally from the range of 0.001 to 0.5, optionally from the range of 0.001 to 0.1, more optionally from the range of 0.001 to 0.005; and / or,
[0031] Said n is selected from the range of 0 to 0.1, optionally selected from the range of 0.001 to 0.1.
[0032] As a result, the gram capacity of the material can be further increased, the rate performance and / or kinetic performance of the secondary battery can be further improved, and the cycle performance and / or high temperature performance of the battery can be further improved.
[0033] In any embodiment, x is 0, z is selected from the range of 0.001 to 0.5, and n is selected from the range of 0.001 to 0.1; or,
[0034] x is selected from the range of 0.001 to 0.1, z is 0, and n is selected from the range of 0.001 to 0.1; or,
[0035] x is selected from the range of 0.001 to 0.1, z is selected from the range of 0.001 to 0.5, and n is 0; or,
[0036] x is 0, z is 0, and n is selected from the range of 0.001 to 0.1; or,
[0037] x is 0, z is selected from the range of 0.001 to 0.5, and n is 0; or,
[0038] x is selected from the range of 0.001 to 0.1, z is selected from the range of 0.001 to 0.5, and n is selected from the range of 0.001 to 0.1.
[0039] Therefore, the present application can significantly improve the rate performance, significantly reduce the dissolution of Mn and the doping elements at the Mn position, significantly improve the cycle performance and / or high temperature stability, and significantly increase the gram capacity and compacted density of the material by doping a specific element at the Mn position of the compound LiMnPO4 and optionally at the Li position, P position and / or O position, especially doping a specific element at the Mn position and P position of LiMnPO4 or at the Li position, Mn position, P position and O position of LiMnPO4.
[0040] In any embodiment, y:z is selected from the range of 0.002 to 999, and can be selected from the range of 0.025 to 999, and can be selected from the range of 0.2 to 600. Thus, the defects of the material can be reduced, and the integrity of the material framework structure can be improved, thereby effectively improving the structural stability of the material, and further improving the cycle stability of the secondary battery.
[0041] In any embodiment, z:n is selected from the range of 0.002 to 500, and can be selected from the range of 0.2 to 100, and can be selected from the range of 0.2 to 50. Thus, the defects of the material can be further reduced, the integrity of the material framework structure can be further improved, the structural stability of the material can be effectively improved, and the cycle stability of the secondary battery can be improved.
[0042] In any embodiment,
[0043] A includes one or more elements selected from Zn, Al, Na, K, Mg, Nb, Mo and W;
[0044] B includes one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge;
[0045] C includes one or more elements selected from B (boron), S, Si and N;
[0046] D comprises one or more elements selected from S, F, Cl and Br;
[0047] a is selected from the range of 0.9 to 1.1, x is selected from the range of 0.001 to 0.1, y is selected from the range of 0.001 to 0.5, z is selected from the range of 0.001 to 0.1, and n is selected from the range of 0.001 to 0.1.
[0048] Therefore, the present application can obtain significantly improved rate performance by doping specific elements in specific amounts at the Li position, Mn position, P position and O position of the compound LiMnPO4, while significantly reducing the dissolution of Mn and the doping elements at the Mn position, thereby obtaining significantly improved cycle performance and / or high temperature stability, and the gram capacity and compaction density of the material can also be improved.
[0049] In any embodiment,
[0050] B comprises one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and optionally one or more elements selected from Zn, Fe, Ti, V, Ni, Co and Mg;
[0051] C is one or more elements selected from B, Si, N and S;
[0052] a is selected from the range of 0.9 to 1.1, x is 0, y is selected from the range of 0.001 to 0.5, z is selected from the range of 0.001 to 0.1, and n is 0.
[0053] Therefore, the present application can improve the rate performance, reduce the dissolution of Mn and the doping elements at the Mn position, improve the cycle performance and / or high temperature stability, and increase the gram capacity and compaction density of the material by doping specific elements at the Mn position and the P position of the compound LiMnPO4 in specific amounts at the same time.
[0054] In any embodiment, the positive electrode active material includes a core and a shell covering the core, and the core includes the compound represented by the above formula I;
[0055] The shell includes one or more coating layers; the coating layers have ion conductivity or electronic conductivity.
[0056] The present application provides a novel positive electrode active material with a core-shell structure by doping a specific element in a specific amount at the Mn position of the compound LiMnPO4 and optionally at the Li position, P position and / or O position to obtain a doped lithium manganese phosphate core, and arranging a coating layer with ionic conductivity or electronic conductivity on the surface of the core. The positive electrode active material is applied to a secondary battery, which can significantly improve the high-temperature cycle performance, cycle stability and high-temperature storage performance of the secondary battery.
[0057] In any embodiment, the shell includes a coating;
[0058] Optionally, the coating layer includes one or more selected from pyrophosphate, phosphate, carbon, doped carbon, oxide, boride and polymer.
[0059] Therefore, the present application adopts the above materials to obtain a coating layer with ionic conductivity or electronic conductivity, thereby improving the high-temperature cycle performance, cycle stability and high-temperature storage performance of the secondary battery.
[0060] In any embodiment, the shell includes a first coating layer coating the inner core and a second coating layer coating the first coating layer;
[0061] Optionally, the first coating layer and the second coating layer each independently include one or more selected from pyrophosphate, phosphate, carbon, doped carbon, oxide, boride and polymer.
[0062] Therefore, the present application adopts the above-mentioned material as the material of the coating layer, and the provision of two coating layers can further improve the high-temperature cycle performance, cycle stability and high-temperature storage performance of the secondary battery.
[0063] In any embodiment, the first coating layer includes one or more selected from pyrophosphate, phosphate, oxide and boride, and the second coating layer includes one or more selected from carbon and doped carbon.
[0064] Therefore, the present application adopts a first coating layer of a specific material and a second coating layer of a specific material, which can further improve the rate performance and further reduce the dissolution of Mn and Mn-doped elements, thereby improving the cycle performance and / or high temperature stability of the secondary battery.
[0065] In any embodiment, the shell includes a first coating layer coating the inner core, a second coating layer coating the first coating layer, and a third coating layer coating the second coating layer;
[0066] Optionally, the first coating layer, the second coating layer and the third coating layer each independently include one or more selected from pyrophosphate, phosphate, carbon, doped carbon, oxide, boride and polymer.
[0067] Therefore, the present application adopts the above materials as the materials of the coating layer, and setting three layers of coating layers can further reduce the dissolution of Mn and Mn-doped elements, and further improve the high-temperature cycle performance, cycle stability and high-temperature storage performance of the secondary battery.
[0068] In any embodiment, the first coating layer includes pyrophosphate, the second coating layer includes one or more selected from phosphates, oxides, and borides, and the third coating layer includes one or more selected from carbon and doped carbon.
[0069] Therefore, the present application adopts a first coating layer of a specific material, a second coating layer of a specific material, and a third coating layer of a specific material, which further improves the rate performance, further reduces the dissolution of Mn and Mn-doped elements, thereby improving the cycle performance and / or high temperature stability of the secondary battery, and further improves the gram capacity and compaction density of the material.
[0070] In any embodiment, the one or more coating layers each independently include one or more selected from pyrophosphate, phosphate, carbon, doped carbon, oxide, boride and polymer.
[0071] In any embodiment, the pyrophosphate is b (P2O7) c and / or,
[0072] Phosphate is X m (PO4) q and / or,
[0073] The doping element in the doped carbon includes one or more elements selected from Group IIIA, Group VA, Group VIA and Group VIIA; and / or,
[0074] Oxide is M' d O e and / or,
[0075] Boride is Z v B w and / or,
[0076] The polymer includes one or more selected from polysaccharides and their derivatives, and polysiloxanes;
[0077] in,
[0078] M, X and Z each independently include one or more elements selected from Group IA, Group IIA, Group IIIA, Group IB, Group IIB, Group IVB, Group VB, Group VIIB and Group VIII; b is selected from the range of 1 to 4, c is selected from the range of 1 to 6; m is selected from the range of 1 to 2, q is selected from the range of 1 to 4; M' includes one or more elements selected from alkali metals, alkaline earth metals, transition metals, Group IIIA elements, Group IVA elements, lanthanides and Sb, d is greater than 0 and less than or equal to 2, e is greater than 0 and less than or equal to 5; v is selected from the range of 1 to 7, and w is selected from the range of 1 to 2.
[0079] Therefore, by using the above-mentioned materials as the coating layer, the present application can further reduce the dissolution of Mn and Mn-doping elements, further increase the gram capacity and compaction density of the material, and further improve the rate performance, high-temperature cycle performance and high-temperature storage performance of the secondary battery.
[0080] In any embodiment, M, X and Z each independently include one or more elements selected from Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb and Al; and / or,
[0081] The doping element in the doped carbon includes one or more selected from nitrogen, phosphorus, sulfur, boron and fluorine; and / or,
[0082] M′ comprises one or more elements selected from Li, Be, B, Na, Mg, Al, Si, P, K, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, As, Se, Sr, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Te, W, La and Ce, and may optionally comprise one or more elements selected from Mg, Al, Si, Zn, Zr and Sn; and / or
[0083] The polysiloxane is selected from one or more of linear polysiloxane and cyclic polysiloxane; and / or,
[0084] The polysaccharide is selected from one or more of plant polysaccharides and marine polysaccharides.
[0085] Therefore, the present application can further reduce the dissolution of Mn and Mn-doping elements by using the above-mentioned specific material as the coating layer, and further improve the high-temperature cycle performance and high-temperature storage performance of the secondary battery.
[0086] In any embodiment, the positive electrode active material includes a core and a shell covering the core.
[0087] The kernel includes Li a Mn 1-y By P 1-z C z O4, wherein a is selected from the range of 0.9 to 1.1, y is selected from the range of 0.001 to 0.5, z is selected from the range of 0.001 to 0.1, B includes one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb, Zn and Ge, and C includes one or more elements selected from B (boron), S, Si and N;
[0088] The shell includes a first coating layer covering the inner core and a second coating layer covering the first coating layer.
[0089] Wherein, the first coating layer comprises pyrophosphate MP2O7 and phosphate XPO4, wherein M and X are each independently selected from one or more of Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb and Al;
[0090] The second coating layer includes carbon.
[0091] Thus, the positive electrode active material of the present application can improve the gram capacity, cycle performance and safety performance of the secondary battery. Although the mechanism is not clear, it is speculated that the positive electrode active material of the lithium manganese phosphate of the present application is a core-shell structure, wherein by doping elements at the manganese position and the phosphorus position of the lithium manganese phosphate core respectively, it can not only effectively reduce manganese dissolution, thereby reducing the manganese ions migrating to the negative electrode, reducing the electrolyte consumed by the decomposition of the SEI film, and improving the cycle performance and safety performance of the secondary battery, but also can promote the adjustment of the Mn-O bond, reduce the lithium ion migration barrier, promote lithium ion migration, and improve the rate performance of the secondary battery; by coating the core with a first coating layer including pyrophosphate and phosphate, it is possible to further increase the migration resistance of manganese, reduce its dissolution, and reduce the surface impurity lithium content, reduce the contact between the core and the electrolyte, thereby reducing the interface side reaction, reducing the gas production, and improving the high temperature storage performance, cycle performance and safety performance of the secondary battery; by further coating the carbon-containing layer as the second coating layer, the safety performance and kinetic performance of the secondary battery can be further improved.
[0092] In any embodiment, the positive electrode active material includes a core and a shell covering the core.
[0093] The kernel includes Li a Mn 1-y B y P 1-z C zO4, wherein a is selected from the range of 0.9 to 1.1, y is selected from the range of 0.001 to 0.5, z is selected from the range of 0.001 to 0.1, B includes one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge, and C includes one or more elements selected from B (boron), S, Si and N;
[0094] The shell includes a first coating layer coating the inner core, a second coating layer coating the first coating layer, and a third coating layer coating the second coating layer, wherein:
[0095] The first coating layer includes pyrophosphate Li f QP2O7 and / or Q g (P2O7) h , where 0≤f≤2, 1≤g≤4, 1≤h≤6, pyrophosphate Li f QP2O7 and / or Q g (P2O7) h Q in which each independently represents one or more elements selected from Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb and Al;
[0096] The second coating layer includes crystalline phosphate XPO4, wherein X is one or more elements selected from Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb and Al;
[0097] The third coating layer includes carbon.
[0098] The present application provides a novel lithium manganese phosphate positive electrode active material with a core-shell structure by doping elements at the manganese position of lithium manganese phosphate and doping elements at the phosphorus position to obtain a doped lithium manganese phosphate core and performing three-layer coating on the surface of the core in sequence. The positive electrode active material is applied to a secondary battery, which can significantly improve the high-temperature cycle performance, cycle stability and high-temperature storage performance of the secondary battery.
[0099] In any embodiment, one or more coating layers in the shell that are farthest from the core each independently include one or more selected from polysiloxane, polysaccharide and polysaccharide derivatives.
[0100] As a result, the uniformity of the coating can be improved, and the interfacial side reactions caused by high voltage can be effectively blocked, thereby improving the high-temperature cycle performance and high-temperature storage performance of the material; and the coating layer has good electronic conductivity and ionic conductivity, which helps to improve the gram capacity of the material while reducing the heat generation of the battery cell.
[0101] In any embodiment, the polysiloxane comprises a structural unit represented by formula (i),
[0102]
[0103]
[0104] Wherein, R1 and R2 are independently selected from H, -COOH, -OH, -SH, -CN, -SCN, amino, phosphate, carboxylate, amide, aldehyde, sulfonyl, polyether segment, C1-C20 aliphatic, C1-C20 halogenated aliphatic, C1-C20 heteroaliphatic, C1-C20 halogenated heteroaliphatic, C6-C20 aromatic, C6-C20 halogenated aromatic, C2-C20 heteroaromatic and C2-C20 halogenated heteroaromatic;
[0105] Optionally, R1 and R2 are independently selected from H, amino, phosphate, polyether segment, C1-C8 alkyl, C1-C8 haloalkyl, C1-C8 heteroalkyl, C1-C8 haloheteroalkyl, C2-C8 alkenyl and C2-C8 haloalkenyl.
[0106] In any embodiment, the polysiloxane further comprises an end-capping group, which includes at least one of the following functional groups: polyether, C1-C8 alkyl, C1-C8 haloalkyl, C1-C8 heteroalkyl, C1-C8 haloheteroalkyl, C2-C8 alkenyl, C2-C8 haloalkenyl, C6-C20 aromatic hydrocarbon group, C1-C8 alkoxy, C2-C8 epoxy, hydroxyl, C1-C8 hydroxyalkyl, amino, C1-C8 aminoalkyl, carboxyl, C1-C8 carboxylalkyl.
[0107] In any embodiment, the polysiloxane comprises a polydimethylsiloxane, a polydiethylsiloxane, a polymethylethylsiloxane, a polymethylvinylsiloxane, a polyphenylmethylsiloxane, a polymethylhydrogensiloxane, a carboxyl functionalized polysiloxane, an epoxy-terminated polysiloxane, a methoxy-terminated polydimethylsiloxane, a hydroxypropyl-terminated polydimethylsiloxane, a polymethylchloropropylsiloxane, a hydroxy-terminated polydimethylsiloxane, a polymethyltrifluoropropylsiloxane, a perfluorooctylmethylpolysiloxane, an aminoethylaminopropyl polydimethylsiloxane, a terminal polyether polydimethylsiloxane, a side chain aminopropyl polysiloxane. , aminopropyl-terminated polydimethylsiloxane, side chain phosphate grafted polydimethylsiloxane, side chain polyether grafted polydimethylsiloxane, 1,3,5,7-octamethylcyclotetrasiloxane, 1,3,5,7-tetrahydro-1,3,5,7-tetramethylcyclotetrasiloxane, cyclopentapolydimethylsiloxane, 2,4,6,8-tetramethylcyclotetrasiloxane, 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane, cyclic polymethylvinylsiloxane, hexadecylcyclooctasiloxane, tetradecamethylcycloheptasiloxane, cyclic polydimethylsiloxane or more.
[0108] In any embodiment, the number average molecular weight of polysiloxane, polysaccharide and polysaccharide derivative is independently below 300,000, optionally 10,000 to 200,000, more optionally 20,000 to 120,000, further optionally 400 to 80,000.
[0109] In any embodiment, the mass percentage of polar functional groups in the polysiloxane is α, 0≤α<50%, optionally, 5%≤α≤30%.
[0110] In any embodiment, the substituents attached to the sugar units in the polysaccharide and the polysaccharide derivatives each independently include at least one of the group consisting of the following functional groups: -OH, -COOH and salts thereof, -R-OH, -SO3H and salts thereof, -R-OH, -R-SO3H and salts thereof, sulfate, alkoxy, wherein R represents an alkylene group, optionally a C1 to C5 alkylene group;
[0111] Optionally, the substituents attached to the sugar units in the polysaccharides and polysaccharide derivatives each independently include at least one of the group consisting of the following functional groups: -OH, -COOH, -COOLi, -COONa, -COOK, -SO3H, -SO3Li, -SO3Na, -SO3K, -CH2-SO3H, -CH2-SO3Li, -CH2-SO3Na, -CH2-SO3K, methoxy, ethoxy.
[0112] In any embodiment, the polysaccharide includes one or more selected from pectin, carboxymethyl starch, hydroxypropyl starch, dextrin, cellulose ether, carboxymethyl chitosan, hydroxyethyl cellulose, carboxymethyl cellulose, carboxypropyl methyl cellulose, guar gum, sesbania gum, gum arabic, lithium alginate, sodium alginate, potassium alginate, fucoidan, agar, carrageenan, carrageenan, xanthan gum and fenugreek gum.
[0113] In any embodiment, the mass percentage of the substituents attached to the sugar units in the polysaccharide and the polysaccharide derivatives is independently 20% to 85%, optionally 30% to 78%.
[0114] In any embodiment, the lattice mismatch between the core material and the shell material is less than 10%, thereby enabling good contact between the core and the shell (or coating layer) to prevent the shell (or coating layer) from falling off.
[0115] In any embodiment, based on the weight of the positive electrode active material,
[0116] The manganese content is in the range of 10 wt% to 35 wt%, optionally in the range of 13.3 wt% to 33.2 wt%, more optionally in the range of 15 wt% to 30 wt%, further optionally in the range of 17 wt% to 20 wt%; and / or,
[0117] The phosphorus content is in the range of 12 wt% to 25 wt%, optionally in the range of 15 wt% to 20 wt%, and more optionally in the range of 16.8 wt% to 19.5 wt%; and / or,
[0118] The weight ratio of manganese element to phosphorus element ranges from 0.71 to 1.85, and can be selected from 0.90 to 1.25, and more preferably from 0.95 to 1.20.
[0119] The manganese content of the present application is within the above range, which can effectively reduce the problems of poor material structure stability and density reduction, thereby improving the cycle, storage and compaction density performance of the secondary battery; and can reduce the problem of too low voltage platform, thereby improving the energy density of the secondary battery.
[0120] In any embodiment, the surface of the positive electrode active material is coated with one or more of carbon and doped carbon; alternatively, the surface of the positive electrode active material is coated with carbon, thereby improving the conductivity of the positive electrode active material.
[0121] In any embodiment, the doping element in the doped carbon includes one or more elements selected from nitrogen, phosphorus, sulfur, boron and fluorine, so as to facilitate the control of the performance of the doped carbon layer.
[0122] In any implementation, in the kernel,
[0123] (1-y): y is in the range of 0.1-999, optionally in the range of 0.1-10 or in the range of 0.67-999, more optionally in the range of 1 to 10, further optionally in the range of 1 to 4, and further optionally in the range of 1.5 to 3; and / or,
[0124] a:x is in the range of 1 to 1200, and can be optionally in the range of 9 to 1100, and can be more optionally in the range of 190-998.
[0125] As a result, the energy density and cycle performance of the positive electrode active material can be further improved.
[0126] In any embodiment, in the core, the ratio of z to 1-z is 1:9 to 1:999, and can be 1:499 to 1:249. Thus, the cycle performance and rate performance of the secondary battery are further improved.
[0127] In any embodiment, the coating amount of the shell is 0.1% to 6%, based on the weight of the core. The coating amount of the coating layer of the present application is preferably within the above range, which can fully coat the core and further improve the kinetic performance and safety performance of the secondary battery without sacrificing the gram capacity of the positive electrode active material.
[0128] In any embodiment, the coating amount of the first coating layer is greater than 0 wt % and less than or equal to 7 wt %, optionally greater than 0 and less than or equal to 6 wt %, more optionally greater than 0 and less than or equal to 5.5 wt % or 4-5.6 wt %, further optionally greater than 0 and less than or equal to 2 wt %, based on the weight of the kernel; and / or,
[0129] The coating amount of the second coating layer is greater than 0 wt % and less than or equal to 6 wt %, optionally greater than 0 and less than or equal to 5.5 wt %, more optionally 2-4 wt % or 3-5 wt %, based on the weight of the kernel; and / or,
[0130] The coating amount of the third coating layer is greater than 0 and less than or equal to 6 wt %, optionally greater than 0 and less than or equal to 5.5 wt %, and more optionally greater than 0 and less than or equal to 2 wt %, based on the weight of the core.
[0131] In any embodiment, the shell further comprises a fourth coating layer coating the third coating layer and a fifth coating layer coating the fourth coating layer; wherein,
[0132] The coating amounts of the fourth coating layer and the fifth coating layer are each independently 0.01 to 10 wt %, optionally 0.05 to 10 wt %, more optionally 0.1 to 5 wt %, further 0.1 to 2 wt %, based on the weight of the core.
[0133] In the positive electrode active material with a core-shell structure of the present application, the coating amount of each coating layer is preferably within the above range, thereby being able to fully coat the inner core and at the same time further improve the kinetic performance and safety performance of the secondary battery without sacrificing the gram capacity of the positive electrode active material.
[0134] In any embodiment, the shell is located on 40% to 90% of the surface of the core, and optionally 60% to 80% of the surface, so that the core can be fully coated, thereby improving the dynamic performance and safety performance of the secondary battery.
[0135] In any embodiment, the shell has a thickness of 1-15 nm.
[0136] In any embodiment, the thickness of the first coating layer is 1-10 nm, optionally 2-10 nm; and / or,
[0137] The thickness of the second coating layer is 2-25 nm, optionally 2-15 nm, more optionally 3-15 nm; and / or,
[0138] The thickness of the third cladding layer is 2-25 nm, and can be 5-25 nm.
[0139] In the present application, the first coating layer has the above-mentioned thickness range, which can further reduce the adverse effects on the kinetic properties of the material and can reduce the problem of being unable to effectively hinder the migration of transition metal ions.
[0140] The second coating layer has the above-mentioned thickness range, so that the surface structure of the second coating layer is stable and the side reaction with the electrolyte is small, so the interface side reaction can be effectively reduced, thereby improving the high temperature performance of the secondary battery.
[0141] The third coating layer has the above-mentioned thickness range, which can enhance the electrical conductivity of the material and improve the compaction density performance of the battery pole piece prepared using the positive electrode active material.
[0142] In any embodiment, the one or more coating layers each independently include one or more selected from pyrophosphate, phosphate and oxide, and the one or more selected from pyrophosphate, phosphate and oxide is crystalline;
[0143] Optionally, the crystallinity of the pyrophosphate, phosphate and oxide is each independently from 10% to 100%, more preferably from 50% to 100%.
[0144] Herein, crystalline means that the crystallinity is above 50%, i.e., 50%-100%. Crystallinity less than 50% is called glassy state. The crystallinity of the crystalline pyrophosphate and crystalline phosphate of the present application is 50% to 100%.
[0145] Pyrophosphates and phosphates with a certain degree of crystallinity are not only conducive to fully exerting the pyrophosphate coating's ability to hinder manganese dissolution and the phosphate coating's excellent ability to conduct lithium ions and reduce interface side reactions, but also enable the pyrophosphate coating and the phosphate coating to better lattice match, thereby achieving a close bond between the coatings.
[0146] In any embodiment, in the shell, the weight ratio of pyrophosphate to phosphate and the weight ratio of pyrophosphate to oxide are independently 1:3 to 3:1, and can be 1:3 to 1:1. Thus, by having pyrophosphate and phosphate in a suitable weight ratio range or pyrophosphate and oxide in a suitable weight ratio range, manganese dissolution can be effectively hindered, and the surface impurity lithium content can be effectively reduced, and the interface side reaction can be reduced, thereby improving the high temperature storage performance, safety performance and cycle performance of the secondary battery.
[0147] In any embodiment, the one or more coating layers each independently include carbon, and the carbon is a mixture of SP2 carbon and SP3 carbon. Optionally, the molar ratio of SP2 carbon to SP3 carbon in the carbon is any value in the range of 0.07-13, and can be any value in the range of 0.1-10, and can be any value in the range of 2.0-3.0.
[0148] The present application improves the comprehensive performance of the secondary battery by limiting the molar ratio of SP2 carbon to SP3 carbon within the above range.
[0149] In any embodiment, the one or more coating layers independently include doped carbon, and the mass content of the doped element in the doped carbon is less than 30%; optionally, the mass content of the doped element in the doped carbon is less than 20%. The doping elements within the above content range can not only fully improve the conductivity of the pure carbon layer, but also effectively avoid excessive surface activity caused by excessive doping of the doping elements, thereby effectively controlling the interface side reactions caused by excessive doping of the coating layer.
[0150] In any embodiment, the one or more coating layers each independently include doped carbon, in which the doped carbon is
[0151] The doping element is nitrogen and / or sulfur, and the mass content of the doping element in the doped carbon is 1% to 15%; or,
[0152] The doping element is phosphorus, boron and / or fluorine, and the mass content of the doping element in the doped carbon is 0.5% to 5%;
[0153] Optionally, the doping element is nitrogen, phosphorus, sulfur, boron or fluorine.
[0154] Since nitrogen atoms and sulfur atoms are closer to the atomic radius of carbon atoms and are not easy to destroy the carbon skeleton, when the doping amount of nitrogen atoms and sulfur atoms is within the above relatively wide range, the conductivity of the doped carbon layer can be fully exerted, and the lithium ion transmission and lithium ion desolvation ability can be promoted.
[0155] Since the atomic radius of phosphorus atoms, boron atoms and / or fluorine atoms is different from that of carbon atoms, excessive doping can easily destroy the carbon skeleton. Therefore, when the doping amount of phosphorus atoms, boron atoms and / or fluorine atoms is within the relatively small range mentioned above, the conductivity of the doped carbon layer can be fully exerted, and the lithium ion transmission and lithium ion desolvation capabilities can be promoted.
[0156] In any embodiment, the one or more coating layers independently include pyrophosphate, the interplanar spacing of the pyrophosphate is in the range of 0.293-0.470nm, optionally 0.297-0.462nm or 0.293-0.326nm, more optionally 0.300-0.310nm, and the angle of the crystal direction (111) is in the range of 18.00°-32.57°, optionally 18.00°-32.00° or 26.41°-32.57°, more optionally 19.211°-30.846°, and further optionally 29.00°-30.00°; and / or,
[0157] The one or more coating layers independently include phosphate, the interplanar spacing of the phosphate is in the range of 0.244-0.425 nm, optionally 0.345-0.358 nm, and the angle of the crystal direction (111) is in the range of 20.00°-37.00°, optionally 24.25°-26.45°;
[0158] Optionally, the first coating layer or the second coating layer comprises a phosphate.
[0159] The first coating layer and the second coating layer in the positive electrode active material of the present application are both made of crystalline materials, and their interplanar spacing and angle ranges are within the above ranges. Thus, the impurity phase in the coating layer can be effectively reduced, thereby improving the material's gram capacity, cycle performance and rate performance.
[0160] In any embodiment, the lattice change rate of the positive electrode active material before and after complete lithium deintercalation is less than 50%, optionally less than 9.8%, more optionally less than 8.1%, further optionally less than 7.5%, further optionally less than 6%, further optionally less than 4%, further optionally less than 3.8%, and further optionally 2.0-3.8%.
[0161] Therefore, the use of positive electrode active materials can improve the gram capacity and rate performance of secondary batteries.
[0162] In any embodiment, the Li / Mn antisite defect concentration of the positive electrode active material is less than 5.3%, optionally less than 5.1%, more optionally less than 4%, further optionally less than 2.2%, further optionally less than 2%, further optionally less than 1.5%-2.2% or less than 0.5%.
[0163] When the Li / Mn antisite defect concentration is within the above range, the Mn 2+ Obstacles + transmission, while improving the gram capacity and rate performance of the positive electrode active material.
[0164] In any embodiment, the compaction density of the positive electrode active material at 3T is 1.89 g / cm 3 Above, optional 1.95g / cm 3 Above, 1.98g / cm2 is optional 3 Above, further optional 2.0g / cm 3 Above, further optional 2.2g / cm 3 Above, further optionally 2.2 g / cm 3 Above and 2.8g / cm 3 Below or 2.2g / cm 3 Above and 2.65g / cm 3 the following.
[0165] Therefore, increasing the compaction density increases the weight of the active material per unit volume, which is more conducive to increasing the volume energy density of the secondary battery.
[0166] In any embodiment, the surface oxygen valence state of the positive electrode active material is below -1.55, optionally below -1.82, more optionally below -1.88, further optionally below -1.90 or from -1.98 to -1.88, further optionally from -1.98 to -1.89, further optionally from -1.98 to -1.90.
[0167] Therefore, by limiting the surface oxygen valence state of the positive electrode active material within the above range, the interface side reaction between the positive electrode material and the electrolyte can be reduced, thereby improving the cycle performance, high temperature storage gas generation performance and the like of the battery cell.
[0168] The second aspect of the present application also provides a method for preparing a positive electrode active material, which comprises the following steps:
[0169] reacting a manganese source with a source of element B to obtain a manganese salt doped with element B;
[0170] A lithium source, a phosphorus source, an optional source of element A, an optional source of element C, an optional source of element D and a manganese salt doped with element B are mixed, dried, and sintered to obtain a core Li a A x Mn 1-y B y P 1-z C z O 4-n D n ; wherein A, B, C, D, a, x, y, z and n are defined as in the first aspect of the present application.
[0171] Therefore, the present application can obtain significantly improved rate performance by doping a specific element in a specific amount at the Mn position of the compound LiMnPO4 and optionally at the Li position, P position and / or O position, while significantly reducing the dissolution of Mn and the doping element at the Mn position, obtaining significantly improved cycle performance and / or high temperature stability, and the gram capacity and compaction density of the material can also be improved.
[0172] In any embodiment, the method specifically comprises the following steps:
[0173] A manganese source, a source of element B and an acid are mixed and stirred in a solvent to generate a suspension of a manganese salt doped with element B, and the suspension is filtered and a filter cake is dried to obtain a manganese salt doped with element B;
[0174] Adding a lithium source, a phosphorus source, an optional source of element A, an optional source of element C and an optional source of element D, a solvent and a manganese salt doped with element B into a reaction container, grinding and mixing to obtain a slurry;
[0175] The obtained slurry is transferred to a spray drying device for spray drying and granulation to obtain granules;
[0176] The obtained particles are sintered to obtain the core Li a A x Mn 1-y B y P 1-z C z O 4-n D n ; wherein A, B, C, D, a, x, y, z and n are defined as in the first aspect of the present application.
[0177] In any embodiment, in the step of preparing the slurry, a lithium source, a phosphorus source, an optional source of element A, an optional source of element C, an optional source of element D, a carbon source, a source of a carbon layer doping element, a solvent and a manganese salt doped with element B are added to a reaction container, ground and mixed to obtain a slurry; the other steps are the same as above; and a positive electrode active material is obtained;
[0178] The positive electrode active material includes a core and a shell covering the core, wherein the core includes Li a A x Mn 1-y B y P 1-z C z O 4-n D n , the shell comprises doped carbon, and the doping elements in the doped carbon include one or more selected from nitrogen, phosphorus, sulfur, boron and fluorine; wherein A, B, C, D, a, x, y, z and n are defined as in the first aspect of the present application.
[0179] In any embodiment, the method further comprises the steps of:
[0180] coating the surface of the inner core with a mixture of one or more selected from pyrophosphate, phosphate, carbon, doped carbon, oxide, boride and polymer by dry coating or wet coating to obtain a positive electrode active material;
[0181] The positive electrode active material includes a core and a shell covering the core, and the core is Li a A x Mn 1-y B y P 1-z C z O 4-n D n The shell includes one or more coating layers, each coating layer independently includes one or more selected from pyrophosphate, phosphate, carbon, doped carbon, oxide, boride and polymer; wherein A, B, C, D, a, x, y, z and n are defined as in the first aspect of the present application; optionally, the polymer includes one or more selected from polysiloxane, polysaccharide and polysaccharide derivatives.
[0182] In any embodiment, the method further comprises the steps of:
[0183] Provide pyrophosphate M b (P2O7) c Powder, containing phosphatesX m (PO4) q and / or oxide M′ d O e The suspension further comprises a carbon source and / or a carbon-doped source;
[0184] The kernel, pyrophosphate M b (P2O7) c The powder is added to the suspension and mixed, and the positive electrode active material is obtained by sintering; wherein,
[0185] The positive electrode active material includes a core and a shell covering the core, the shell includes a first coating layer covering the core and a second coating layer covering the first coating layer, the core includes Li a A x Mn 1-y B y P 1-z C z O 4-n D n The first coating layer includes pyrophosphate M b (P2O7) c and selected from phosphate X m (PO4) q and oxide M′d O e The second coating layer includes one or more selected from carbon and doped carbon, optionally, the doping element in the doped carbon includes one or more selected from nitrogen, phosphorus, sulfur, boron and fluorine, wherein A, B, C, D, a, x, y, z and n are defined as in the first aspect of the present application, and M, X, M′, b, c, d, e, m, q are defined as in the first aspect of the present application.
[0186] In any embodiment, the method further comprises the steps of:
[0187] Providing pyrophosphate MP2O7 powder and phosphate XPO4 suspension containing a carbon source;
[0188] The core and pyrophosphate MP2O7 powder are added to the XPO4 suspension containing the carbon source and mixed, and the positive electrode active material is obtained by sintering; wherein,
[0189] The positive electrode active material includes a core and a shell covering the core, the shell includes a first coating layer covering the core and a second coating layer covering the first coating layer, the core includes Li a A x Mn 1-y B y P 1-z C z O 4-n D n , the first coating layer includes pyrophosphate MP2O7 and phosphate XPO4, and the second coating layer includes carbon, wherein A, B, C, D, a, x, y, z and n are defined as in the first aspect of the present application, and M and X are defined as in the first aspect of the present application.
[0190] In any embodiment, the method further comprises the steps of:
[0191] Pyrophosphate M b (P2O7) c Suspension, comprising phosphate X m (PO4) q , oxide M′ d O e and a suspension of one or more of a boride and a suspension comprising a source of carbon and / or a source doped with carbon;
[0192] The core is mixed with all the above suspensions and sintered to obtain the positive electrode active material; wherein,
[0193] The positive electrode active material includes a core and a shell covering the core.
[0194] The kernel includes Li a Mn 1-y By P 1-z C z O4, the shell includes a first coating layer covering the core, a second coating layer covering the first coating layer, and a third coating layer covering the second coating layer, the first coating layer includes pyrophosphate M b (P2O7) c The second coating layer includes a phosphate selected from m (PO4) q , oxide M′ d O e and one or more of borides, and the third coating layer is selected from one or more of carbon and doped carbon, wherein A, B, C, D, a, x, y, z and n are defined as in the first aspect of the present application, and M, X, M′, b, c, d, e, m, q are defined as in the first aspect of the present application.
[0195] In any embodiment, the method further comprises the steps of:
[0196] Provide Li f QP2O7 and / or Q g (P2O7) h and XPO4 suspension, adding the core into the suspension and mixing, and sintering to obtain the positive electrode active material; wherein,
[0197] The positive electrode active material includes a core and a shell covering the core, wherein the core includes Li a A x Mn 1-y B y P 1-z C z O 4-n D n The shell includes a first coating layer covering the core, a second coating layer covering the first coating layer, and a third coating layer covering the second coating layer, wherein the first coating layer includes pyrophosphate Li f QP2O7 and / or Q g (P2O7) h The second coating layer includes phosphate XPO4, and the third coating layer includes carbon, wherein A, B, C, D, a, x, y, z and n are defined as in the first aspect of the present application, and Q, X, f, g and h are defined as in the first aspect of the present application.
[0198] In any embodiment, the method further comprises the steps of:
[0199] The first coating step: dissolving a source of element Q, a phosphorus source, an acid, and optionally a lithium source in a solvent to obtain a Li f QP2O7 and / or Q g (P2O7) hThe core and the first coating layer suspension are fully mixed, dried, and sintered to obtain a material coated with the first coating layer;
[0200] The second coating step: dissolving the source of element X, the phosphorus source and the acid in a solvent to obtain a second coating layer suspension containing XPO4; fully mixing the first coating layer coated material obtained in the first coating step with the second coating layer suspension, drying and sintering to obtain a material coated with two coating layers;
[0201] The third coating step: dissolving the carbon source in a solvent and fully dissolving it to obtain a third coating layer solution; then adding the two-layer coating material obtained in the second coating step to the third coating layer solution, mixing evenly, drying, and then sintering to obtain a three-layer coating material, i.e., the positive electrode active material.
[0202] In any embodiment, the method further comprises the steps of:
[0203] Pyrophosphate M b (P2O7) c Powder, selected from phosphate X m (PO4) q , oxide M′ d O e and one or more powders of borides and carbon source powder and / or doped carbon source powder;
[0204] The core is mixed with all the above powders, ground, and dried to obtain a positive electrode active material; wherein,
[0205] The positive electrode active material includes a core and a shell covering the core.
[0206] The kernel includes Li a Mn 1-y B y P 1-z C z O4, the shell includes a first coating layer covering the core, a second coating layer covering the first coating layer, and a third coating layer covering the second coating layer, the first coating layer includes pyrophosphate M b (P2O7) c The second coating layer includes a phosphate selected from m (PO4) q , oxide M′ d O e and one or more of borides, the third coating layer is selected from one or more of carbon and doped carbon, wherein A, B, C, D, a, x, y, z and n and M, X, M', b, c, d, e, m, q are defined as in the first aspect of the present application;
[0207] Alternatively, drying is performed by means of a spray granulation dryer.
[0208] In any embodiment, the method further comprises the steps of:
[0209] Providing a polymer, wherein the polymer includes one or more selected from polysiloxane, polysaccharide and polysaccharide derivatives;
[0210] The positive electrode active material and the polymer are coated by dry coating or wet coating, and the obtained material includes a core and a shell coating the core;
[0211] The one or more coating layers in the shell that are farthest from the core each independently include one or more selected from polysiloxane, polysaccharide and polysaccharide derivatives.
[0212] In any embodiment, the source of element A is selected from at least one of a simple substance, an oxide, a phosphate, an oxalate, a carbonate, and a sulfate of element A; and / or,
[0213] The source of element B is selected from at least one of a simple substance, oxide, phosphate, oxalate, carbonate, halide, nitrate, organic acid salt, hydroxide and sulfate of element B, and may be selected from at least one of a simple substance, oxide, phosphate, oxalate, carbonate and sulfate of element B, and may be selected from at least one of a simple substance, sulfate, halide, nitrate, organic acid salt, oxide and hydroxide of element B, and may be selected from at least one of a simple substance, carbonate, sulfate, chloride, nitrate, organic acid salt, oxide and hydroxide of element B; and / or,
[0214] The source of element C is selected from at least one of a simple substance, a halide, an organic acid salt, an oxide, a hydroxide, an inorganic acid, an organic acid, a sulfate, a borate, a nitrate and a silicate of element C, and may be selected from at least one of a sulfate, a borate, a nitrate and a silicate of element C, and may be selected from at least one of a simple substance, a sulfate, a halide, a nitrate, an organic acid salt, an oxide, a hydroxide and an inorganic acid of element C, and may be selected from at least one of an inorganic acid, an organic acid, a sulfate, a chloride, a nitrate, an organic acid salt, an oxide and a hydroxide of element C; and / or,
[0215] The source of element D is selected from at least one of a simple substance of element D and an ammonium salt.
[0216] In any embodiment, in the step of preparing the manganese salt doped with element B,
[0217] The stirring is carried out at a temperature in the range of 20-120°C, optionally at a temperature in the range of 25-80°C or 40-120°C, further optionally at a temperature in the range of 60-120°C, and / or,
[0218] The stirring is carried out at a stirring rate of 200-800 rpm, optionally at 400-700 rpm for 1-9 hours, more optionally at 500-700 rpm for 60-420 minutes, further optionally at 3-7 hours or 120-360 minutes.
[0219] In any embodiment, in the step of preparing the slurry, grinding and mixing are performed for 1-15 hours, optionally 8-15 hours; optionally, mixing is performed at a temperature of 20-120° C., more preferably 40-120° C. for 1-10 hours.
[0220] In any embodiment, in the step of preparing the inner core, sintering is performed at a temperature ranging from 600 to 900° C. for 6 to 14 hours.
[0221] In any embodiment, the step of preparing the slurry further comprises: adding a carbon source into the reaction container for grinding and mixing.
[0222] In any embodiment, the MP2O7 powder is prepared by the following method:
[0223] A source of element M and a source of phosphorus are added to a solvent to obtain a mixture, the pH of the mixture is adjusted to 4-6, stirred and fully reacted, and then dried and sintered to obtain, wherein M is selected from one or more of Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb and Al.
[0224] In any embodiment, in the method for preparing MP2O7 powder,
[0225] The drying step is to dry at 100-300° C., optionally 150-200° C. for 4-8 hours.
[0226] In any embodiment, in the method for preparing MP2O7 powder,
[0227] The sintering step is to sinter at 500-800° C., optionally 650-800° C., in an inert gas atmosphere for 4-10 hours.
[0228] In any embodiment, the sintering temperature in the coating step is 500-800° C., and the sintering time is 4-10 h.
[0229] In any embodiment, in the first coating step,
[0230] The solution containing the source of element Q, the phosphorus source, the acid and optionally the lithium source is controlled to have a pH of 3.5-6.5, and then stirred and reacted for 1-5 hours, and then the solution is heated to 50-120° C. and maintained at the temperature for 2-10 hours, and / or,
[0231] Sintering is performed at 650-800°C for 2-6 hours.
[0232] In any embodiment, in the second coating step,
[0233] After dissolving the source of element X, the phosphorus source and the acid in a solvent, stirring and reacting for 1-10 hours, then heating the solution to 60-150° C. and maintaining the temperature for 2-10 hours, and / or,
[0234] Sintering is carried out at 500-700°C for 6-10 hours.
[0235] In any embodiment, the sintering in the third coating step is performed at 700-800° C. for 6-10 hours.
[0236] The third aspect of the present application provides a positive electrode plate, which includes a positive electrode collector and a positive electrode film layer arranged on at least one surface of the positive electrode collector, the positive electrode film layer includes a first positive electrode active material, and the first positive electrode active material is the positive electrode active material of the first aspect of the present application or the positive electrode active material prepared by the method of the second aspect of the present application; optionally, the content of the positive electrode active material in the positive electrode film layer is 90-99.5% by weight, and more optionally 95-99.5% by weight, based on the total weight of the positive electrode film layer.
[0237] In any embodiment, the positive electrode sheet further includes a second positive electrode active material, and the second positive electrode active material is different from the first positive electrode active material.
[0238] In any embodiment, the second positive electrode active material includes LiE t Co s F (1-t-s) O2, one or more of spinel lithium manganate and spinel lithium titanate, wherein E includes one or more elements selected from Group VIII, F includes one or more elements selected from Group IIIA and VIIB, t is selected from the range of 0 to 0.9, and the sum of t and s is selected from the range of 0.3 to 1.
[0239] In any embodiment, E includes one or more elements selected from Ni, Fe, Ru and Rh, and F includes one or more elements selected from Mn, Al, Ga and In.
[0240] In any embodiment, the second positive electrode active material is selected from LiNi t Co s Mn (1-t-s) O2、LiNi t Co s Al (1-t-s)O2, LiCoO2, spinel lithium manganese oxide and spinel lithium titanate or more; wherein t is independently selected from 0.3-0.9, and can be selected from 0.33-0.8, and the sum of t and s is independently selected from 0.3-0.9, and can be selected from 0.66-0.9.
[0241] In any embodiment, the mass ratio of the first active material to the second active material is 1:7-7:1, and can be optionally 1:4-4:1.
[0242] In any embodiment, in the second positive electrode active material,
[0243] LiNi t Co s Mn (1-t-s) The ratio of t, (1-ts) and s in O2 is 5:2:3 or 3:1:1 or 8:1:1; and / or,
[0244] LiNi t Co s Al (1-t-s) The ratios of t, s and (1-ts) in O2 are 5:2:3 or 3:1:1 or 8:1:1.
[0245] In any embodiment, the sum of the mass of the first positive electrode active material and the second positive electrode active material accounts for 88% to 98.7% of the mass of the positive electrode sheet.
[0246] The fourth aspect of the present application provides a secondary battery, comprising the positive electrode material of the first aspect of the present application or the positive electrode active material prepared by the method of the second aspect of the present application or the positive electrode plate of the third aspect of the present application.
[0247] A fifth aspect of the present application provides a battery module, comprising the secondary battery of the fourth aspect of the present application.
[0248] The sixth aspect of the present application provides a battery pack, comprising the battery module of the fifth aspect of the present application.
[0249] The seventh aspect of the present application provides an electrical device comprising at least one selected from the secondary battery of the fourth aspect of the present application, the battery module of the fifth aspect of the present application, and the battery pack of the sixth aspect of the present application.
[0250] 1. A positive electrode active material having a chemical formula Li a A x Mn 1-y B y P 1-z C z O 4-n D n ,
[0251] wherein A comprises one or more elements selected from Zn, Al, Na, K, Mg, Nb, Mo and W,
[0252] B includes one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge,
[0253] C includes one or more elements selected from B (boron), S, Si and N,
[0254] D comprises one or more elements selected from S, F, Cl and Br,
[0255] a is selected from the range of 0.9 to 1.1, x is selected from the range of 0.001 to 0.1, y is selected from the range of 0.001 to 0.5, z is selected from the range of 0.001 to 0.1, n is selected from the range of 0.001 to 0.1, and the positive electrode active material is electrically neutral.
[0256] 2. The positive electrode active material of item 1, wherein A, C and D are each independently any one element within the above respective ranges, and B is at least two elements within the ranges;
[0257] Optionally,
[0258] A is any one element selected from Mg and Nb, and / or,
[0259] B is at least two elements selected from Fe, Ti, V, Co and Mg, and optionally Fe and one or more elements selected from Ti, V, Co and Mg, and / or,
[0260] C is S, and / or,
[0261] D is F.
[0262] 3. The positive electrode active material of item 1 or 2, wherein x is selected from the range of 0.001 to 0.005; and / or y is selected from the range of 0.01 to 0.5, optionally selected from the range of 0.25 to 0.5; and / or z is selected from the range of 0.001 to 0.005; and / or n is selected from the range of 0.001 to 0.005.
[0263] 4. The positive electrode active material of any one of items 1 to 3, wherein (1-y):y is in the range of 1 to 4, optionally in the range of 1.5 to 3, and a:x is in the range of 9 to 1100, optionally in the range of 190-998.
[0264] 5. The positive electrode active material according to any one of 1 to 4, wherein the lattice change rate thereof is 8% or less, and optionally 4% or less.
[0265] 6. The positive electrode active material according to any one of 1 to 5, wherein the Li / Mn antisite defect concentration thereof is 2% or less, and optionally 0.5% or less.
[0266] 7. The positive electrode active material according to any one of 1 to 6, wherein the surface oxygen valence state thereof is -1.82 or less, and optionally -1.89 to -1.98.
[0267] 8. The positive electrode active material according to any one of items 1 to 7, wherein the compaction density at 3T is 2.0 g / cm 3 Above, optionally 2.2 g / cm 3 above.
[0268] 9. The positive electrode active material according to any one of 1 to 8, wherein the surface thereof is coated with carbon.
[0269] 10. A method for preparing a positive electrode active material, comprising the following steps:
[0270] (1) dissolving a manganese source, a source of element B and an acid in a solvent and stirring to generate a suspension of a manganese salt doped with element B, filtering the suspension and drying the filter cake to obtain a manganese salt doped with element B;
[0271] (2) adding a lithium source, a phosphorus source, a source of element A, a source of element C, a source of element D, a solvent, and the manganese salt doped with element B obtained in step (1) into a reaction container, grinding and mixing to obtain a slurry;
[0272] (3) transferring the slurry obtained in step (2) to a spray drying device for spray drying and granulation to obtain granules;
[0273] (4) Sintering the particles obtained in step (3) to obtain a positive electrode active material.
[0274] 11. The method of item 10, wherein the source of element A is selected from at least one of a simple substance, oxide, phosphate, oxalate, carbonate and sulfate of element A, the source of element B is selected from at least one of a simple substance, oxide, phosphate, oxalate, carbonate and sulfate of element B, the source of element C is selected from at least one of a sulfate, borate, nitrate and silicate of element C, and the source of element D is selected from at least one of a simple substance and an ammonium salt of element D.
[0275] 12. The method of item 10 or 11, wherein the stirring in step (1) is carried out at a temperature in the range of 60-120° C., and / or,
[0276] The stirring in step (1) is performed at a stirring rate of 200-800 rpm.
[0277] 13. The method according to any one of items 10 to 12, wherein the grinding and mixing in step (2) is performed for 8-15 hours.
[0278] 14. The method according to any one of items 10 to 13, wherein the sintering in step (4) is performed at a temperature in the range of 600-900°C for 6-14 hours.
[0279] 15. The method according to any one of items 10 to 14, wherein step (2) further comprises: adding a carbon source into the reaction container for grinding and mixing.
[0280] 16. A positive electrode sheet, comprising a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, the positive electrode film layer comprising the positive electrode active material of any one of items 1-9 or the positive electrode active material prepared by the method of any one of items 10-15, and the content of the positive electrode active material in the positive electrode film layer is 10 weight % or more, optionally, 95-99.5 weight %, based on the total weight of the positive electrode film layer.
[0281] 17. A secondary battery comprising the positive electrode active material of any one of items 1 to 8 or the positive electrode active material prepared by the method of any one of items 10 to 15 or the positive electrode sheet of item 16.
[0282] 18. A battery module comprising the secondary battery according to item 17.
[0283] 19. A battery pack, comprising the battery module of item 18.
[0284] 20. An electric device comprising at least one selected from the group consisting of the secondary battery of item 17, the battery module of item 18, and the battery pack of item 19.
[0285] 1) A positive electrode active material having a core-shell structure, comprising a core and a shell covering the core,
[0286] The kernel includes Li 1+x Mn 1-y A y P 1-z R z O4, wherein x=-0.100-0.100, y=0.001-0.500, z=0.001-0.100, A is selected from one or more of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and can be selected from one or more of Fe, Ti, V, Ni, Co and Mg, and R is selected from one or more of B, Si, N and S;
[0287] The shell includes a first coating layer covering the inner core and a second coating layer covering the first coating layer.
[0288] Wherein, the first coating layer comprises pyrophosphate MP2O7 and phosphate XPO4, wherein M and X are each independently selected from one or more of Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb or Al;
[0289] The second coating layer includes carbon.
[0290] 2) The positive electrode active material according to item 1), wherein
[0291] The interplanar spacing of the phosphate in the first coating layer is 0.345-0.358 nm, and the angle of the crystal direction (111) is 24.25°-26.45°; the interplanar spacing of the pyrophosphate in the first coating layer is 0.293-0.326 nm, and the angle of the crystal direction (111) is 26.41°-32.57°.
[0292] 3) The positive electrode active material according to item 1) or 2), wherein
[0293] In the kernel, the ratio of y to 1-y is 1:10 to 10:1, and optionally 1:4 to 1:1.
[0294] 4) The positive electrode active material according to any one of items 1) to 3), wherein
[0295] In the kernel, the ratio of z to 1-z is 1:9 to 1:999, and optionally 1:499 to 1:249.
[0296] 5) The positive electrode active material according to any one of items 1) to 4), wherein
[0297] The coating amount of the first coating layer is greater than 0 wt % and less than or equal to 7 wt %, and may be 4-5.6 wt %, based on the weight of the core.
[0298] 6) The positive electrode active material according to any one of 1) to 5), wherein
[0299] The weight ratio of pyrophosphate to phosphate in the first coating layer is 1:3 to 3:1, and can be optionally 1:3 to 1:1.
[0300] 7) The positive electrode active material according to any one of items 1) to 6), wherein
[0301] The crystallinity of the pyrophosphate and the phosphate is each independently from 10% to 100%, optionally from 50% to 100%.
[0302] 8) The positive electrode active material according to any one of 1) to 7), wherein
[0303] The coating amount of the second coating layer is greater than 0 wt % and less than or equal to 6 wt %, and can be optionally 3-5 wt %, based on the weight of the core.
[0304] 9) The positive electrode active material according to any one of items 1) to 8), wherein
[0305] A is selected from at least two of Fe, Ti, V, Ni, Co and Mg.
[0306] 10) The positive electrode active material according to any one of 1) to 9), wherein
[0307] The Li / Mn antisite defect concentration of the positive electrode active material is 4% or less, and may be 2% or less.
[0308] 11) The positive electrode active material according to any one of items 1) to 10), wherein
[0309] The lattice change rate of the positive electrode active material is 6% or less, and may be 4% or less.
[0310] 12) The positive electrode active material according to any one of items 1) to 11), wherein
[0311] The surface oxygen valence state of the positive electrode active material is -1.88 or less, and may be -1.98 to -1.88.
[0312] 13) The positive electrode active material according to any one of items 1) to 12), wherein
[0313] The compaction density of the positive electrode active material at 3 tons is 2.0 g / cm 3 Above, optionally 2.2 g / cm 3 above.
[0314] 14) A method for preparing a positive electrode active material, comprising the following steps:
[0315] Steps for providing core material: The core includes Li 1+x Mn 1-y A y P 1-z R z O4, wherein x=-0.100-0.100, y=0.001-0.500, z=0.001-0.100, A is selected from one or more of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and can be selected from one or more of Fe, Ti, V, Ni, Co and Mg, and R is selected from one or more of B, Si, N and S;
[0316] Coating step: providing MP2O7 powder and XPO4 suspension containing a carbon source, adding the core material and the MP2O7 powder into the XPO4 suspension containing a carbon source and mixing, and sintering to obtain a positive electrode active material, wherein M and X are each independently selected from one or more of Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb or Al;
[0317] Among them, the positive electrode active material has a core-shell structure, which includes an inner core and a shell covering the inner core, the shell includes a first coating layer covering the inner core and a second coating layer covering the first coating layer, the first coating layer includes pyrophosphate MP2O7 and phosphate XPO4, and the second coating layer contains carbon.
[0318] 15) The method for preparing the positive electrode active material of item 14), wherein the step of providing the core material comprises the following steps:
[0319] Step (1): mixing a manganese source, a source of element A and an acid in a container and stirring to obtain manganese salt particles doped with element A;
[0320] Step (2): mixing manganese salt particles doped with element A with a lithium source, a phosphorus source, and a source of element R in a solvent to obtain a slurry, and sintering the slurry under an inert gas atmosphere to obtain lithium manganese phosphate doped with element A and element R, wherein the lithium manganese phosphate doped with element A and element R is Li 1+x Mn 1-y A y P 1-z R z O4, wherein x=-0.100-0.100, y=0.001-0.500, z=0.001-0.100, A is selected from one or more of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and can be selected from one or more of Fe, Ti, V, Ni, Co and Mg, and R is selected from one or more of B, Si, N and S.
[0321] 16) The method according to item 15), wherein
[0322] Step (1) is carried out at a temperature of 20-120° C., optionally 25-80° C.; and / or,
[0323] In step (1), stirring is performed at 500-700 rpm for 60-420 minutes, optionally for 120-360 minutes.
[0324] 17) The method according to any one of items 15) to 16), wherein
[0325] The source of element A is selected from one or more of a simple substance, sulfate, halide, nitrate, organic acid salt, oxide or hydroxide of element A; and / or, the source of element R is selected from one or more of a simple substance, sulfate, halide, nitrate, organic acid salt, oxide or hydroxide of element R and an inorganic acid of element R.
[0326] 18) The method according to any one of items 14) to 17), wherein
[0327] MP2O7 powder was prepared by the following method:
[0328] A source of element M and a source of phosphorus are added to a solvent to obtain a mixture, the pH of the mixture is adjusted to 4-6, stirred and fully reacted, and then dried and sintered to obtain, wherein M is selected from one or more of Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb or Al.
[0329] 19) The method according to item 18), wherein
[0330] The drying step is to dry at 100-300° C., optionally 150-200° C. for 4-8 hours.
[0331] 20) The method according to any one of items 18) to 19), wherein
[0332] The sintering step is to sinter at 500-800° C., optionally 650-800° C., in an inert gas atmosphere for 4-10 hours.
[0333] 21) The method according to any one of items 14) to 20), wherein
[0334] The sintering temperature in the coating step is 500-800°C, and the sintering time is 4-10h.
[0335] 22) A positive electrode sheet, comprising a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, the positive electrode film layer comprising the positive electrode active material of any one of 1)-13) or the positive electrode active material prepared by the method of any one of 14)-21), and the content of the positive electrode active material in the positive electrode film layer is 10 weight % or more, based on the total weight of the positive electrode film layer.
[0336] 23) The positive electrode sheet according to item 22), wherein the content of the positive electrode active material in the positive electrode film layer is 90-99.5 wt %, based on the total weight of the positive electrode film layer.
[0337] 24) A secondary battery comprising the positive electrode active material of any one of 1) to 13) or the positive electrode active material prepared by the method of any one of 14) to 21) or the positive electrode sheet of 22) or 23).
[0338] 25) A battery module, characterized by comprising the secondary battery of item 24).
[0339] 26) A battery pack, characterized in that it comprises the battery module of item 25).
[0340] 27) An electrical device, characterized in that it comprises at least one selected from the secondary battery of item 24), the battery module of item 25) and the battery pack of item 26).
[0341] (1) A positive electrode active material having a core-shell structure, comprising a core and a shell covering the core,
[0342] The chemical formula of the core is Li 1+x Mn 1-y A y P 1-z R z O4, wherein x is any value in the range of -0.100-0.100, y is any value in the range of 0.001-0.500, z is any value in the range of 0.001-0.100, A is one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and can be one or more elements selected from Fe, Ti, V, Ni, Co and Mg, R is one or more elements selected from B, Si, N and S, and optionally, R is an element selected from B, Si, N and S;
[0343] The values of x, y, and z satisfy the following conditions: keep the entire core electrically neutral;
[0344] The shell includes a first coating layer coating the inner core, a second coating layer coating the first coating layer, and a third coating layer coating the second coating layer, wherein:
[0345] The first coating layer includes crystalline pyrophosphate Li a MP2O7 and / or M b (P2O7) c , where 0≤a≤2, 1≤b≤4, 1≤c≤6, and the values of a, b and c satisfy the following conditions: a MP2O7 or M b (P2O7) c Maintain electrical neutrality,
[0346] Crystalline pyrophosphate Li a MP2O7 and M b (P2O7) cEach of the M's is independently one or more elements selected from Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb or Al,
[0347] The second coating layer includes crystalline phosphate XPO4, wherein X is one or more elements selected from Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb or Al;
[0348] The third coating layer is carbon.
[0349] (2) The positive electrode active material having a core-shell structure according to item (1), wherein
[0350] The interplanar spacing of the crystalline pyrophosphate in the first coating layer ranges from 0.293 to 0.470 nm, and the angle of the crystal direction (111) ranges from 18.00° to 32.00°; the interplanar spacing of the crystalline phosphate in the second coating layer ranges from 0.244 to 0.425 nm, and the angle of the crystal direction (111) ranges from 20.00° to 37.00°.
[0351] (3) The positive electrode active material with a core-shell structure according to item (1) or (2), wherein in the inner core, the ratio of y to 1-y is 1:10 to 1:1, and can be optionally 1:4 to 1:1.
[0352] (4) The positive electrode active material having a core-shell structure according to any one of (1) to (4), wherein in the inner core, the ratio of z to 1-z is 1:9 to 1:999, and optionally 1:499 to 1:249.
[0353] (5) A positive electrode active material with a core-shell structure according to any one of items (1) to (4), wherein the carbon in the third coating layer is a mixture of SP2 carbon and SP3 carbon, and optionally, the molar ratio of SP2 carbon to SP3 carbon is any value in the range of 0.1-10, and can be any value in the range of 2.0-3.0.
[0354] (6) The positive electrode active material having a core-shell structure according to any one of (1) to (5), wherein
[0355] The coating amount of the first coating layer is greater than 0 and less than or equal to 6% by weight, optionally greater than 0 and less than or equal to 5.5% by weight, and more optionally greater than 0 and less than or equal to 2% by weight, based on the weight of the kernel; and / or
[0356] The coating amount of the second coating layer is greater than 0 and less than or equal to 6% by weight, optionally greater than 0 and less than or equal to 5.5% by weight, and more optionally 2-4% by weight, based on the weight of the kernel; and / or
[0357] The coating amount of the third coating layer is greater than 0 and less than or equal to 6 wt %, optionally greater than 0 and less than or equal to 5.5 wt %, and more optionally greater than 0 and less than or equal to 2 wt %, based on the weight of the core.
[0358] (7) The positive electrode active material having a core-shell structure according to any one of (1) to (6), wherein the thickness of the first coating layer is 1 to 10 nm; and / or
[0359] The thickness of the second coating layer is 2-15 nm; and / or
[0360] The thickness of the third coating layer is 2-25 nm.
[0361] (8) The positive electrode active material having a core-shell structure according to any one of (1) to (7), wherein
[0362] Based on the weight of the positive electrode active material, the manganese content is in the range of 10 wt%-35 wt%, optionally in the range of 15 wt%-30 wt%, and more optionally in the range of 17 wt%-20 wt%. The phosphorus content is in the range of 12 wt%-25 wt%, optionally in the range of 15 wt%-20 wt%. The weight ratio of manganese to phosphorus is in the range of 0.90-1.25, and optionally in the range of 0.95-1.20.
[0363] (9) A core-shell positive electrode active material according to any one of (1) to (8), wherein the lattice change rate of the core-shell positive electrode active material before and after complete lithium deintercalation is 4% or less, optionally 3.8% or less, and more optionally 2.0-3.8%.
[0364] (10) The positive electrode active material with a core-shell structure according to any one of items (1) to (9), wherein the Li / Mn antisite defect concentration of the positive electrode active material with a core-shell structure is less than 4%, optionally less than 2.2%, and more optionally 1.5-2.2%.
[0365] (11) The positive electrode active material with a core-shell structure according to any one of (1) to (10), wherein the compaction density of the positive electrode active material with a core-shell structure at 3T is 2.2 g / cm 3 Above, optionally 2.2 g / cm 3 Above and 2.8g / cm 3 the following.
[0366] (12) The positive electrode active material having a core-shell structure according to any one of (1) to (11), wherein the surface oxygen valence state of the positive electrode active material having a core-shell structure is -1.90 or less, and optionally -1.90 to -1.98.
[0367] (13) A method for preparing a positive electrode active material, comprising the following steps:
[0368] Steps for providing core material: The core chemical formula is Li 1+x Mn 1-y A y P 1-z R z O4, wherein x is any value in the range of -0.100-0.100, y is any value in the range of 0.001-0.500, z is any value in the range of 0.001-0.100, A is one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and can be one or more elements selected from Fe, Ti, V, Ni, Co and Mg, R is one or more elements selected from B, Si, N and S, and can be selected from B, Si, N and S.
[0369] Coating steps: Provide Li a MP2O7 and / or M b (P2O7) c and XPO4 suspension, adding the core material to the suspension and mixing, and sintering to obtain the positive electrode active material, wherein 0≤a≤2, 1≤b≤4, 1≤c≤6, and the values of a, b and c satisfy the following conditions: a MP2O7 or M b (P2O7) c Maintain electrical neutrality; M is independently one or more elements selected from Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb or Al; X is one or more elements selected from Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb or Al;
[0370] The positive electrode active material has a core-shell structure, which includes a core and a shell covering the core, the shell includes a first coating layer covering the core, a second coating layer covering the first coating layer, and a third coating layer covering the second coating layer, the first coating layer includes crystalline pyrophosphate Li a MP2O7 and / or M b (P2O7) c The second coating layer includes crystalline phosphate XPO4, and the third coating layer is carbon.
[0371] (14) The method for preparing a positive electrode active material according to item (13), wherein the step of providing a core material comprises the following steps:
[0372] Step (1): mixing a manganese source, a dopant of element A and an acid in a container and stirring to obtain manganese salt particles doped with element A;
[0373] Step (2): mixing manganese salt particles doped with element A with a lithium source, a phosphorus source and a dopant of element R in a solvent to obtain a slurry, and sintering under an inert gas atmosphere to obtain a core doped with element A and element R, wherein the core doped with element A and element R is Li 1+x Mn 1-y A y P 1-z R z O4, wherein x is any value in the range of -0.100-0.100, y is any value in the range of 0.001-0.500, z is any value in the range of 0.001-0.100, A is one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and can be one or more elements selected from Fe, Ti, V, Ni, Co and Mg, R is one or more elements selected from B, Si, N and S, and optionally, R is an element selected from B, Si, N and S.
[0374] (15) The method for preparing a positive electrode active material according to item (14), wherein:
[0375] Step (1) is mixed at a temperature of 20-120° C., optionally 40-120° C.; and / or
[0376] In step (1), stirring is performed at 400-700 rpm for 1-9 h, optionally 3-7 h.
[0377] (16) The method for preparing a positive electrode active material according to item (14), wherein step (2) is performed at a temperature of 20-120° C., optionally 40-120° C., for 1-10 h.
[0378] (17) The method for preparing a positive electrode active material according to any one of (14) to (16), wherein:
[0379] The dopant of element A is one or more of the simple substance, carbonate, sulfate, chloride, nitrate, organic acid salt, oxide, hydroxide of one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge; and / or,
[0380] The dopant of element R is one or more of inorganic acids, organic acids, sulfates, chlorides, nitrates, organic acid salts, oxides, hydroxides of one or more elements selected from B, Si, N and S.
[0381] (18) The method for preparing a positive electrode active material according to any one of (13) to (17), wherein the coating step comprises:
[0382] The first coating step: dissolving the source of element M, the phosphorus source and the acid and optionally the lithium source in a solvent to obtain a first coating layer suspension; fully mixing the core obtained in the core step with the first coating layer suspension obtained in the first coating step, drying, and then sintering to obtain a material coated with the first coating layer;
[0383] The second coating step: dissolving the source of element X, the phosphorus source and the acid in a solvent to obtain a second coating layer suspension; fully mixing the first coating layer-coated material obtained in the first coating step with the second coating layer suspension obtained in the second coating step, drying, and then sintering to obtain a material coated with two coating layers;
[0384] The third coating step: dissolving the carbon source in a solvent and fully dissolving it to obtain a third coating layer solution; then adding the two-layer coating material obtained in the second coating step to the third coating layer solution, mixing evenly, drying, and then sintering to obtain a three-layer coating material, i.e., the positive electrode active material.
[0385] (19) The method for preparing a positive electrode active material according to item (18), wherein:
[0386] In the first coating step, the pH of the solution containing the source of element M, the phosphorus source, the acid and optionally the lithium source is controlled to be 3.5-6.5, and then stirred and reacted for 1-5 hours, and then the solution is heated to 50-120° C. and maintained at this temperature for 2-10 hours, and / or,
[0387] Sintering is performed at 650-800°C for 2-6 hours.
[0388] (20) The method for preparing a positive electrode active material according to any one of (18) to (19), wherein:
[0389] In the second coating step, the source of element X, the phosphorus source and the acid are dissolved in a solvent, stirred and reacted for 1-10 hours, and then the solution is heated to 60-150° C. and maintained at this temperature for 2-10 hours, and / or,
[0390] Sintering is carried out at 500-700°C for 6-10 hours.
[0391] (21) The method for preparing a positive electrode active material according to any one of (18) to (20), wherein the sintering in the third coating step is performed at 700 to 800° C. for 6 to 10 hours.
[0392] (22) A positive electrode electrode sheet, comprising a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, the positive electrode film layer comprising a positive electrode active material with a core-shell structure according to any one of (1) to (12) or a positive electrode active material prepared by a positive electrode active material preparation method according to any one of (13) to (21), and the content of the positive electrode active material in the positive electrode film layer is 90-99.5% by weight, and can be optionally 95-99.5% by weight, based on the total weight of the positive electrode film layer.
[0393] (23) A secondary battery comprising the positive electrode active material having a core-shell structure of any one of (1) to (12) or the positive electrode active material prepared by the method for preparing a positive electrode active material of any one of (13) to (21) or the positive electrode sheet of (22).
[0394] (24) A battery module comprising the secondary battery according to item (23).
[0395] (25) A battery pack comprising the battery module according to item (24).
[0396] (26) An electric device comprising at least one selected from the secondary battery of item (23), the battery module of item (24), and the battery pack of item (25). BRIEF DESCRIPTION OF THE DRAWINGS
[0397] Figure 1 Schematic diagram of a core-shell structured positive electrode active material having two coating layers in one embodiment of the present application.
[0398] Figure 2 X-ray diffraction (XRD) patterns of undoped LiMnPO4 and the positive electrode active material prepared in Example I-2.
[0399] Figure 3 Schematic diagram of a positive electrode active material with a core-shell structure having three coating layers in one embodiment of the present application.
[0400] Figure 4 is a schematic diagram of a secondary battery according to one embodiment of the present application.
[0401] Figure 5 yes Figure 4 An exploded view of a secondary battery according to an embodiment of the present application is shown.
[0402] Figure 6 is a schematic diagram of a battery module according to an embodiment of the present application.
[0403] Figure 7 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0404] Figure 8 yes Figure 7 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0405] Fig. 9 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.
[0406] Fig.10 This is the EDS spectrum of the positive electrode active material prepared in Example I-2 of the present application.
[0407] Description of reference numerals:
[0408] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION
[0409] Below, the embodiments of the positive electrode active material and its preparation method, positive electrode sheet, secondary battery, battery module, battery pack and electric device of the present application are specifically disclosed with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0410] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0411] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0412] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0413] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may also include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0414] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, "include" and "comprising" may represent that other components not listed may also be included or only listed components may be included or only listed components may be included.
[0415] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0416] [Secondary battery]
[0417] Secondary batteries, also known as rechargeable batteries or storage batteries, refer to batteries that can continue to be used by recharging the active materials after the battery is discharged.
[0418] Normally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. During the battery charging and discharging process, active ions (such as lithium ions) are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing active ions to pass through. The electrolyte is between the positive electrode sheet and the negative electrode sheet, mainly to conduct active ions.
[0419] [Positive electrode active material]
[0420] One embodiment of the present application provides a positive electrode active material, including a compound represented by formula (I),
[0421] Li a A x Mn 1-y B y P 1-z C z O 4-n D n
[0422] (I)
[0423] in,
[0424] A includes one or more elements selected from Group IA, Group IIA, Group IIIA, Group IIB, Group VB and Group VIB;
[0425] B comprises one or more elements selected from Group IA, Group IIA, Group IIIA, Group IVA, Group VA, Group IIB, Group IVB, Group VB, Group VIB, and Group VIII;
[0426] C includes one or more elements selected from Group IIIA, Group IVA, Group VA and Group VIA;
[0427] D comprises one or more elements selected from Group VIA and Group VIIA;
[0428] a is selected from the range of 0.85 to 1.15;
[0429] x is selected from the range of 0 to 0.1;
[0430] y is selected from the range of 0.001 to 0.999;
[0431] z is selected from the range of 0 to 0.5;
[0432] n is selected from the range of 0 to 0.5.
[0433] Unless otherwise specified, in the above chemical formula, when A is more than two elements, the above-mentioned limitation on the numerical range of x is not only a limitation on the stoichiometric number of each element as A, but also a limitation on the sum of the stoichiometric numbers of each element as A. For example, when A is more than two elements A1, A2...An, the stoichiometric numbers x1, x2...xn of A1, A2...An each need to fall within the numerical range of x defined in this application, and the sum of x1, x2...xn also needs to fall within the numerical range. Similarly, for the case where B, C and D are more than two elements, the limitation on the numerical range of the stoichiometric numbers of B, C and D in this application also has the above meaning.
[0434] The positive electrode active material of the present application is obtained by doping elements in the compound LiMnPO4, wherein A, B, C and D are elements doped in the Li position, Mn position, P position and O position of the compound LiMnPO4, respectively. Without wishing to be limited by theory, it is now believed that the performance improvement of lithium manganese phosphate is related to reducing the lattice change rate of lithium manganese phosphate during lithium insertion and extraction and reducing the surface activity. Reducing the lattice change rate can reduce the lattice constant difference between the two phases at the grain boundary, reduce the interface stress, and enhance the Li +The transmission capacity at the interface improves the rate performance of the positive electrode active material. However, high surface activity can easily lead to serious side reactions at the interface, aggravating gas production, electrolyte consumption and interface damage, thereby affecting the cycle performance of the battery. In the present application, the lattice change rate can be reduced by doping with Li and / or Mn. Mn doping can also effectively reduce the surface activity, thereby inhibiting Mn dissolution and side reactions at the interface between the positive electrode active material and the electrolyte. P-site doping makes the change rate of the Mn-O bond length faster, reduces the migration barrier of the small polaron of the material, and is beneficial to electronic conductivity. O-site doping has a good effect on reducing side reactions at the interface. P-site and / or O-site doping also affects the Mn dissolution and kinetic properties of anti-site defects. Therefore, doping reduces the concentration of anti-site defects in the material, improves the kinetic properties and gram capacity of the material, and can also change the morphology of the particles, thereby improving the compaction density. The applicant unexpectedly discovered that by doping a specific element in a specific amount at the Mn position of the compound LiMnPO4 and optionally at the Li position, P position and / or O position, a significantly improved rate performance can be obtained, while the dissolution of Mn and the doping element at the Mn position is significantly reduced, a significantly improved cycle performance and / or high temperature stability is obtained, and the gram capacity and compaction density of the material are also improved.
[0435] In some embodiments, A includes one or more elements selected from Rb, Cs, Be, Ca, Sr, Ba, Ga, In, Cd, V, Ta, Cr, Zn, Al, Na, K, Mg, Nb, Mo and W, and may optionally include one or more elements selected from Zn, Al, Na, K, Mg, Nb, Mo and W; and / or,
[0436] B includes one or more elements selected from Rb, Cs, Be, Ca, Sr, Ba, In, Pb, Bi, Cd, Hf, Ta, Cr, Ru, Rh, Pd, Os, Ir, Pt, Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and can optionally include one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge; and / or, C includes one or more elements selected from B (boron), S, Si and N; and / or, D includes one or more elements selected from S, F, Cl and Br.
[0437] In some embodiments, A includes any one element selected from Zn, Al, Na, K, Mg, Nb, Mo and W, and may be any one element selected from Mg and Nb; and / or,
[0438] B comprises one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge, and may be selected from at least two elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge, and may be selected from at least two elements selected from Fe, Ti, V, Ni, Co and Mg, and may be further selected from at least two elements selected from Fe, Ti, V, Co and Mg, and may be further selected from Fe and one or more elements selected from Ti, V, Co and Mg; and / or,
[0439] C includes any one element selected from B (boron), S, Si and N, and may be S; and / or,
[0440] D includes any one element selected from S, F, Cl and Br, and may be F.
[0441] By selecting the Li-position doping element within the above range, the lattice change rate during the delithiation process can be further reduced, thereby further improving the rate performance of the battery. By selecting the Mn-position doping element within the above range, the electronic conductivity can be further improved and the lattice change rate can be further reduced, thereby improving the rate performance and gram capacity of the battery. By selecting the P-position doping element within the above range, the rate performance of the battery can be further improved. By selecting the O-position doping element within the above range, the side reactions of the interface can be further reduced and the high temperature performance of the battery can be improved.
[0442] In some embodiments, a is selected from the range of 0.9 to 1.1, optionally selected from the range of 0.97 to 1.01; and / or,
[0443] x is selected from the range of 0.001 to 0.005; and / or,
[0444] y is selected from the range of 0.001 to 0.5, optionally selected from the range of 0.01 to 0.5, optionally selected from the range of 0.25 to 0.5; and / or,
[0445] z is selected from the range of 0.001 to 0.5, optionally selected from the range of 0.001 to 0.1, more optionally selected from the range of 0.001 to 0.005; and / or,
[0446] n is selected from the range of 0 to 0.1, optionally from the range of 0.001 to 0.005.
[0447] Alternatively, x is selected from the range of 0 to 0.005, optionally from the range of 0.001 to 0.1; and / or,
[0448] The y is selected from the range of 0.001 to 0.5, optionally selected from the range of 0.01 to 0.5, optionally selected from the range of 0.25 to 0.5; and / or,
[0449] The z is selected from the range of 0 to 0.5, optionally from the range of 0.001 to 0.5, optionally from the range of 0.001 to 0.1, more optionally from the range of 0.001 to 0.005; and / or,
[0450] Said n is selected from the range of 0 to 0.1, optionally selected from the range of 0.001 to 0.1.
[0451] By selecting the y value within the above range, the gram capacity and rate performance of the material can be further improved. By selecting the x value within the above range, the kinetic performance of the material can be further improved. By selecting the z value within the above range, the rate performance of the secondary battery can be further improved. By selecting the n value within the above range, the high temperature performance of the secondary battery can be further improved.
[0452] In some embodiments, x is 0, z is selected from the range of 0.001 to 0.5, and n is selected from the range of 0.001 to 0.1; or,
[0453] x is selected from the range of 0.001 to 0.1, z is 0, and n is selected from the range of 0.001 to 0.1; or,
[0454] x is selected from the range of 0.001 to 0.1, z is selected from the range of 0.001 to 0.5, and n is 0; or,
[0455] x is 0, z is 0, and n is selected from the range of 0.001 to 0.1; or,
[0456] x is 0, z is selected from the range of 0.001 to 0.5, and n is 0; or,
[0457] x is selected from the range of 0.001 to 0.1, z is selected from the range of 0.001 to 0.5, and n is selected from the range of 0.001 to 0.1.
[0458] Therefore, the present application can significantly improve the rate performance, significantly reduce the dissolution of Mn and the doping elements at the Mn position, significantly improve the cycle performance and / or high temperature stability, and significantly increase the gram capacity and compacted density of the material by doping a specific element at the Mn position of the compound LiMnPO4 and optionally at the Li position, P position and / or O position, especially doping a specific element at the Mn position and P position of LiMnPO4 or at the Li position, Mn position, P position and O position of LiMnPO4.
[0459] In some embodiments, y:z is selected from the range of 0.002 to 999, and may be selected from the range of 0.025 to 999 or the range of 0.002 to 500, and may be selected from the range of 0.2 to 600, such as 0.2, 0.25, 1, 2, 3, 4, 5, 6, 8, 10, 12, 13, 15, 17, 20, 70, 80, 84, 67, 91, 100, 134, 150, 182, 200, 250, 300, 320, 350, 400, 420, 450, 500, 600, 999 or any two of the above values. Thus, the defects of the material can be reduced, the integrity of the material framework structure can be improved, thereby effectively improving the structural stability of the material, and then improving the cycle stability of the secondary battery.
[0460] In some embodiments, z:n is selected from the range of 0.002 to 500, and can be selected from the range of 0.2 to 100, and can be selected from the range of 0.2 to 50, such as 0.2, 0.8, 1, 1.25, 4, 5, 50, or a range consisting of any two of the above values. Thus, the defects of the material can be further reduced, the integrity of the material framework structure can be further improved, the structural stability of the material can be effectively improved, and the cycle stability of the secondary battery can be improved.
[0461] In some embodiments,
[0462] A includes one or more elements selected from Zn, Al, Na, K, Mg, Nb, Mo and W;
[0463] B includes one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge;
[0464] C includes one or more elements selected from B (boron), S, Si and N;
[0465] D comprises one or more elements selected from S, F, Cl and Br;
[0466] a is selected from the range of 0.9 to 1.1, x is selected from the range of 0.001 to 0.1, y is selected from the range of 0.001 to 0.5, z is selected from the range of 0.001 to 0.1, and n is selected from the range of 0.001 to 0.1.
[0467] Therefore, the present application can obtain significantly improved rate performance by doping specific elements in specific amounts at the Li position, Mn position, P position and O position of the compound LiMnPO4, while significantly reducing the dissolution of Mn and the doping elements at the Mn position, thereby obtaining significantly improved cycle performance and / or high temperature stability, and the gram capacity and compaction density of the material can also be improved.
[0468] In some embodiments,
[0469] B comprises one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and optionally one or more elements selected from Zn, Fe, Ti, V, Ni, Co and Mg;
[0470] C is one or more elements selected from B, Si, N and S;
[0471] a is selected from the range of 0.9 to 1.1, x is 0, y is selected from the range of 0.001 to 0.5, z is selected from the range of 0.001 to 0.1, and n is 0.
[0472] Therefore, the present application can improve the rate performance, reduce the dissolution of Mn and the doping elements at the Mn position, improve the cycle performance and / or high temperature stability, and increase the gram capacity and compaction density of the material by doping specific elements at the Mn position and the P position of the compound LiMnPO4 in specific amounts at the same time.
[0473] The average particle size of the core prepared in this application is in the range of 50-500nm. v 50 is 200-300nm. The primary particle size of the core is in the range of 50-500nm, D v 50 is 200-300 nm. Thus, the gram capacity of the secondary battery is improved, and the uniformity of the coating layer on the core is improved.
[0474] In this application, the median particle size D v 50 refers to the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%. In this application, the median particle size D v 50 can be measured by laser diffraction particle size analysis. For example, referring to the standard GB / T19077-2016, a laser particle size analyzer (such as MalvernMaster Size 3000) is used for measurement.
[0475] Through process control (for example, fully mixing and grinding the materials of various sources), it is possible to ensure that each element is evenly distributed in the lattice without aggregation. The main characteristic peak positions in the XRD diagram of lithium manganese phosphate doped with elements B and C are consistent with those of undoped LiMnPO4, indicating that the doping process does not introduce impurity phases. Therefore, the improvement in core performance mainly comes from element doping, rather than impurity phases. After preparing the positive active material of the present application, the inventors of the present application cut the middle area of the prepared positive active material particles by focused ion beam (FIB for short), and tested them by transmission electron microscopy (TEM for short) and X-ray energy spectrum analysis (EDS for short) and found that the elements were evenly distributed without aggregation.
[0476] In some embodiments, the positive electrode active material includes a core and a shell covering the core, wherein the core includes the compound represented by the above formula (I);
[0477] The shell includes one or more coating layers; the coating layers have ion conductivity or electronic conductivity.
[0478] The present application provides a novel positive electrode active material with a core-shell structure by doping a specific element in a specific amount at the Mn position of the compound LiMnPO4 and optionally at the Li position, P position and / or O position to obtain a doped lithium manganese phosphate core, and arranging a coating layer with ionic conductivity or electronic conductivity on the surface of the core. The positive electrode active material is applied to a secondary battery, which can significantly improve the high-temperature cycle performance, cycle stability and high-temperature storage performance of the secondary battery.
[0479] In some embodiments, the shell includes a coating;
[0480] Optionally, the coating layer includes one or more selected from pyrophosphate, phosphate, carbon, doped carbon, oxide, boride and polymer.
[0481] Therefore, the present application adopts the above materials to obtain a coating layer with ionic conductivity or electronic conductivity, thereby improving the high-temperature cycle performance, cycle stability and high-temperature storage performance of the secondary battery.
[0482] In some embodiments, the shell includes a first coating layer coating the inner core and a second coating layer coating the first coating layer;
[0483] Optionally, the first coating layer and the second coating layer each independently include one or more selected from pyrophosphate, phosphate, carbon, doped carbon, oxide, boride and polymer.
[0484] Therefore, the present application adopts the above-mentioned material as the material of the coating layer, and the provision of two coating layers can further improve the high-temperature cycle performance, cycle stability and high-temperature storage performance of the secondary battery.
[0485] In some embodiments, the first coating layer includes one or more selected from pyrophosphate, phosphate, oxide, and boride, and the second coating layer includes one or more selected from carbon and doped carbon.
[0486] Therefore, the present application adopts a first coating layer of a specific material and a second coating layer of a specific material, which can further improve the rate performance and further reduce the dissolution of Mn and Mn-doped elements, thereby improving the cycle performance and / or high temperature stability of the secondary battery.
[0487] In some embodiments, the shell includes a first coating layer coating the inner core, a second coating layer coating the first coating layer, and a third coating layer coating the second coating layer;
[0488] Optionally, the first coating layer, the second coating layer and the third coating layer each independently include one or more selected from pyrophosphate, phosphate, carbon, doped carbon, oxide, boride and polymer.
[0489] Therefore, the present application adopts the above materials as the materials of the coating layer, and setting three layers of coating layers can further reduce the dissolution of Mn and Mn-doped elements, and further improve the high-temperature cycle performance, cycle stability and high-temperature storage performance of the secondary battery.
[0490] In some embodiments, the first coating layer includes pyrophosphate, the second coating layer includes one or more selected from phosphates, oxides, and borides, and the third coating layer includes one or more selected from carbon and doped carbon.
[0491] Therefore, the present application adopts a first coating layer of a specific material, a second coating layer of a specific material, and a third coating layer of a specific material, which further improves the rate performance, further reduces the dissolution of Mn and Mn-doped elements, thereby improving the cycle performance and / or high temperature stability of the secondary battery, and further improves the gram capacity and compaction density of the material.
[0492] In some embodiments, the one or more coating layers each independently include one or more selected from the group consisting of pyrophosphate, phosphate, carbon, doped carbon, oxide, boride, and polymer.
[0493] In some embodiments, the pyrophosphate is b (P2O7) c and / or,
[0494] Phosphate is X m (PO4) q and / or,
[0495] The doping element in the doped carbon includes one or more elements selected from Group IIIA, Group VA, Group VIA and Group VIIA; and / or,
[0496] Oxide is M' d O e and / or,
[0497] Boride is Z v B w and / or,
[0498] The polymer includes one or more selected from polysaccharides and their derivatives, and polysiloxanes;
[0499] in,
[0500] M, X and Z each independently include one or more elements selected from Group IA, Group IIA, Group IIIA, Group IB, Group IIB, Group IVB, Group VB, Group VIIB and Group VIII; b is selected from the range of 1 to 4, c is selected from the range of 1 to 6; m is selected from the range of 1 to 2, q is selected from the range of 1 to 4; M' includes one or more elements selected from alkali metals, alkaline earth metals, transition metals, Group IIIA elements, Group IVA elements, lanthanides and Sb, d is greater than 0 and less than or equal to 2, e is greater than 0 and less than or equal to 5; v is selected from the range of 1 to 7, and w is selected from the range of 1 to 2.
[0501] Therefore, by using the above-mentioned materials as the coating layer, the present application can further reduce the dissolution of Mn and Mn-doping elements, further increase the gram capacity and compaction density of the material, and further improve the rate performance, high-temperature cycle performance and high-temperature storage performance of the secondary battery.
[0502] In some embodiments, M, X and Z each independently include one or more elements selected from Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb and Al; and / or,
[0503] The doping element in the doped carbon includes one or more selected from nitrogen, phosphorus, sulfur, boron and fluorine; and / or,
[0504] M′ comprises one or more elements selected from Li, Be, B, Na, Mg, Al, Si, P, K, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, As, Se, Sr, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Te, W, La and Ce, and may optionally comprise one or more elements selected from Mg, Al, Si, Zn, Zr and Sn; and / or
[0505] The polysiloxane is selected from one or more of linear polysiloxane and cyclic polysiloxane; and / or,
[0506] The polysaccharide is selected from one or more of plant polysaccharides and marine polysaccharides.
[0507] Therefore, the present application can further reduce the dissolution of Mn and Mn-doping elements by using the above-mentioned specific material as the coating layer, and further improve the high-temperature cycle performance and high-temperature storage performance of the secondary battery.
[0508] In some embodiments, the positive electrode active material includes a core and a shell covering the core.
[0509] The kernel includes Li a Mn 1-y B y P 1-z C z O4, wherein a is selected from the range of 0.9 to 1.1, y is selected from the range of 0.001 to 0.5, z is selected from the range of 0.001 to 0.1, B includes one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb, Zn and Ge, and C includes one or more elements selected from B (boron), S, Si and N;
[0510] The shell includes a first coating layer covering the inner core and a second coating layer covering the first coating layer.
[0511] Wherein, the first coating layer comprises pyrophosphate MP2O7 and phosphate XPO4, wherein M and X are each independently selected from one or more of Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb and Al;
[0512] The second coating layer includes carbon.
[0513] like Figure 1As shown, the lithium manganese phosphate positive electrode active material of the present application is a core-shell structure with two layers of coating layers. The element B doped in the manganese position of the core of the lithium manganese phosphate helps to reduce the lattice change rate of the lithium manganese phosphate during the lithium insertion and extraction process, improves the structural stability of the lithium manganese phosphate positive electrode material, greatly reduces the dissolution of manganese and reduces the oxygen activity on the particle surface. The element C doped in the phosphorus position helps to change the difficulty of the Mn-O bond length change, thereby reducing the lithium ion migration barrier, promoting lithium ion migration, and improving the rate performance of the secondary battery. The first coating layer of the positive electrode active material of the present application includes pyrophosphate and phosphate. Since the migration barrier of transition metals in pyrophosphate is high (>1eV), the dissolution of transition metals can be effectively inhibited. Phosphates have excellent lithium ion conductivity and can reduce the surface impurity lithium content. In addition, since the second coating layer is a carbon-containing layer, it can effectively improve the conductivity and desolvation ability of LiMnPO4. In addition, the "barrier" effect of the second coating layer can further hinder the migration of manganese ions into the electrolyte and reduce the corrosion of the electrolyte to the active material. Therefore, the present application can effectively inhibit the dissolution of Mn during the lithium insertion and extraction process by performing specific element doping and surface coating on lithium manganese phosphate, while promoting the migration of lithium ions, thereby improving the rate performance of the battery cell and improving the cycle performance and high temperature performance of the secondary battery.
[0514] It should be pointed out that if Figure 2 As shown, in the present application, by comparing the XRD spectra before and after LiMnPO4 doping, it can be seen that the positions of the main characteristic peaks of the positive electrode active material of the present application are basically consistent with those before LiMnPO4 doping, indicating that the doped lithium manganese phosphate positive electrode active material has no impurity phase, and the improvement in the performance of the secondary battery mainly comes from element doping, rather than impurity phase.
[0515] In some embodiments, the positive electrode active material includes a core and a shell covering the core.
[0516] The kernel includes Li a Mn 1-y B y P 1-z C z O4, wherein a is selected from the range of 0.9 to 1.1, y is selected from the range of 0.001 to 0.5, z is selected from the range of 0.001 to 0.1, B includes one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge, and C includes one or more elements selected from B (boron), S, Si and N;
[0517] The shell includes a first coating layer coating the inner core, a second coating layer coating the first coating layer, and a third coating layer coating the second coating layer, wherein:
[0518] The first coating layer includes pyrophosphate Lif QP2O7 and / or Q g (P2O7) h , where 0≤f≤2, 1≤g≤4, 1≤h≤6, pyrophosphate Li f QP2O7 and / or Q g (P2O7) h Q in which each independently represents one or more elements selected from Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb and Al;
[0519] The second coating layer includes crystalline phosphate XPO4, wherein X is one or more elements selected from Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb and Al;
[0520] The third coating layer includes carbon.
[0521] The positive electrode active material of the present application can improve the gram capacity, cycle performance and safety performance of the secondary battery. Although the mechanism is not clear, it is speculated that the lithium manganese phosphate positive electrode active material of the present application is a core-shell structure, in which the manganese site and phosphorus site of the lithium manganese phosphate core are doped with elements B and C respectively, which can not only effectively reduce manganese dissolution, thereby reducing the manganese ions migrating to the negative electrode, reducing the electrolyte consumed by SEI film decomposition, and improving the cycle performance and safety performance of the secondary battery, but also can promote Mn-O bond adjustment, reduce the lithium ion migration barrier, promote lithium ion migration, and improve the rate performance of the secondary battery; by coating the core with a first coating layer including pyrophosphate, it can Further increase the migration resistance of manganese, reduce its dissolution, reduce the surface impurity lithium content, reduce the contact between the core and the electrolyte, thereby reducing the interface side reaction, reducing gas production, and improving the high temperature storage performance, cycle performance and safety performance of the secondary battery; by further coating with a phosphate coating layer with excellent lithium ion conductivity, the interface side reaction on the surface of the positive electrode active material can be effectively reduced, thereby improving the high temperature cycle and storage performance of the secondary battery; by further coating with a carbon layer as the third coating layer, the safety performance and kinetic performance of the secondary battery can be further improved. In addition, in the core, the element B doped at the manganese position of lithium manganese phosphate also helps to reduce the lattice change rate of lithium manganese phosphate during the process of lithium insertion and extraction, improve the structural stability of the lithium manganese phosphate positive electrode material, greatly reduce the dissolution of manganese and reduce the oxygen activity on the particle surface; the element C doped at the phosphorus position also helps to change the difficulty of the Mn-O bond length change, thereby improving the electronic conductivity and reducing the lithium ion migration barrier, promoting lithium ion migration, and improving the rate performance of the secondary battery.
[0522] Figure 3Schematic diagram of an ideal three-layer coating structure of a positive electrode active material. As shown in the figure, the innermost circle schematically represents the core, and from the inside to the outside are the first coating layer, the second coating layer, and the third coating layer. The figure shows an ideal state in which each layer is completely coated. In practice, each coating layer can be completely coated or partially coated.
[0523] In addition, the entire core system maintains electrical neutrality, which can ensure that there are as few defects and impurities in the positive electrode active material as possible. If there is an excess of transition metal (such as manganese) in the positive electrode active material, since the material system itself has a relatively stable structure, the excess transition metal is likely to precipitate in the form of a single substance or form an impurity phase inside the lattice. Maintaining electrical neutrality can minimize such impurities. In addition, ensuring the electrical neutrality of the system can also produce lithium vacancies in the material in some cases, thereby making the material's kinetic properties more excellent.
[0524] In some embodiments, the one or more coating layers in the shell that are farthest from the core each independently include one or more selected from polysiloxane, polysaccharide, and polysaccharide derivatives.
[0525] As a result, the uniformity of the coating can be improved, and the interfacial side reactions caused by high voltage can be effectively blocked, thereby improving the high-temperature cycle performance and high-temperature storage performance of the material; and the coating layer has good electronic conductivity and ionic conductivity, which helps to improve the gram capacity of the material while reducing the heat generation of the battery cell.
[0526] In some embodiments, the polysiloxane comprises a structural unit represented by formula (i),
[0527]
[0528] Wherein, R1 and R2 are independently selected from H, -COOH, -OH, -SH, -CN, -SCN, amino, phosphate, carboxylate, amide, aldehyde, sulfonyl, polyether segment, C1-C20 aliphatic, C1-C20 halogenated aliphatic, C1-C20 heteroaliphatic, C1-C20 halogenated heteroaliphatic, C6-C20 aromatic, C6-C20 halogenated aromatic, C2-C20 heteroaromatic and C2-C20 halogenated heteroaromatic;
[0529] Optionally, R1 and R2 are independently selected from H, amino, phosphate, polyether segment, C1-C8 alkyl, C1-C8 haloalkyl, C1-C8 heteroalkyl, C1-C8 haloheteroalkyl, C2-C8 alkenyl and C2-C8 haloalkenyl.
[0530] In some embodiments, the polysiloxane further comprises an end-capping group, which includes at least one of the following functional groups: polyether, C1-C8 alkyl, C1-C8 haloalkyl, C1-C8 heteroalkyl, C1-C8 haloheteroalkyl, C2-C8 alkenyl, C2-C8 haloalkenyl, C6-C20 aromatic hydrocarbon group, C1-C8 alkoxy, C2-C8 epoxy, hydroxyl, C1-C8 hydroxyalkyl, amino, C1-C8 aminoalkyl, carboxyl, C1-C8 carboxylalkyl.
[0531] In some embodiments, the polysiloxane includes a polydimethylsiloxane, a polydiethylsiloxane, a polymethylethylsiloxane, a polymethylvinylsiloxane, a polyphenylmethylsiloxane, a polymethylhydrogensiloxane, a carboxyl functionalized polysiloxane, an epoxy-terminated polysiloxane, a methoxy-terminated polydimethylsiloxane, a hydroxypropyl-terminated polydimethylsiloxane, a polymethylchloropropylsiloxane, a hydroxy-terminated polydimethylsiloxane, a polymethyltrifluoropropylsiloxane, a perfluorooctylmethylpolysiloxane, an aminoethylaminopropyl polydimethylsiloxane, a terminal polyether polydimethylsiloxane, a side chain aminopropyl polysiloxane. , aminopropyl-terminated polydimethylsiloxane, side chain phosphate grafted polydimethylsiloxane, side chain polyether grafted polydimethylsiloxane, 1,3,5,7-octamethylcyclotetrasiloxane, 1,3,5,7-tetrahydro-1,3,5,7-tetramethylcyclotetrasiloxane, cyclopentapolydimethylsiloxane, 2,4,6,8-tetramethylcyclotetrasiloxane, 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane, cyclic polymethylvinylsiloxane, hexadecylcyclooctasiloxane, tetradecamethylcycloheptasiloxane, cyclic polydimethylsiloxane or more.
[0532] In some embodiments, the number average molecular weight of polysiloxane, polysaccharide and polysaccharide derivative is independently below 300,000, optionally 10,000 to 200,000, more optionally 20,000 to 120,000, further optionally 400 to 80,000.
[0533] In some embodiments, the mass percentage of polar functional groups in the polysiloxane is α, 0≤α<50%, optionally, 5%≤α≤30%.
[0534] In some embodiments, the substituents attached to the sugar units in the polysaccharides and polysaccharide derivatives each independently include at least one of the following functional groups: -OH, -COOH and salts thereof, -R-OH, -SO3H and salts thereof, -R-OH, -R-SO3H and salts thereof, sulfate, alkoxy, wherein R represents an alkylene group, optionally a C1 to C5 alkylene group;
[0535] Optionally, the substituents attached to the sugar units in the polysaccharides and polysaccharide derivatives each independently include at least one of the group consisting of the following functional groups: -OH, -COOH, -COOLi, -COONa, -COOK, -SO3H, -SO3Li, -SO3Na, -SO3K, -CH2-SO3H, -CH2-SO3Li, -CH2-SO3Na, -CH2-SO3K, methoxy, ethoxy.
[0536] In some embodiments, the polysaccharide includes one or more selected from pectin, carboxymethyl starch, hydroxypropyl starch, dextrin, cellulose ether, carboxymethyl chitosan, hydroxyethyl cellulose, carboxymethyl cellulose, carboxypropyl methyl cellulose, guar gum, sesbania gum, gum arabic, lithium alginate, sodium alginate, potassium alginate, fucoidan, agar, carrageenan, carrageenan, xanthan gum and fenugreek gum.
[0537] In some embodiments, the mass percentage of the substituents attached to the sugar units in the polysaccharide and the polysaccharide derivatives is independently 20% to 85%, optionally 30% to 78%.
[0538] In some embodiments, the lattice mismatch between the material of the core and the material of the shell is less than 10%, thereby enabling good contact between the core and the shell (or coating layer) to prevent the shell (or coating layer) from falling off.
[0539] In some embodiments, based on the weight of the positive electrode active material,
[0540] The manganese content is in the range of 10 wt% to 35 wt%, optionally in the range of 13.3 wt% to 33.2 wt%, more optionally in the range of 15 wt% to 30 wt%, further optionally in the range of 17 wt% to 20 wt%; and / or,
[0541] The phosphorus content is in the range of 12 wt% to 25 wt%, optionally in the range of 15 wt% to 20 wt%, and more optionally in the range of 16.8 wt% to 19.5 wt%; and / or,
[0542] The weight ratio of manganese element to phosphorus element ranges from 0.71 to 1.85, and can be selected from 0.90 to 1.25, and more preferably from 0.95 to 1.20.
[0543] In the present application, in the case where manganese is contained only in the core of the positive electrode active material, the content of manganese may correspond to the content of the core.
[0544] In the present application, limiting the content of manganese element within the above range can further improve the stability and density of the material, thereby improving the cycle, storage and compaction performance of the secondary battery; and can maintain a higher voltage platform, thereby improving the energy density of the secondary battery.
[0545] In the present application, limiting the content of phosphorus within the above range can effectively reduce the influence of small polaron conduction on the conductivity of the material, and can further improve the stability of the lattice structure, thereby affecting the overall stability of the material.
[0546] The weight ratio of manganese to phosphorus content has the following effects on the performance of secondary batteries: it can further reduce manganese dissolution, further improve the stability and gram capacity of the positive electrode active material, and thus affect the cycle performance and storage performance of the secondary battery; it can reduce impurities, further reduce the discharge voltage platform of the material, and thus reduce the energy density of the secondary battery.
[0547] The measurement of manganese and phosphorus can be carried out by conventional technical means in the art. In particular, the following method is used to determine the content of manganese and phosphorus: the material is dissolved in dilute hydrochloric acid (concentration 10-30%), the content of each element in the solution is tested by ICP, and then the content of manganese is measured and converted to obtain its weight percentage.
[0548] In some embodiments, the surface of the positive electrode active material is coated with one or more of carbon and doped carbon; alternatively, the surface of the positive electrode active material is coated with carbon, thereby improving the conductivity of the positive electrode active material.
[0549] In some embodiments, the doping element in the doped carbon includes one or more selected from nitrogen, phosphorus, sulfur, boron and fluorine, so as to facilitate the control of the performance of the doped carbon layer.
[0550] In some embodiments, in the kernel,
[0551] (1-y): y is in the range of 0.1-999, optionally in the range of 0.1-10 or in the range of 0.67-999, more optionally in the range of 1 to 10, further optionally in the range of 1 to 4, and further optionally in the range of 1.5 to 3; and / or,
[0552] a:x is in the range of 1 to 1200, and can be optionally in the range of 9 to 1100, and can be more optionally in the range of 190-998.
[0553] Here, y represents the sum of the stoichiometric numbers of the doping elements at the Mn position. When the above conditions are met, the energy density and cycle performance of the positive electrode active material can be further improved.
[0554] In some embodiments, in the core, the ratio of z to 1-z is 1:9 to 1:999, and optionally 1:499 to 1:249. When the above conditions are met, the energy density and cycle performance of the positive electrode active material can be further improved.
[0555] In some embodiments, the coating amount of the shell is 0.1% to 6%, based on the weight of the core. The coating amount of the coating layer of the present application is preferably within the above range, which can fully coat the core and further improve the kinetic performance and safety performance of the secondary battery without sacrificing the gram capacity of the positive electrode active material.
[0556] In some embodiments, the coating amount of the first coating layer is greater than 0 wt % and less than or equal to 7 wt %, optionally greater than 0 and less than or equal to 6 wt %, more optionally greater than 0 and less than or equal to 5.5 wt % or 4-5.6 wt %, further optionally greater than 0 and less than or equal to 2 wt %, based on the weight of the kernel; and / or,
[0557] The coating amount of the second coating layer is greater than 0 wt % and less than or equal to 6 wt %, optionally greater than 0 and less than or equal to 5.5 wt %, more optionally 2-4 wt % or 3-5 wt %, based on the weight of the kernel; and / or,
[0558] The coating amount of the third coating layer is greater than 0 and less than or equal to 6 wt %, optionally greater than 0 and less than or equal to 5.5 wt %, and more optionally greater than 0 and less than or equal to 2 wt %, based on the weight of the core.
[0559] In some embodiments, the shell further includes a fourth coating layer coating the third coating layer and a fifth coating layer coating the fourth coating layer; wherein,
[0560] The coating amounts of the fourth coating layer and the fifth coating layer are each independently 0.01 to 10 wt %, optionally 0.05 to 10 wt %, more optionally 0.1 to 5 wt %, further 0.1 to 2 wt %, based on the weight of the core.
[0561] In the positive electrode active material with a core-shell structure of the present application, the coating amount of each coating layer is preferably within the above range, thereby being able to fully coat the inner core and at the same time further improve the kinetic performance and safety performance of the secondary battery without sacrificing the gram capacity of the positive electrode active material.
[0562] In some embodiments, the shell is located on 40% to 90% of the surface of the core, and optionally 60% to 80% of the surface, thereby fully coating the core, thereby improving the dynamic performance and safety performance of the secondary battery.
[0563] In some embodiments, the shell has a thickness of 1-15 nm.
[0564] In some embodiments, the thickness of the first coating layer is 1-10 nm, optionally 2-10 nm; and / or,
[0565] The thickness of the second coating layer is 2-25 nm, optionally 2-15 nm, more optionally 3-15 nm; and / or,
[0566] The thickness of the third cladding layer is 2-25 nm, and can be 5-25 nm.
[0567] In some embodiments, the thickness of the first coating layer can be about 2 nm, about 3 nm, about 4 nm, about 5 nm, about 6 nm, about 7 nm, about 8 nm, about 9 nm, or about 10 nm, or any range thereof.
[0568] In some embodiments, the thickness of the second coating layer may be about 2 nm, about 3 nm, about 4 nm, about 5 nm, about 6 nm, about 7 nm, about 8 nm, about 9 nm, about 10 nm, about 11 nm, about 12 nm, about 13 nm, about 14 nm, about 15 nm, or within any range of any of the above values.
[0569] In some embodiments, the thickness of the third coating layer may be about 2 nm, about 3 nm, about 4 nm, about 5 nm, about 6 nm, about 7 nm, about 8 nm, about 9 nm, about 10 nm, about 11 nm, about 12 nm, about 13 nm, about 14 nm, about 15 nm, about 16 nm, about 17 nm, about 18 nm, about 19 nm, about 20 nm, about 21 nm, about 22 nm, about 23 nm, about 24 nm or about 25 nm, or within any range of any of the above values.
[0570] In the present application, the first coating layer has the above-mentioned thickness range, which can further reduce the adverse effects on the kinetic properties of the material and can reduce the problem of being unable to effectively hinder the migration of transition metal ions.
[0571] The second coating layer has the above-mentioned thickness range, so that the surface structure of the second coating layer is stable and the side reaction with the electrolyte is small, so the interface side reaction can be effectively reduced, thereby improving the high temperature performance of the secondary battery.
[0572] The third coating layer has the above-mentioned thickness range, which can enhance the electrical conductivity of the material and improve the compaction density performance of the battery pole piece prepared using the positive electrode active material.
[0573] The thickness test of the coating layer is mainly carried out by FIB. The specific method may include the following steps: randomly select a single particle from the positive electrode active material powder to be tested, cut a thin slice with a thickness of about 100nm from the middle position or near the middle position of the selected particle, and then perform TEM test on the thin slice to measure the thickness of the coating layer, measure 3-5 positions, and take the average value.
[0574] In some embodiments, the one or more coating layers each independently include one or more selected from pyrophosphate, phosphate, and oxide, and the one or more selected from pyrophosphate, phosphate, and oxide is crystalline;
[0575] Optionally, the crystallinity of the pyrophosphate, phosphate and oxide is each independently from 10% to 100%, more preferably from 50% to 100%.
[0576] Herein, crystalline means that the crystallinity is above 50%, i.e., 50%-100%. Crystallinity less than 50% is called glassy state. The crystallinity of the crystalline pyrophosphate and crystalline phosphate of the present application is 50% to 100%.
[0577] Pyrophosphates and phosphates with a certain degree of crystallinity are not only conducive to fully exerting the pyrophosphate coating's ability to hinder manganese dissolution and the phosphate coating's excellent ability to conduct lithium ions and reduce interface side reactions, but also enable the pyrophosphate coating and the phosphate coating to better lattice match, thereby achieving a close bond between the coatings.
[0578] It should be noted that, in the present application, the crystallinity can be adjusted by adjusting the process conditions of the sintering process, such as sintering temperature, sintering time, etc. The crystallinity can be measured by methods known in the art, such as X-ray diffraction, density method, infrared spectroscopy, differential scanning calorimetry, and nuclear magnetic resonance absorption method. The specific method of testing the crystallinity of the positive electrode active material by X-ray diffraction method can include the following steps:
[0579] Take a certain amount of positive electrode active material powder and measure the total scattering intensity by X-ray. It is the sum of the scattering intensities of all matter in space and is only related to the intensity of the primary rays, the chemical structure of the positive electrode active material powder, and the total number of electrons participating in the diffraction, i.e. the mass, but has nothing to do with the order state of the sample. Then separate the crystalline scattering and non-crystalline scattering from the diffraction pattern, and the degree of crystallinity is the ratio of the scattering of the crystalline part to the total scattering intensity.
[0580] In some embodiments, in the shell, the weight ratio of pyrophosphate to phosphate and the weight ratio of pyrophosphate to oxide are independently 1:3 to 3:1, and can be 1:3 to 1:1. Thus, by having pyrophosphate and phosphate in a suitable weight ratio range or pyrophosphate and oxide in a suitable weight ratio range, manganese dissolution can be effectively hindered, and the surface impurity lithium content can be effectively reduced, and the interface side reaction can be reduced, thereby improving the high temperature storage performance, safety performance and cycle performance of the secondary battery.
[0581] In some embodiments, one or more coating layers independently include carbon, and the carbon is a mixture of SP2 carbon and SP3 carbon. Optionally, the molar ratio of SP2 carbon to SP3 carbon in the carbon is any value in the range of 0.07-13, and can be any value in the range of 0.1-10, and can be any value in the range of 2.0-3.0.
[0582] In some embodiments, the molar ratio of SP2 carbon to SP3 carbon may be about 0.1, about 0.2, about 0.3, about 0.4, about 0.5, about 0.6, about 0.7, about 0.8, about 0.9, about 1, about 2, about 3, about 4, about 5, about 6, about 7, about 8, about 9, or about 10, or any range of any of the above values.
[0583] In the present application, "about" a certain numerical value indicates a range, which means a range of ±10% of the numerical value.
[0584] By selecting the form of carbon in the carbon coating layer, the comprehensive electrical performance of the secondary battery is improved. Specifically, by using a mixed form of SP2 carbon and SP3 carbon and limiting the ratio of SP2 carbon to SP3 carbon within a certain range, the following situations can be avoided: if the carbon in the coating layer is all amorphous SP3, the conductivity is poor; if it is all graphitized SP2, although the conductivity is good, there are few lithium ion pathways, which is not conducive to lithium deintercalation. In addition, limiting the molar ratio of SP2 carbon to SP3 carbon within the above range can not only achieve good conductivity, but also ensure the passage of lithium ions, which is beneficial to the realization of the function of the secondary battery and its cycle performance. The mixing ratio of the SP2 and SP3 forms of carbon can be controlled by sintering conditions such as sintering temperature and sintering time. The molar ratio of SP2 carbon to SP3 carbon can be determined by Raman spectroscopy. The specific test method is as follows: by peak decomposing the energy spectrum of the Raman test, Id / Ig (where Id is the peak intensity of SP3 carbon, and Ig is the peak intensity of SP2 carbon) is obtained to confirm the molar ratio of the two.
[0585] In some embodiments, one or more coating layers independently include doped carbon, and the mass content of the doped element in the doped carbon is less than 30%; optionally, the mass content of the doped element in the doped carbon is less than 20%. The doping element within the above content range can not only fully improve the conductivity of the pure carbon layer, but also effectively avoid excessive surface activity caused by excessive doping of the doping element, thereby effectively controlling the interface side reactions caused by excessive doping of the coating layer.
[0586] In some embodiments, one or more coating layers each independently include doped carbon, wherein the doped carbon
[0587] The doping element is nitrogen and / or sulfur, and the mass content of the doping element in the doped carbon is 1% to 15%; or,
[0588] The doping element is phosphorus, boron and / or fluorine, and the mass content of the doping element in the doped carbon is 0.5% to 5%;
[0589] Optionally, the doping element is nitrogen, phosphorus, sulfur, boron or fluorine.
[0590] Since nitrogen atoms and sulfur atoms are closer to the atomic radius of carbon atoms and are not easy to destroy the carbon skeleton, when the doping amount of nitrogen atoms and sulfur atoms is within the above relatively wide range, the conductivity of the doped carbon layer can be fully exerted, and the lithium ion transmission and lithium ion desolvation ability can be promoted.
[0591] Since the atomic radius of phosphorus atoms, boron atoms and / or fluorine atoms is different from that of carbon atoms, excessive doping can easily destroy the carbon skeleton. Therefore, when the doping amount of phosphorus atoms, boron atoms and / or fluorine atoms is within the relatively small range mentioned above, the conductivity of the doped carbon layer can be fully exerted, and the lithium ion transmission and lithium ion desolvation capabilities can be promoted.
[0592] In some embodiments, one or more coating layers independently include pyrophosphate, the interplanar spacing of the pyrophosphate is in the range of 0.293-0.470 nm, optionally 0.297-0.462 nm or 0.293-0.326 nm, more optionally 0.300-0.310 nm, and the angle of the crystal direction (111) is in the range of 18.00°-32.57°, optionally 18.00°-32.00° or 26.41°-32.57°, more optionally 19.211°-30.846°, and further optionally 29.00°-30.00°; and / or,
[0593] The one or more coating layers independently include phosphate, the interplanar spacing of the phosphate is in the range of 0.244-0.425 nm, optionally 0.345-0.358 nm, and the angle of the crystal direction (111) is in the range of 20.00°-37.00°, optionally 24.25°-26.45°;
[0594] Optionally, the first coating layer or the second coating layer comprises a phosphate.
[0595] The first coating layer and the second coating layer in the positive electrode active material of the present application are both made of crystalline materials, and their interplanar spacing and angle ranges are within the above ranges. Thus, the impurity phase in the coating layer can be effectively reduced, thereby improving the material's gram capacity, cycle performance and rate performance.
[0596] In some embodiments, the lattice change rate of the positive electrode active material before and after complete lithium deintercalation is less than 50%, optionally less than 9.8%, more optionally less than 8.1%, further optionally less than 7.5%, further optionally less than 6%, further optionally less than 4%, further optionally less than 3.8%, and further optionally 2.0-3.8%.
[0597] By reducing the lattice change rate, Li ion transmission can be made easier, that is, the mobility of Li ions in the material is stronger, which is beneficial to improve the rate performance of the secondary battery. The lattice change rate can be measured by methods known in the art, such as X-ray diffraction (XRD) patterns.
[0598] In some embodiments, the Li / Mn antisite defect concentration of the positive electrode active material is 5.3% or less, optionally 5.1% or less, more optionally 4% or less, further optionally 2.2% or less, further optionally 2% or less, further optionally 1.5%-2.2% or 0.5% or less.
[0599] The so-called Li / Mn antisite defect refers to the Li + With Mn 2+ The positions of Li / Mn are interchanged. The Li / Mn antisite defect concentration refers to the number of Li / Mn antisite defects in the positive electrode active material. 2+ The exchanged Li + Occupy + The percentage of total antisite defect Mn 2+ Will hinder Li + The transport of Li / Mn antisite defects is beneficial to improve the specific capacity and rate performance of the positive electrode active material by reducing the concentration of Li / Mn antisite defects. The concentration of Li / Mn antisite defects can be measured by methods known in the art, such as XRD.
[0600] In some embodiments, the compaction density of the positive electrode active material at 3T is 1.89 g / cm 3 Above, optional 1.95g / cm 3 Above, 1.98g / cm2 is optional 3 Above, further optional 2.0g / cm 3 Above, further optional 2.2g / cm 3 Above, further optionally 2.2 g / cm 3 Above and 2.8g / cm 3 Below or 2.2g / cm 3 Above and 2.65g / cm 3 the following.
[0601] The higher the compaction density, the greater the weight of the active material per unit volume, so increasing the compaction density is beneficial to increasing the volume energy density of the battery cell. The compaction density can be measured according to GB / T24533-2009.
[0602] In some embodiments, the surface oxygen valence state of the positive electrode active material is below -1.55, optionally below -1.82, more optionally below -1.88, further optionally below -1.90 or from -1.98 to -1.88, further optionally from -1.98 to -1.89, further optionally from -1.98 to -1.90.
[0603] By reducing the surface oxygen valence state, the interfacial side reactions between the positive electrode active material and the electrolyte can be reduced, thereby improving the cycle performance and high temperature stability of the secondary battery. The surface oxygen valence state can be measured by methods known in the art, such as by electron energy loss spectroscopy (EELS).
[0604] [Method for preparing positive electrode active material]
[0605] The present application provides a method for preparing a positive electrode active material, which comprises the following steps:
[0606] reacting a manganese source with a source of element B to obtain a manganese salt doped with element B;
[0607] A lithium source, a phosphorus source, an optional source of element A, an optional source of element C, an optional source of element D and a manganese salt doped with element B are mixed, dried, and sintered to obtain a core Li a A x Mn 1-y B y P 1-z C z O 4-n D n ; wherein A, B, C, D, a, x, y, z and n are defined as in [positive electrode active material].
[0608] Therefore, the present application can obtain significantly improved rate performance by doping a specific element in a specific amount at the Mn position of the compound LiMnPO4 and optionally at the Li position, P position and / or O position, while significantly reducing the dissolution of Mn and the doping element at the Mn position, obtaining significantly improved cycle performance and / or high temperature stability, and the gram capacity and compaction density of the material can also be improved.
[0609] In some embodiments, the method specifically comprises the following steps:
[0610] A manganese source, a source of element B and an acid are mixed and stirred in a solvent to generate a suspension of a manganese salt doped with element B, and the suspension is filtered and a filter cake is dried to obtain a manganese salt doped with element B;
[0611] Adding a lithium source, a phosphorus source, an optional source of element A, an optional source of element C and an optional source of element D, a solvent and a manganese salt doped with element B into a reaction container, grinding and mixing to obtain a slurry;
[0612] The obtained slurry is transferred to a spray drying device for spray drying and granulation to obtain granules;
[0613] The obtained particles are sintered to obtain the core Li a A x Mn 1-y B y P 1-z C z O 4-n D n ; wherein A, B, C, D, a, x, y, z and n are defined as in [positive electrode active material].
[0614] In some embodiments, in the step of preparing the slurry, a lithium source, a phosphorus source, an optional source of element A, an optional source of element C, an optional source of element D, a carbon source, a source of a carbon layer doping element, a solvent and a manganese salt doped with element B are added to a reaction container, ground and mixed to obtain a slurry; the other steps are the same as above; obtaining a positive electrode active material;
[0615] The positive electrode active material includes a core and a shell covering the core, wherein the core includes Li a A x Mn 1-y B y P 1-z C z O 4-n D n The shell contains doped carbon, and the doping element in the doped carbon includes one or more selected from nitrogen, phosphorus, sulfur, boron and fluorine; wherein A, B, C, D, a, x, y, z and n are defined as in [positive electrode active material].
[0616] In some embodiments, the solvents in the step of preparing a manganese salt doped with element B and the step of preparing a slurry can each independently be a solvent conventionally used by those skilled in the art in the preparation of manganese salts and lithium manganese phosphate, for example, they can each independently be selected from at least one of ethanol, water (e.g., deionized water), and the like.
[0617] In some embodiments, the method further comprises the steps of:
[0618] coating the surface of the inner core with a mixture of one or more selected from pyrophosphate, phosphate, carbon, doped carbon, oxide, boride and polymer by dry coating or wet coating to obtain a positive electrode active material;
[0619] The positive electrode active material includes a core and a shell covering the core, and the core is Li a A x Mn 1-y B y P 1-z C z O 4-n D n The shell includes one or more coating layers, each coating layer independently includes one or more selected from pyrophosphate, phosphate, carbon, doped carbon, oxide, boride and polymer; wherein A, B, C, D, a, x, y, z and n are defined as in [positive electrode active material]; optionally, the polymer includes one or more selected from polysiloxane, polysaccharide and polysaccharide derivatives.
[0620] In some embodiments, the method further comprises the steps of:
[0621] Provide pyrophosphate M b (P2O7) c Powder, containing phosphatesX m (PO4) q and / or oxide M′ d O e The suspension further comprises a carbon source and / or a carbon-doped source;
[0622] The kernel, pyrophosphate M b (P2O7) c The powder is added to the suspension and mixed, and the positive electrode active material is obtained by sintering; wherein,
[0623] The positive electrode active material includes a core and a shell covering the core, the shell includes a first coating layer covering the core and a second coating layer covering the first coating layer, the core includes Li a A x Mn 1-y B y P1-z C z O 4-n D n The first coating layer includes pyrophosphate M b (P2O7) c and selected from phosphate X m (PO4) q and oxide M′ d O e The second coating layer includes one or more selected from carbon and doped carbon, optionally, the doping element in the doped carbon includes one or more selected from nitrogen, phosphorus, sulfur, boron and fluorine, wherein A, B, C, D, a, x, y, z and n are defined as in [positive electrode active material], and M, X, M′, b, c, d, e, m, q are defined as in [positive electrode active material].
[0624] In some embodiments, the method further comprises the steps of:
[0625] Providing pyrophosphate MP2O7 powder and phosphate XPO4 suspension containing a carbon source;
[0626] The core and pyrophosphate MP2O7 powder are added to the XPO4 suspension containing the carbon source and mixed, and the positive electrode active material is obtained by sintering; wherein,
[0627] The positive electrode active material includes a core and a shell covering the core, the shell includes a first coating layer covering the core and a second coating layer covering the first coating layer, the core includes Li a A x Mn 1-y B y P 1-z C z O 4-n D n The first coating layer includes pyrophosphate MP2O7 and phosphate XPO4, and the second coating layer includes carbon, wherein A, B, C, D, a, x, y, z and n are defined as in [positive electrode active material], and M and X are defined as in [positive electrode active material].
[0628] In some embodiments, the method further comprises the steps of:
[0629] Pyrophosphate M b (P2O7) c Suspension, comprising phosphate X m (PO4) q , oxide M′ d O e and a suspension of one or more of a boride and a suspension comprising a source of carbon and / or a source doped with carbon;
[0630] The core is mixed with all the above suspensions and sintered to obtain the positive electrode active material; wherein,
[0631] The positive electrode active material includes a core and a shell covering the core.
[0632] The kernel includes Li a Mn 1-y B y P 1-z C z O4, the shell includes a first coating layer covering the core, a second coating layer covering the first coating layer, and a third coating layer covering the second coating layer, the first coating layer includes pyrophosphate M b (P2O7) c The second coating layer includes a phosphate selected from m (PO4) q , oxide M′ d O e and one or more of borides, and the third coating layer is selected from one or more of carbon and doped carbon, wherein A, B, C, D, a, x, y, z and n are defined as in [positive electrode active material], and M, X, M′, b, c, d, e, m, q are defined as in [positive electrode active material].
[0633] In some embodiments, the method further comprises the steps of:
[0634] Provide Li f QP2O7 and / or Q g (P2O7) h and XPO4 suspension, adding the core into the suspension and mixing, and sintering to obtain the positive electrode active material; wherein,
[0635] The positive electrode active material includes a core and a shell covering the core, wherein the core includes Li a A x Mn 1-y B y P 1-z C z O 4-n D n The shell includes a first coating layer covering the core, a second coating layer covering the first coating layer, and a third coating layer covering the second coating layer, wherein the first coating layer includes pyrophosphate Li f QP2O7 and / or Q g (P2O7) h The second coating layer includes phosphate XPO4, and the third coating layer includes carbon, wherein A, B, C, D, a, x, y, z and n are defined as in [positive electrode active material], and Q, X, f, g and h are defined as in [positive electrode active material].
[0636] In some embodiments, the method further comprises the steps of:
[0637] The first coating step: dissolving a source of element Q, a phosphorus source, an acid, and optionally a lithium source in a solvent to obtain a Li f QP2O7 and / or Q g (P2O7) h The core and the first coating layer suspension are fully mixed, dried, and sintered to obtain a material coated with the first coating layer;
[0638] The second coating step: dissolving the source of element X, the phosphorus source and the acid in a solvent to obtain a second coating layer suspension containing XPO4; fully mixing the first coating layer coated material obtained in the first coating step with the second coating layer suspension, drying and sintering to obtain a material coated with two coating layers;
[0639] The third coating step: dissolving the carbon source in a solvent and fully dissolving it to obtain a third coating layer solution; then adding the two-layer coating material obtained in the second coating step to the third coating layer solution, mixing evenly, drying, and then sintering to obtain a three-layer coating material, i.e., the positive electrode active material.
[0640] In some embodiments, the method further comprises the steps of:
[0641] Pyrophosphate M b (P2O7) c Powder, selected from phosphate X m (PO4) q , oxide M′ d O e and one or more powders of borides and carbon source powder and / or doped carbon source powder;
[0642] The core is mixed with all the above powders, ground, and dried to obtain a positive electrode active material; wherein,
[0643] The positive electrode active material includes a core and a shell covering the core.
[0644] The kernel includes Li a Mn 1-y B y P 1-z C z O4, the shell includes a first coating layer covering the core, a second coating layer covering the first coating layer, and a third coating layer covering the second coating layer, the first coating layer includes pyrophosphate M b (P2O7) c The second coating layer includes a phosphate selected from m (PO4) q , oxide M′d O e and one or more of borides, the third coating layer is selected from one or more of carbon and doped carbon, wherein A, B, C, D, a, x, y, z and n and M, X, M′, b, c, d, e, m, q are as defined in [positive electrode active material];
[0645] Alternatively, drying is performed by means of a spray granulation dryer.
[0646] In some embodiments, the method further comprises the steps of:
[0647] Providing a polymer, wherein the polymer includes one or more selected from polysiloxane, polysaccharide and polysaccharide derivatives;
[0648] The positive electrode active material and the polymer are coated by dry coating or wet coating, and the obtained material includes a core and a shell coating the core;
[0649] The one or more coating layers in the shell that are farthest from the core each independently include one or more selected from polysiloxane, polysaccharide and polysaccharide derivatives.
[0650] In any embodiment, the source of element A is selected from at least one of a simple substance, an oxide, a phosphate, an oxalate, a carbonate, and a sulfate of element A; and / or,
[0651] The source of element B is selected from at least one of a simple substance, oxide, phosphate, oxalate, carbonate, halide, nitrate, organic acid salt, hydroxide and sulfate of element B, and may be selected from at least one of a simple substance, oxide, phosphate, oxalate, carbonate and sulfate of element B, and may be selected from at least one of a simple substance, sulfate, halide, nitrate, organic acid salt, oxide and hydroxide of element B, and may be selected from at least one of a simple substance, carbonate, sulfate, chloride, nitrate, organic acid salt, oxide and hydroxide of element B; and / or,
[0652] The source of element C is selected from at least one of a simple substance, a halide, an organic acid salt, an oxide, a hydroxide, an inorganic acid, an organic acid, a sulfate, a borate, a nitrate and a silicate of element C, and may be selected from at least one of a sulfate, a borate, a nitrate and a silicate of element C, and may be selected from at least one of a simple substance, a sulfate, a halide, a nitrate, an organic acid salt, an oxide, a hydroxide and an inorganic acid of element C, and may be selected from at least one of an inorganic acid, an organic acid, a sulfate, a chloride, a nitrate, an organic acid salt, an oxide and a hydroxide of element C; and / or,
[0653] The source of element D is selected from at least one of a simple substance of element D and an ammonium salt.
[0654] In some embodiments, the acid is selected from one or more of hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, organic acid such as oxalic acid, etc., for example, oxalic acid. In some embodiments, the acid is a dilute acid with a concentration of 60 wt % or less.
[0655] In some embodiments, the manganese source may be a manganese-containing substance known in the art that can be used to prepare lithium manganese phosphate. For example, the manganese source may be selected from elemental manganese, manganese dioxide, manganese phosphate, manganese oxalate, manganese carbonate, or a combination thereof.
[0656] In some embodiments, the lithium source may be a lithium-containing material known in the art that can be used to prepare lithium manganese phosphate. For example, the lithium source may be selected from one of lithium carbonate, lithium hydroxide, lithium phosphate, lithium dihydrogen phosphate, or a combination thereof.
[0657] In some embodiments, the phosphorus source may be a phosphorus-containing substance known in the art that can be used to prepare lithium manganese phosphate, for example, the phosphorus source may be selected from one of diammonium hydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate and phosphoric acid, or a combination thereof.
[0658] The amount of each source of elements A, B, C, and D added depends on the target doping amount, and the ratio of the amount of lithium source, manganese source, and phosphorus source used conforms to the stoichiometric ratio.
[0659] In any embodiment, in the step of preparing the manganese salt doped with element B,
[0660] The stirring is carried out at a temperature in the range of 20-120°C, optionally at a temperature in the range of 25-80°C or 40-120°C, further optionally at a temperature in the range of 60-120°C, and / or,
[0661] The stirring is carried out at a stirring rate of 200-800 rpm, optionally at 400-700 rpm for 1-9 hours, more optionally at 500-700 rpm for 60-420 minutes, further optionally at 3-7 hours or 120-360 minutes.
[0662] In some embodiments, in the step of preparing the slurry, grinding and mixing are performed for 1-15 hours, optionally 8-15 hours; optionally, mixing is performed at a temperature of 20-120° C., more preferably 40-120° C. for 1-10 hours.
[0663] By controlling the reaction temperature, stirring rate and mixing time during doping, the doping elements can be evenly distributed and the crystallinity of the material after sintering can be higher, thereby improving the material's gram capacity and rate performance.
[0664] In some embodiments, the filter cake may be washed before drying the filter cake in the step of preparing the manganese salt doped with element B.
[0665] In some embodiments, the drying in the step of preparing the manganese salt doped with element B can be performed by methods and conditions known to those skilled in the art, for example, the drying temperature can be in the range of 120-300° C. Optionally, the filter cake can be ground into particles after drying, for example, ground to a median particle size Dv of 0.04-0.08. 50 In the range of 50-200nm. Among them, the median particle size Dv 50 It refers to the particle size corresponding to the cumulative volume distribution percentage of the positive electrode active material reaching 50%. In this application, the median particle size Dv of the core is 50 The particle size can be determined by laser diffraction particle size analysis, for example, by referring to the standard GB / T 19077-2016 and using a laser particle size analyzer (such as Malvern Master Size 3000).
[0666] In some embodiments, in the step of preparing the slurry, a carbon source is also added to the reaction vessel for grinding and mixing. Thus, the method can obtain a positive electrode active material with a surface coated with carbon. Optionally, the carbon source includes one or a combination of starch, sucrose, glucose, polyvinyl alcohol, polyethylene glycol, and citric acid. The amount of the carbon source is generally in the range of 0.1%-5% by molar ratio relative to the amount of the lithium source. Grinding can be performed by a suitable grinding method known in the art, for example, by sand milling.
[0667] The temperature and time of spray drying may be conventional in the art, for example, at 100-300° C. for 1-6 hours.
[0668] In some embodiments, in the step of preparing the inner core, sintering is performed at a temperature ranging from 600 to 900° C. for 6 to 14 hours.
[0669] In some embodiments, the sintering is performed under a protective atmosphere, which may be nitrogen, an inert gas, hydrogen, or a mixture thereof.
[0670] In some embodiments, the MP2O7 powder is a commercially available product, or the MP2O7 powder is prepared by the following method:
[0671] A source of element M and a source of phosphorus are added to a solvent to obtain a mixture, the pH of the mixture is adjusted to 4-6, stirred and fully reacted, and then dried and sintered to obtain, wherein M is selected from one or more of Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb and Al.
[0672] In some embodiments, in the method for preparing MP2O7 powder,
[0673] The drying step is to dry at 100-300° C., optionally 150-200° C. for 4-8 hours.
[0674] In some embodiments, in the method for preparing MP2O7 powder,
[0675] The sintering step is to sinter at 500-800° C., optionally 650-800° C., in an inert gas atmosphere for 4-10 hours.
[0676] In some embodiments, the sintering temperature in the coating step is 500-800° C., and the sintering time is 4-10 h.
[0677] In some embodiments, the XPO4 suspension containing a carbon source is commercially available, or is prepared by the following method: a lithium source, an X source, a phosphorus source, and a carbon source are uniformly mixed in a solvent, and then the reaction mixture is heated to 60-120° C. and maintained for 2-8 hours to obtain the XPO4 suspension containing a carbon source. Optionally, in the process of preparing the XPO4 suspension containing a carbon source, the pH of the mixture is adjusted to 4-6.
[0678] In some embodiments, in the step of preparing the positive electrode active material, the mass ratio of the core, the MP2O7 powder and the XPO4 suspension containing the carbon source is: 1: (0.001-0.05): (0.001-0.05).
[0679] In some embodiments, in the first coating step,
[0680] The solution containing the source of element Q, the phosphorus source, the acid and optionally the lithium source is controlled to have a pH of 3.5-6.5, and then stirred and reacted for 1-5 hours, and then the solution is heated to 50-120° C. and maintained at the temperature for 2-10 hours, and / or,
[0681] Sintering is performed at 650-800°C for 2-6 hours.
[0682] In some embodiments, in the second coating step,
[0683] After dissolving the source of element X, the phosphorus source and the acid in a solvent, stirring and reacting for 1-10 hours, then heating the solution to 60-150° C. and maintaining the temperature for 2-10 hours, and / or,
[0684] Sintering is carried out at 500-700°C for 6-10 hours.
[0685] In some embodiments, the sintering in the third coating step is performed at 700-800° C. for 6-10 hours.
[0686] [Positive electrode]
[0687] The positive electrode plate includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, the positive electrode film layer includes a first positive electrode active material, and the first positive electrode active material is the aforementioned positive electrode active material or the positive electrode active material prepared by the aforementioned method; optionally, the content of the positive electrode active material in the positive electrode film layer is 90-99.5% by weight, and more optionally 95-99.5% by weight, based on the total weight of the positive electrode film layer.
[0688] In some embodiments, the positive electrode sheet further includes a second positive electrode active material, and the second positive electrode active material is different from the first positive electrode active material.
[0689] In some embodiments, the second positive electrode active material includes LiE t Co s F (1-t-s) O2, one or more of spinel lithium manganate and spinel lithium titanate, wherein E includes one or more elements selected from Group VIII, F includes one or more elements selected from Group IIIA and VIIB, t is selected from the range of 0 to 0.9, and the sum of t and s is selected from the range of 0.3 to 1.
[0690] In some embodiments, E includes one or more elements selected from Ni, Fe, Ru, and Rh, and F includes one or more elements selected from Mn, Al, Ga, and In.
[0691] In some embodiments, the second positive electrode active material is selected from LiNi t Co s Mn (1-t-s) O2、LiNi t Co s Al (1-t-s) O2, LiCoO2, spinel lithium manganese oxide and spinel lithium titanate or more; wherein t is independently selected from 0.3-0.9, and can be selected from 0.33-0.8, and the sum of t and s is independently selected from 0.3-0.9, and can be selected from 0.66-0.9.
[0692] In some embodiments, the mass ratio of the first active material to the second active material is 1:7-7:1, and can be 1:4-4:1.
[0693] In some embodiments, in the second positive electrode active material,
[0694] LiNi t Co s Mn (1-t-s) The ratio of t, (1-ts) and s in O2 is 5:2:3 or 3:1:1 or 8:1:1; and / or,
[0695] LiNi tCo s Al (1-t-s) The ratios of t, s and (1-ts) in O2 are 5:2:3 or 3:1:1 or 8:1:1.
[0696] In some embodiments, the sum of the mass of the first positive electrode active material and the second positive electrode active material accounts for 88% to 98.7% of the mass of the positive electrode sheet.
[0697] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0698] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0699] In some embodiments, the positive electrode active material may also be a positive electrode active material for a battery known in the art. As an example, the positive electrode active material may include at least one of the following materials: an olivine-structured lithium-containing phosphate, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more.
[0700] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0701] In some embodiments, the positive electrode film layer may further include a conductive agent, for example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0702] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0703] [Negative electrode]
[0704] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer arranged on at least one surface of the negative electrode current collector, and the negative electrode film layer includes a negative electrode active material.
[0705] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0706] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0707] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0708] In some embodiments, the negative electrode film layer may further include a binder. As an example, the binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0709] In some embodiments, the negative electrode film layer may further include a conductive agent. As an example, the conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0710] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0711] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0712] [Electrolytes]
[0713] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0714] In some embodiments, the electrolyte is liquid and includes an electrolyte salt and a solvent.
[0715] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0716] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0717] In some embodiments, the electrolyte may further include additives. As examples, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0718] [Isolation film]
[0719] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0720] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0721] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0722] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0723] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0724] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 4 The secondary battery 5 is a square structure as an example.
[0725] In some embodiments, reference Figure 5 , the outer package may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0726] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0727] Figure 6 4 is an example of a battery module. Figure 6In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0728] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0729] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0730] Figure 7 and Figure 8 1 is a battery pack 1 as an example. Figure 7 and Figure 8 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0731] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0732] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.
[0733] Fig. 9 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0734] [Example]
[0735] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0736] The sources of raw materials involved in the embodiments of this application are as follows:
[0737]
[0738]
[0739] [Preparation of positive electrode active materials including core and battery]
[0740] Example I-1
[0741] 1) Preparation of positive electrode active materials
[0742] Preparation of doped manganese oxalate: 1.3 mol of MnSO4﹒H2O and 0.7 mol of FeSO4﹒H2O were fully mixed in a mixer for 6 hours. The mixture was transferred to a reactor, and 10 L of deionized water and 2 mol of dihydrated oxalic acid (calculated as oxalic acid) were added. The reactor was heated to 80°C and stirred at 600 rpm for 6 hours. The reaction was terminated (no bubbles were generated) to obtain a Fe-doped manganese oxalate suspension. The suspension was then filtered, and the filter cake was dried at 120°C and then ground to obtain a median particle size Dv 50 Fe-doped manganese oxalate particles with a size of about 100 nm.
[0743] Preparation of doped lithium manganese phosphate: Take 1 mol of the above manganese oxalate particles, 0.497 mol of lithium carbonate, 0.001 mol of Mo(SO4)3, an aqueous phosphoric acid solution containing 0.999 mol of phosphoric acid at a concentration of 85%, 0.001 mol of H4SiO4, 0.0005 mol of NH4HF2 and 0.005 mol of sucrose and add them to 20L of deionized water. Transfer the mixture to a sand mill and grind and stir it for 10 hours to obtain a slurry. Transfer the slurry to a spray drying equipment for spray drying and granulation, set the drying temperature to 250°C, dry for 4 hours, and obtain particles. In a protective atmosphere of nitrogen (90 volume %) + hydrogen (10 volume %), sinter the above powder at 700°C for 10 hours to obtain a carbon-coated Li 0.994 Mo 0.001 Mn 0.65 Fe 0.35 P 0.999 Si 0.001 O 3.999 F 0.001The element content of the positive electrode active material can be detected by inductively coupled plasma emission spectroscopy (ICP).
[0744] 2) Preparation of button cells
[0745] The positive electrode active material, polyvinylidene fluoride (PVDF), and acetylene black were added to N-methylpyrrolidone (NMP) at a weight ratio of 90:5:5, and stirred in a drying room to form a slurry. The slurry was coated on aluminum foil, dried, and cold pressed to form a positive electrode sheet. The coating amount was 0.2 g / cm 2 , compacted density is 2.0g / cm 3 .
[0746] A lithium sheet was used as the negative electrode, and a solution of 1 mol / L LiPF6 in ethylene carbonate (EC), diethyl carbonate (DEC) and dimethyl carbonate (DMC) in a volume ratio of 1:1:1 was used as the electrolyte. Together with the positive electrode sheet prepared above, they were assembled into a button battery (hereinafter also referred to as "button battery") in a button box.
[0747] 3) Preparation of full battery
[0748] The positive electrode active material, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) were mixed uniformly in an N-methylpyrrolidone solvent system at a weight ratio of 92:2.5:5.5, and then coated on an aluminum foil, dried, and cold pressed to obtain a positive electrode sheet. The coating amount was 0.4 g / cm 2 , compacted density is 2.4g / cm 3 .
[0749] The negative electrode active material artificial graphite, hard carbon, conductive agent acetylene black, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) were mixed evenly in deionized water at a weight ratio of 90:5:2:2:1, coated on copper foil, dried, and cold pressed to obtain a negative electrode sheet. The coating amount was 0.2g / cm 2 , compacted density is 1.7g / cm 3 .
[0750] Using a polyethylene (PE) porous polymer film as a separator, the positive electrode sheet, separator, and negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrodes to play a role of isolation, and then wound to obtain a bare cell. The bare cell is placed in an outer package, injected with the same electrolyte as in the above preparation of the buckle battery, and packaged to obtain a full battery (hereinafter also referred to as "full battery").
[0751] Example I-2
[0752] Except that in "1) Preparation of positive electrode active material", the amount of high-purity Li2CO3 was changed to 0.4885 mol, Mo(SO4)3 was replaced by MgSO4, the amount of FeSO4﹒H2O was changed to 0.68 mol, 0.02 mol of Ti(SO4)2 was added when preparing doped manganese oxalate, and H4SiO4 was replaced by HNO3, the rest was the same as Example I-1.
[0753] Example I-3
[0754] Except that in “1) Preparation of positive electrode active material”, the amount of high-purity Li2CO3 is changed to 0.496 mol, Mo(SO4)3 is replaced by W(SO4)3, and H4SiO4 is replaced by H2SO4, the rest is the same as Example I-1.
[0755] Example I-4
[0756] Except that in "1) Preparation of positive electrode active material", the amount of high-purity Li2CO3 is changed to 0.4985 mol, 0.001 mol of Mo(SO4)3 is replaced by 0.0005 mol of Al2(SO4)3 and NH4HF2 is replaced by NH4HCl2, the rest is the same as Example I-1.
[0757] Example I-5
[0758] The above steps are the same as those in Example I-1, except that in “1) Preparation of positive electrode active material”, 0.7 mol of FeSO4﹒H2O is replaced by 0.69 mol, 0.01 mol of VCl2 is added when preparing doped manganese oxalate, the amount of Li2CO3 is changed to 0.4965 mol, 0.001 mol of Mo(SO4)3 is replaced by 0.0005 mol of Nb2(SO4)5 and H4SiO4 is replaced by H2SO4.
[0759] Example I-6
[0760] Except that in "1) Preparation of positive electrode active material", the amount of FeSO4﹒H2O is changed to 0.68 mol, 0.01 mol of VCl2 and 0.01 mol of MgSO4 are added when preparing doped manganese oxalate, the amount of Li2CO3 is changed to 0.4965 mol, 0.001 mol of Mo(SO4)3 is replaced by 0.0005 mol of Nb2(SO4)5 and H4SiO4 is replaced by H2SO4, the rest is the same as Example I-1.
[0761] Example I-7
[0762] Except that MgSO4 is replaced by CoSO4 in "1) Preparation of positive electrode active material", the rest is the same as Example I-6.
[0763] Example I-8
[0764] Except that MgSO4 is replaced by NiSO4 in "1) Preparation of positive electrode active material", the rest is the same as Example I-6.
[0765] Example I-9
[0766] The present invention is the same as that in Example I-1, except that in "1) Preparation of positive electrode active material", the amount of FeSO4﹒H2O is changed to 0.698 mol, 0.002 mol of Ti(SO4)2 is added when preparing doped manganese oxalate, the amount of Li2CO3 is changed to 0.4955 mol, 0.001 mol of Mo(SO4)3 is replaced by 0.0005 mol of Nb2(SO4)5, H4SiO4 is replaced by H2SO4, and NH4HF2 is made into NH4HCl2.
[0767] Example I-10
[0768] Except that in "1) Preparation of positive electrode active material", the amount of FeSO4﹒H2O is changed to 0.68 mol, 0.01 mol of VCl2 and 0.01 mol of MgSO4 are added when preparing doped manganese oxalate, the amount of Li2CO3 is changed to 0.4975 mol, 0.001 mol of Mo(SO4)3 is replaced by 0.0005 mol of Nb2(SO4)5 and NH4HF2 is replaced by NH4HBr2, the rest is the same as Example I-1.
[0769] Example I-11
[0770] Except that in "1) Preparation of positive electrode active material", the amount of FeSO4﹒H2O was changed to 0.69 mol, 0.01 mol of VCl2 was added when preparing doped manganese oxalate, the amount of Li2CO3 was changed to 0.499 mol, Mo(SO4)3 was replaced by MgSO4 and NH4HF2 was replaced by NH4HBr2, the rest was the same as Example I-1.
[0771] Example I-12
[0772] The preparation method was the same as that in Example I-1, except that in "1) Preparation of positive electrode active material", the amount of MnSO4﹒H2O was changed to 1.36 mol, the amount of FeSO4﹒H2O was changed to 0.6 mol, 0.04 mol of VCl2 was added when preparing doped manganese oxalate, the amount of Li2CO3 was changed to 0.4985 mol, Mo(SO4)3 was replaced by MgSO4 and H4SiO4 was replaced by HNO3, and the rest was the same as that in Example I-1 to obtain Li 0.99 7Mg 0.001 Mn 0.68 Fe 0.3 V 0.02 P 0.999 N 0.001 O 3.999 F 0.001
[0773] Example I-13
[0774] The process was the same as that of Example I-12 except that in “1) Preparation of positive electrode active material” the amount of MnSO4.H2O was changed to 1.16 mol and the amount of FeSO4.H2O was changed to 0.8 mol.
[0775] Example I-14
[0776] Except that in “1) Preparation of positive electrode active material”, the amount of MnSO4.H2O was changed to 1.3 mol and the amount of VCl2 was changed to 0.1 mol, the rest was the same as Example I-12.
[0777] Example I-15
[0778] Except that in "1) Preparation of positive electrode active material", the amount of MnSO4﹒H2O was changed to 1.2 mol, 0.1 mol of VCl2 was added when preparing doped manganese oxalate, the amount of Li2CO3 was changed to 0.494 mol, 0.001 mol of Mo(SO4)3 was replaced by 0.005 mol of MgSO4 and H4SiO4 was replaced by H2SO4, the rest was the same as Example I-1.
[0779] Example I-16
[0780] The following are the same as in Example I-1 except that in “1) Preparation of positive electrode active material”, the amount of MnSO4﹒H2O is changed to 1.2 mol, 0.1 mol of VCl2 is added when preparing doped manganese oxalate, the amount of Li2CO3 is changed to 0.467 mol, 0.001 mol of Mo(SO4)3 is replaced by 0.005 mol of MgSO4, 0.001 mol of H4SiO4 is replaced by 0.005 mol of H2SO4, and 1.175 mol of 85% phosphoric acid is replaced by 1.171 mol of 85% phosphoric acid.
[0781] Example I-17
[0782] The preparation method is the same as that in Example I-1, except that in "1) Preparation of positive electrode active material", the amount of MnSO4﹒H2O is changed to 1.2 mol, 0.1 mol of VCl2 is added when preparing doped manganese oxalate, the amount of Li2CO3 is changed to 0.492 mol, 0.001 mol of Mo(SO4)3 is replaced by 0.005 mol of MgSO4, H4SiO4 is replaced by H2SO4 and 0.0005 mol of NH4HF2 is changed to 0.0025 mol.
[0783] Example I-18
[0784] The following are the same as in Example I-1 except that in “1) Preparation of positive electrode active material”, the amount of FeSO4﹒H2O is changed to 0.5 mol, 0.1 mol of VCl2 and 0.1 mol of CoSO4 are added when preparing doped manganese oxalate, the amount of Li2CO3 is changed to 0.492 mol, 0.001 mol of Mo(SO4)3 is replaced by 0.005 mol of MgSO4, H4SiO4 is replaced by H2SO4 and 0.0005 mol of NH4HF2 is changed to 0.0025 mol.
[0785] Example I-19
[0786] The process was the same as that of Example I-18 except that in “1) Preparation of positive electrode active material” the amount of FeSO4.H2O was changed to 0.4 mol and 0.1 mol of CoSO4 was changed to 0.2 mol.
[0787] Example I-20
[0788] The method is the same as that of Example I-18 except that in “1) Preparation of positive electrode active material”, the amount of MnSO4.H2O is changed to 1.5 mol, the amount of FeSO4.H2O is changed to 0.1 mol, and the amount of CoSO4 is changed to 0.3 mol.
[0789] Example I-21
[0790] Except that in “1) Preparation of positive electrode active material”, 0.1 mol of CoSO 4 was replaced with 0.1 mol of NiSO 4, the rest was the same as Example I-18.
[0791] Example I-22
[0792] The above method is the same as Example I-18 except that in “1) Preparation of positive electrode active material”, the amount of MnSO4.H2O is changed to 1.5 mol, the amount of FeSO4.H2O is changed to 0.2 mol, and 0.1 mol of CoSO4 is replaced by 0.2 mol of NiSO4.
[0793] Example I-23
[0794] The process was the same as that of Example I-18 except that in “1) Preparation of positive electrode active material”, the amount of MnSO4.H2O was changed to 1.4 mol, the amount of FeSO4.H2O was changed to 0.3 mol, and the amount of CoSO4 was changed to 0.2 mol.
[0795] Example I-24
[0796] The present invention is the same as Example I-1 except that in "1) Preparation of positive electrode active material", 1.3 mol of MnSO4﹒H2O is changed to 1.2 mol, 0.7 mol of FeSO4﹒H2O is changed to 0.5 mol, 0.1 mol of VCl2 and 0.2 mol of CoSO4 are added when preparing doped manganese oxalate, the amount of Li2CO3 is changed to 0.497 mol, 0.001 mol of Mo(SO4)3 is replaced by 0.005 mol of MgSO4, H4SiO4 is replaced by H2SO4 and 0.0005 mol of NH4HF2 is changed to 0.0025 mol.
[0797] Example I-25
[0798] The method is the same as that of Example I-18 except that in “1) Preparation of positive electrode active material”, the amount of MnSO4.H2O is changed to 1.0 mol, the amount of FeSO4.H2O is changed to 0.7 mol, and the amount of CoSO4 is changed to 0.2 mol.
[0799] Example I-26
[0800] Except that in "1) Preparation of positive electrode active material", the amount of MnSO4﹒H2O was changed to 1.4 mol, the amount of FeSO4﹒H2O was changed to 0.3 mol, 0.1 mol of VCl2 and 0.2 mol of CoSO4 were added when preparing doped manganese oxalate, the amount of Li2CO3 was changed to 0.4825 mol, 0.001 mol of Mo(SO4)3 was replaced by 0.005 mol of MgSO4, the amount of H4SiO4 was changed to 0.1 mol, the amount of phosphoric acid was changed to 0.9 mol and the amount of NH4HF2 was changed to 0.04 mol, the rest was the same as Example I-1.
[0801] Example I-27
[0802] Except that in "1) Preparation of positive electrode active material", the amount of MnSO4﹒H2O was changed to 1.4 mol, the amount of FeSO4﹒H2O was changed to 0.3 mol, 0.1 mol of VCl2 and 0.2 mol of CoSO4 were added when preparing doped manganese oxalate, the amount of Li2CO3 was changed to 0.485 mol, 0.001 mol of Mo(SO4)3 was replaced by 0.005 mol of MgSO4, the amount of H4SiO4 was changed to 0.08 mol, the amount of phosphoric acid was changed to 0.92 mol and the amount of NH4HF2 was changed to 0.05 mol, the rest was the same as Example I-1.
[0803] Examples I-28 to I-41
[0804] The stirring speed, temperature, grinding and stirring time in a sand mill, sintering temperature and sintering time were changed when preparing doped manganese oxalate, as shown in Table 13.
[0805] Examples I-42 to I-54
[0806] The sources of lithium source, manganese source, phosphorus source and doping elements A, B, C, D were changed, see Table 14 for details.
[0807] Example I-55
[0808] (1) Preparation of doped manganese oxalate
[0809] 1.2 mol MnSO4·H2O and 0.79 mol FeSO4·H2O were fully mixed in a mixer for 6 hours; the mixture was transferred to a reactor, 10 L of deionized water and 2 mol of dihydrated oxalic acid and 0.01 mol VCl2 were added, heated to 80°C, and then stirred at 600 rpm for 6 hours, the reaction was terminated (no bubbles were generated), and a suspension of Fe-doped manganese oxalate was obtained; the suspension was filtered, the filter cake was dried at 120°C, and ground to obtain a particle size of Dv 50Fe-doped manganese oxalate particles of about 100 nm;
[0810] (2) Preparation of doped lithium manganese phosphate
[0811] Take 1 mol of Fe-doped manganese oxalate particles, 0.45 mol of lithium carbonate, 0.05 mol of MgSO4, 85% phosphoric acid aqueous solution containing 0.9 mol of phosphoric acid, 0.1 mol of H4SiO4, 0.05 mol of NH4HF2 and 0.005 mol of sucrose and add them to 20L of deionized water, transfer the mixture into a sand mill and grind and stir for 10 hours to obtain a slurry; transfer the slurry to a spray drying device for spray drying and granulation, set the drying temperature to 250°C, dry for 4 hours to obtain particles; sinter the particles at 700°C for 10 hours in a nitrogen (90% v / v) + hydrogen (10% v / v) protective atmosphere to obtain a positive electrode active material. The element content is detected by inductively coupled plasma emission spectroscopy (ICP) to obtain the chemical formula Li 0.9 Mg 0.05 Mn 0.6 Fe 0.395 V 0.00 5P 0.9 Si 0.1 O 3.9 F 0.1 .
[0812] Example I-56
[0813] Except that in step (2), lithium carbonate is 0.55 mol, MgSO4 is 0.001 mol, and NH4HF2 is 0.001 mol, the rest is the same as in Preparation Example B55; the positive electrode active material Li 1.1 Mg 0.001 Mn 0.6 Fe 0.395 V 0.005 P 0.9 Si 0.1 O 3.998 F 0.002 .
[0814] Example I-57
[0815] Except that in step (2), MgSO4 is 0.1 mol, the 85% phosphoric acid aqueous solution contains 0.95 mol phosphoric acid, H4SiO4 is 0.05 mol, and NH4HF2 is 0.025 mol, the rest is the same as Preparation Example B55; the positive electrode active material Li 0.9 Mg 0.1 Mn 0.6 Fe 0.395 V 0.005 P 0.95Si 0.05 O 3.95 F 0.05 .
[0816] Example I-58
[0817] The steps are the same as those in Preparation Example B55 except that in step (1), MnSO4·H2O is 1.998 mol, FeSO4·H2O is 0.002 mol, and VCl2 is not used; and in step (2), lithium carbonate is 0.475 mol, the 85% phosphoric acid aqueous solution contains 0.96 mol phosphoric acid, H4SiO4 is 0.04 mol, and NH4HF2 is 0.01 mol; the rest is the same as that in Preparation Example B55; the positive electrode active material Li 0.95 Mg 0.05 Mn 0.999 Fe 0.001 P 0.96 Si 0.04 O 3.99 F 0.01 .
[0818] Example I-59
[0819] The steps are the same as those in Preparation Example B55 except that in step (1), MnSO4·H2O is 1.98 mol, FeSO4·H2O is 0.02 mol, and VCl2 is not used; and in step (2), lithium carbonate is 0.475 mol, the 85% phosphoric acid aqueous solution contains 0.96 mol phosphoric acid, H4SiO4 is 0.04 mol, and NH4HF2 is 0.01 mol; the rest is the same as in Preparation Example B55; the positive electrode active material Li 0.95 Mg 0.05 Mn 0.9 9Fe 0.01 P 0.96 Si 0.04 O 3.99 F 0.01 .
[0820] Example I-60
[0821] The steps are the same as those in Preparation Example B55 except that in step (1), MnSO4·H2O is 1.6 mol, FeSO4·H2O is 0.4 mol, and VCl2 is not used; and in step (2), lithium carbonate is 0.475 mol, the 85% phosphoric acid aqueous solution contains 0.96 mol phosphoric acid, H4SiO4 is 0.04 mol, and NH4HF2 is 0.01 mol; the rest is the same as that in Preparation Example B55; the positive electrode active material Li 0.95 Mg 0.05 Mn 0. 8Fe 0.2 P 0.96 Si 0.04O 3.99 F 0.01 .
[0822] Example I-61
[0823] Preparation of Fe, Co and V co-doped manganese oxalate: 689.5g manganese carbonate (in MnCO3, the same below), 455.2g ferrous carbonate (in FeCO3, the same below), 4.6g cobalt sulfate (in CoSO4, the same below) and 4.9g vanadium dichloride (in VCl2, the same below) are fully mixed in a mixer for 6 hours. The mixture is transferred to a reactor, and 5 liters of deionized water and 1260.6g dihydrated oxalic acid (in C2H2O4.2H2O, the same below) are added. The reactor is heated to 80°C and stirred at a speed of 600rpm for 6 hours until the reaction is terminated (no bubbles are generated) to obtain a Fe, Co, V and S co-doped manganese oxalate suspension. The suspension is then filtered, the filter cake is dried at 120°C, and then ground to obtain Fe, Co and V co-doped dihydrated manganese oxalate particles with a median particle size Dv50 of 100nm.
[0824] Preparation of Fe, Co, V and S co-doped lithium manganese phosphate: Add the manganese oxalate dihydrate particles (1793.4 g) obtained in the previous step, 314 g lithium carbonate (calculated as Li2CO3, the same below), 89.8 g MgSO4, 1.6 g dilute sulfuric acid with a concentration of 60% (calculated as 60% H2SO4, the same below) and 1148.9 g diammonium phosphate (calculated as NH4H2PO4, the same below) to 20 liters of deionized water, and stir the mixture for 10 hours to mix it evenly to obtain a slurry. Transfer the slurry to a spray drying equipment for spray drying and granulation, set the drying temperature to 250°C, dry for 4 hours, and obtain a powder. In a nitrogen (90 volume %) + hydrogen (10 volume %) protective atmosphere, sinter the above powder at 700°C for 4 hours to obtain Li 0.85 Mg 0.075 Mn 0.60 Fe 0.393 V 0.004 Co 0.003 P 0.999 S 0.00 1O4.
[0825] Example I-62
[0826] Without adding MgSO4, the mass of lithium carbonate is 425g, and the rest is the same as in Example I-61, to obtain Li 1.15 Mn 0.60 Fe 0.393 V 0.004 Co 0.003 P 0.999 S 0.001 O4.
[0827] Example I-63
[0828] Without adding cobalt sulfate, vanadium dichloride and MgSO4, the mass of manganese carbonate is 1.149g, the mass of ferrous carbonate is 1157g, the mass of lithium carbonate is 425g, and the rest is the same as in Example I-61, to obtain Li 1.15 Mn 0.001 Fe 0.999 P 0.999 S 0.00 1O4.
[0829] Example I-64
[0830] Without adding Mo(SO4)3, lithium carbonate was adjusted to 0.575 mol, MnSO4﹒H2O was adjusted to 0.002 mol, FeSO4﹒H2O was adjusted to 1.998 mol, phosphoric acid was adjusted to 0.5 mol of 85% phosphoric acid aqueous solution, 0.5 mol of H2SO4 was used to replace 0.001 mol of H4SiO4, manganese oxalate particles were adjusted to 0.875 mol, NH4HF2 was adjusted to 0.25 mol, and the rest was the same as in Example I-1 to obtain Li 1.15 Mn 0.001 Fe 0.999 P 0.5 S 0.5 O 3.5 F 0.5 .
[0831] Example I-65
[0832] Without adding MgSO4, the amount of Li2CO3 was changed to 0.499 mol, and the rest was the same as in Example I-12 to obtain Li 0.998 Mn 0.68 Fe 0.3 V 0.02 P 0.999 N 0.001 O 3.999 F 0.001 .
[0833] Example I-66
[0834] Without adding HNO3, the concentration of phosphoric acid was adjusted to 1 mol with an aqueous solution of 85% phosphoric acid, and the rest was the same as in Example I-12 to obtain Li 0.997 Mg 0.001 Mn 0.68 Fe 0.3 V 0.02 PO 3.999 F 0.001 .
[0835] Example I-67
[0836] Without adding NH4HF2, the rest is the same as in Example I-12 to obtain Li 0.997 Mg 0.001 Mn 0.68 Fe 0.3 V 0.02 P 0.999 N 0.00 1O4.
[0837] Example I-68
[0838] Without adding MgSO4 and HNO3, the amount of Li2CO3 was changed to 0.499 mol, the concentration of phosphoric acid was adjusted to 1 mol of 85% phosphoric acid aqueous solution, and the rest was the same as in Example I-12 to obtain Li 0.998 Mn 0.68 Fe 0.3 V 0.02 PO 3.999 F 0.001 .
[0839] Example I-2-1
[0840] 1) Preparation of positive electrode active materials
[0841] Preparation of doped manganese oxalate: 1.3 mol of MnSO4﹒H2O and 0.7 mol of FeSO4﹒H2O were fully mixed in a mixer for 6 hours. The mixture was transferred to a reactor, and 10 L of deionized water and 2 mol of dihydrated oxalic acid (calculated as oxalic acid) were added. The reactor was heated to 80°C and stirred at 600 rpm for 6 hours. The reaction was terminated (no bubbles were generated) to obtain a Fe-doped manganese oxalate suspension. The suspension was then filtered, and the filter cake was dried at 120°C and then ground to obtain a median particle size Dv 50 Fe-doped manganese oxalate particles with a size of about 100 nm.
[0842] Preparation of doped lithium manganese phosphate: Take 1 mol of the above manganese oxalate particles, 0.497 mol of lithium carbonate, 0.001 mol of Mo(SO4)3, an aqueous phosphoric acid solution containing 0.999 mol of phosphoric acid at a concentration of 85%, 0.001 mol of H4SiO4, 0.0005 mol of NH4HF2, 0.05 mol of sucrose and 0.025 mol of ethylenediamine and add them to 20L of deionized water. Transfer the mixture to a sand mill and grind and stir it for 10 hours to obtain a slurry. Transfer the slurry to a spray drying equipment for spray drying and granulation, set the drying temperature to 250°C, dry for 4 hours, and obtain particles. In a protective atmosphere of nitrogen (90 volume %) + hydrogen (10 volume %), sinter the above powder at 700°C for 10 hours to obtain Li doped with a carbon layer. 0.994 Mo 0.001Mn 0.65 Fe 0.35 P 0.999 Si 0.00 1O 3.999 F 0.001 .
[0843] 2) Preparation of button cells
[0844] The positive electrode active material, polyvinylidene fluoride (PVDF), and acetylene black were added to N-methylpyrrolidone (NMP) at a weight ratio of 90:5:5, and stirred in a drying room to form a slurry. The slurry was coated on aluminum foil, dried, and cold pressed to form a positive electrode sheet. The coating amount was 0.2 g / cm 2 , compacted density is 2.0g / cm 3 .
[0845] A lithium sheet was used as the negative electrode, and a solution of 1 mol / L LiPF6 in ethylene carbonate (EC), diethyl carbonate (DEC) and dimethyl carbonate (DMC) in a volume ratio of 1:1:1 was used as the electrolyte. Together with the positive electrode sheet prepared above, they were assembled into a button battery (hereinafter also referred to as "button battery") in a button box.
[0846] 3) Preparation of full battery
[0847] The positive electrode active material, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) were mixed uniformly in an N-methylpyrrolidone solvent system at a weight ratio of 92:2.5:5.5, and then coated on an aluminum foil, dried, and cold pressed to obtain a positive electrode sheet. The coating amount was 0.4 g / cm 2 , compacted density is 2.4g / cm 3 .
[0848] The negative electrode active material artificial graphite, hard carbon, conductive agent acetylene black, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) were mixed evenly in deionized water at a weight ratio of 90:5:2:2:1, coated on copper foil, dried, and cold pressed to obtain a negative electrode sheet. The coating amount was 0.2g / cm 2 , compacted density is 1.7g / cm 3 .
[0849] Using a polyethylene (PE) porous polymer film as a separator, the positive electrode sheet, separator, and negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrodes to play a role of isolation, and then wound to obtain a bare cell. The bare cell is placed in an outer package, injected with the same electrolyte as in the above preparation of the buckle battery, and packaged to obtain a full battery (hereinafter also referred to as "full battery").
[0850] Example I-2-2
[0851] The preparation method is the same as that in Example 1, except that in "1) Preparation of positive electrode active material", the amount of high-purity Li2CO3 is changed to 0.4885 mol, Mo(SO4)3 is replaced by MgSO4, the amount of FeSO4﹒H2O is changed to 0.68 mol, 0.02 mol of Ti(SO4)2 is added when preparing doped manganese oxalate, and H4SiO4 is replaced by HNO3.
[0852] Comparative Example I-1
[0853] Preparation of manganese oxalate: Add 1 mol of MnSO4﹒H2O to a reactor, and add 10L of deionized water and 1 mol of dihydrated oxalic acid (calculated as oxalic acid). Heat the reactor to 80°C and stir at 600rpm for 6 hours. The reaction is terminated (no bubbles are generated) to obtain a manganese oxalate suspension. Then filter the suspension, dry the filter cake at 120°C, and then grind it to obtain a median particle size Dv 50 The manganese oxalate particles are 50-200nm.
[0854] Preparation of lithium manganese phosphate: Take 1 mol of the above manganese oxalate particles, 0.5 mol of lithium carbonate, 85% phosphoric acid aqueous solution containing 1 mol of phosphoric acid and 0.005 mol of sucrose and add them to 20L of deionized water. Transfer the mixture to a sand mill and grind and stir it for 10 hours to obtain a slurry. Transfer the slurry to a spray drying equipment for spray drying and granulation, set the drying temperature to 250°C, dry for 4 hours, and obtain particles. In a protective atmosphere of nitrogen (90 volume %) + hydrogen (10 volume %), sinter the above powder at 700°C for 10 hours to obtain carbon-coated LiMnPO4.
[0855] Comparative Example I-2
[0856] The process is the same as that of Comparative Example I-1, except that 1 mol of MnSO4﹒H2O is replaced with 0.85 mol of MnSO4﹒H2O and 0.15 mol of FeSO4﹒H2O, which are added to the mixer and mixed thoroughly for 6 hours before being added to the reactor.
[0857] Comparative Example I-3
[0858] Except that in "1) Preparation of positive electrode active material", the amount of MnSO4﹒H2O was changed to 1.9 mol, 0.7 mol of FeSO4﹒H2O was replaced by 0.1 mol of ZnSO4, the amount of Li2CO3 was changed to 0.495 mol, 0.001 mol of Mo(SO4)3 was replaced by 0.005 mol of MgSO4, the amount of phosphoric acid was changed to 1 mol, and H4SiO4 and NH4HF2 were not added, the rest was the same as Example I-1.
[0859] Comparative Example I-4
[0860] Except that in "1) Preparation of positive electrode active material", the amount of MnSO4﹒H2O was changed to 1.2 mol, the amount of FeSO4﹒H2O was changed to 0.8 mol, the amount of Li2CO3 was changed to 0.45 mol, 0.001 mol of Mo(SO4)3 was replaced by 0.005 mol of Nb2(SO4)5, 0.999 mol of phosphoric acid was changed to 1 mol, 0.0005 mol of NH4HF2 was changed to 0.025 mol, and H4SiO4 was not added, the rest was the same as Example I-1.
[0861] Comparative Example I-5
[0862] Except that in "1) Preparation of positive electrode active material", the amount of MnSO4﹒H2O was changed to 1.4 mol, the amount of FeSO4﹒H2O was changed to 0.6 mol, the amount of Li2CO3 was changed to 0.38 mol, and 0.001 mol of Mo(SO4)3 was replaced by 0.12 mol of MgSO4, the rest was the same as Example I-1.
[0863] Comparative Example I-6
[0864] Except that in "1) Preparation of positive electrode active material", the amount of MnSO4﹒H2O was changed to 0.8 mol, 0.7 mol of FeSO4﹒H2O was replaced by 1.2 mol of ZnSO4, the amount of Li2CO3 was changed to 0.499 mol, and 0.001 mol of Mo(SO4)3 was replaced by 0.001 mol of MgSO4, the rest was the same as Example I-1.
[0865] Comparative Example I-7
[0866] Except that in “1) Preparation of positive electrode active material”, the amount of MnSO4﹒H2O was changed to 1.4 mol, the amount of FeSO4﹒H2O was changed to 0.6 mol, the amount of Li2CO3 was changed to 0.534 mol, 0.001 mol of Mo(SO4)3 was replaced by 0.001 mol of MgSO4, the amount of phosphoric acid was changed to 0.88 mol, the amount of H4SiO4 was changed to 0.12 mol, and the amount of NH4HF2 was changed to 0.025 mol, the rest was the same as Example I-1.
[0867] Comparative Example I-8
[0868] Except that in “1) Preparation of positive electrode active material”, the amount of MnSO4﹒H2O was changed to 1.2 mol, the amount of FeSO4﹒H2O was changed to 0.8 mol, the amount of Li2CO3 was changed to 0.474 mol, 0.001 mol of Mo(SO4)3 was replaced by 0.001 mol of MgSO4, the amount of phosphoric acid was changed to 0.93 mol, the amount of H4SiO4 was changed to 0.07 mol, and the amount of NH4HF2 was changed to 0.06 mol, the rest was the same as Example I-1.
[0869]
Double-layer coated positive electrode active material and battery preparation
[0870] Example II-1-1
[0871] (1) Preparation of positive electrode active materials
[0872] Preparation of co-doped lithium manganese phosphate core
[0873] Preparation of Fe, Co and V co-doped manganese oxalate: 689.5g manganese carbonate (in MnCO3, the same below), 455.2g ferrous carbonate (in FeCO3, the same below), 4.6g cobalt sulfate (in CoSO4, the same below) and 4.9g vanadium dichloride (in VCl2, the same below) are fully mixed in a mixer for 6 hours. The mixture is transferred to a reactor, and 5 liters of deionized water and 1260.6g dihydrated oxalic acid (in C2H2O4.2H2O, the same below) are added. The reactor is heated to 80°C and stirred at a speed of 600rpm for 6 hours until the reaction is terminated (no bubbles are generated) to obtain a Fe, Co, V and S co-doped manganese oxalate suspension. The suspension is then filtered, the filter cake is dried at 120°C, and then ground to obtain Fe, Co and V co-doped dihydrated manganese oxalate particles with a median particle size Dv50 of 100nm.
[0874] Preparation of Fe, Co, V and S co-doped lithium manganese phosphate: Add the dihydrate manganese oxalate particles (1793.4 g) obtained in the previous step, 369.0 g lithium carbonate (in terms of Li2CO3, the same below), 1.6 g dilute sulfuric acid with a concentration of 60% (in terms of 60% H2SO4, the same below) and 1148.9 g diammonium phosphate (in terms of NH4H2PO4, the same below) to 20 liters of deionized water, and stir the mixture for 10 hours to mix it evenly to obtain a slurry. The slurry is transferred to a spray drying device for spray drying granulation, the drying temperature is set to 250°C, and dried for 4 hours to obtain a powder. In a nitrogen (90 volume %) + hydrogen (10 volume %) protective atmosphere, the above powder is sintered at 700°C for 4 hours to obtain 1572.1 g of Fe, Co, V and S co-doped lithium manganese phosphate.
[0875] Preparation of lithium iron pyrophosphate and lithium iron phosphate
[0876] Preparation of lithium iron pyrophosphate powder: 4.77g lithium carbonate, 7.47g ferrous carbonate, 14.84g ammonium dihydrogen phosphate and 1.3g oxalic acid dihydrate are dissolved in 50ml deionized water. The pH of the mixture is 5, and the reaction mixture is stirred for 2 hours to fully react. The reacted solution is then heated to 80°C and maintained at this temperature for 4 hours to obtain a suspension containing Li2FeP2O7. The suspension is filtered, washed with deionized water, and dried at 120°C for 4 hours to obtain a powder. The powder is sintered at 650°C in a nitrogen atmosphere for 8 hours, and ground after naturally cooling to room temperature to obtain Li2FeP2O7 powder.
[0877] Preparation of lithium iron phosphate suspension: 11.1 g lithium carbonate, 34.8 g ferrous carbonate, 34.5 g ammonium dihydrogen phosphate, 1.3 g oxalic acid dihydrate and 74.6 g sucrose (C 12 H 22 O 11 The mixture was stirred for 6 hours to allow the mixture to react fully. The solution after the reaction was heated to 120° C. and maintained at this temperature for 6 hours to obtain a suspension containing LiFePO4.
[0878] Wrap
[0879] 1572.1g of the above-mentioned Fe, Co, V and S co-doped lithium manganese phosphate and 15.72g of the above-mentioned lithium iron pyrophosphate (Li2FeP2O7) powder were added to the lithium iron phosphate (LiFePO4) suspension prepared in the previous step, stirred and mixed evenly, and then transferred to a vacuum oven and dried at 150°C for 6 hours. The obtained product was then dispersed by sand milling. After dispersion, the obtained product was sintered at 700°C in a nitrogen atmosphere for 6 hours to obtain the target product, double-layer coated lithium manganese phosphate.
[0880] (2) Preparation of positive electrode sheet
[0881] The double-layer coated lithium manganese phosphate positive electrode active material prepared above, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) were added to N-methylpyrrolidone (NMP) at a weight ratio of 92:2.5:5.5, and stirred and mixed evenly to obtain a positive electrode slurry. Then, the positive electrode slurry was heated to 0.280 g / 1540.25 mm 2 It is evenly coated on aluminum foil, dried, cold pressed and cut to obtain the positive electrode sheet.
[0882] (3) Preparation of negative electrode sheet
[0883] The negative electrode active material artificial graphite, hard carbon, conductive agent acetylene black, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC-Na) were dissolved in deionized water according to a weight ratio of 90:5:2:2:1, and stirred and mixed to prepare the negative electrode slurry. 2 It is evenly coated on the negative electrode current collector copper foil, and the negative electrode sheet is obtained through drying, cold pressing and cutting.
[0884] (4) Preparation of electrolyte
[0885] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), ethylene carbonate (EC) / ethyl methyl carbonate (EMC) were mixed in a volume ratio of 3 / 7 as an organic solvent, 12.5 wt% (based on the weight of the organic solvent) of LiPF6 was added and dissolved in the above organic solvent, and stirred evenly to obtain an electrolyte.
[0886] (5) Isolation film
[0887] A commercially available PP-PE copolymer microporous film (from Zhuogao Electronic Technology Co., Ltd., Model 20) with a thickness of 20 μm and an average pore size of 80 nm was used.
[0888] (6) Preparation of full battery
[0889] The positive electrode sheet, separator, and negative electrode sheet obtained above are stacked in order, with the separator placed between the positive and negative electrodes to play a role of isolation, and then wound to obtain a bare cell. The bare cell is placed in an outer package, injected with the above electrolyte and packaged to obtain a full battery (hereinafter also referred to as "full battery").
[0890] (7) Preparation of button cells
[0891] The double-layer coated lithium manganese phosphate positive electrode active material, PVDF, and acetylene black prepared above were added to NMP at a weight ratio of 90:5:5, and stirred in a drying room to form a slurry. The slurry was coated on aluminum foil, dried, and cold pressed to form a positive electrode sheet. The coating amount was 0.2 g / cm 2 , compacted density is 2.0g / cm 3 .
[0892] A lithium sheet was used as the negative electrode, and a solution of 1 mol / L LiPF6 in a volume ratio of 1:1:1 of ethylene carbonate (EC) + diethyl carbonate (DEC) + dimethyl carbonate (DMC) was used as the electrolyte. Together with the positive electrode sheet prepared above, they were assembled into a button battery (hereinafter also referred to as "button battery") in a button box.
[0893] Examples II-1-2 to II-1-6
[0894] In the preparation process of the co-doped lithium manganese phosphate core, the preparation conditions of the lithium manganese phosphate core in Examples II-1-2 to II-1-6 are the same as those in Example II-1-1, except that vanadium dichloride and cobalt sulfate are not used, and 463.4 g of ferrous carbonate, 1.6 g of 60% concentration dilute sulfuric acid, 1148.9 g of ammonium dihydrogen phosphate and 369.0 g of lithium carbonate are used.
[0895] In addition, in the preparation process of lithium iron pyrophosphate and lithium iron phosphate and the process of coating the first coating layer and the second coating layer, except that the raw materials used are adjusted according to the ratio of the coating amount shown in Table 1 to the coating amount corresponding to Example II-1-1, so that the amount of Li2FeP2O7 / LiFePO4 in Examples II-1-2 to II-1-6 is 12.6g / 37.7g, 15.7g / 47.1g, 18.8g / 56.5g, 22.0 / 66.0g and 25.1g / 75.4g respectively, and the amount of sucrose in Examples II-1-2 to II-1-6 is 37.3g, other conditions are the same as Example II-1-1.
[0896] Examples II-1-7 to II-1-10
[0897] The conditions of Examples II-1-7 to II-1-10 are the same as those of Example II-1-3, except that the amounts of sucrose used are 74.6 g, 149.1 g, 186.4 g and 223.7 g, respectively, so that the corresponding coating amounts of the carbon layer as the second coating layer are 31.4 g, 62.9 g, 78.6 g and 94.3 g, respectively.
[0898] Examples II-1-11 to II-1-14
[0899] The conditions of Examples II-1-11 to II-1-14 are the same as those of Example II-1-7, except that in the preparation process of lithium iron pyrophosphate and lithium iron phosphate, the amounts of various raw materials are adjusted accordingly according to the coating amounts shown in Table 1 so that the amounts of Li2FeP2O7 / LiFePO4 are 23.6g / 39.3g, 31.4g / 31.4g, 39.3g / 23.6g and 47.2g / 15.7g respectively.
[0900] Example II-1-15
[0901] The conditions of Example II-1-15 are the same as those of Example II-1-14, except that 492.80 g ZnCO3 is used instead of ferrous carbonate in the preparation of the co-doped lithium manganese phosphate core.
[0902] Examples II-1-16 to II-1-18
[0903] The conditions of Examples II-1-17 to 1-19 are the same as those of Example II-1-7, except that Example II-1-16 uses 466.4 g of NiCO3, 5.0 g of zinc carbonate and 7.2 g of titanium sulfate instead of ferrous carbonate in the preparation process of the co-doped lithium manganese phosphate core, Example II-1-17 uses 455.2 g of ferrous carbonate and 8.5 g of vanadium dichloride in the preparation process of the co-doped lithium manganese phosphate core, and Example II-1-18 uses 455.2 g of ferrous carbonate, 4.9 g of vanadium dichloride and 2.5 g of magnesium carbonate in the preparation process of the co-doped lithium manganese phosphate core.
[0904] Examples II-1-19 to II-1-20
[0905] Except that Example II-1-19 uses 369.4 g of lithium carbonate and 1.05 g of 60% concentration dilute nitric acid instead of dilute sulfuric acid in the preparation process of the co-doped lithium manganese phosphate core, and Example II-1-20 uses 369.7 g of lithium carbonate and 0.78 g of silicic acid instead of dilute sulfuric acid in the preparation process of the co-doped lithium manganese phosphate core, the conditions of Examples II-1-19 to II-1-20 are the same as those of Example II-1-18.
[0906] Examples II-1-21 to II-1-22
[0907] The conditions of Examples II-1-21 to II-1-22 are the same as those of Example II-1-20, except that Example II-1-21 uses 632.0 g of manganese carbonate, 463.30 g of ferrous carbonate, 30.5 g of vanadium dichloride, 21.0 g of magnesium carbonate and 0.78 g of silicic acid in the preparation process of the co-doped lithium manganese phosphate core; and Example II-1-22 uses 746.9 g of manganese carbonate, 289.6 g of ferrous carbonate, 60.9 g of vanadium dichloride, 42.1 g of magnesium carbonate and 0.78 g of silicic acid in the preparation process of the co-doped lithium manganese phosphate core.
[0908] Examples II-1-23 to II-1-24
[0909] Except that Example II-1-23 uses 804.6g manganese carbonate, 231.7g ferrous carbonate, 1156.2g ammonium dihydrogen phosphate, 1.2g boric acid (mass fraction 99.5%) and 370.8g lithium carbonate in the preparation process of the co-doped lithium manganese phosphate core; and Example II-1-24 uses 862.1g manganese carbonate, 173.8g ferrous carbonate, 1155.1g ammonium dihydrogen phosphate, 1.86g boric acid (mass fraction 99.5%) and 371.6g lithium carbonate in the preparation process of the co-doped lithium manganese phosphate core, the conditions of Examples II-1-23 to II-1-24 are the same as those of Example II-1-22.
[0910] Example II-1-25
[0911] The conditions of Example II-1-25 are the same as those of Example II-1-20, except that Example II-1-25 uses 370.1 g of lithium carbonate, 1.56 g of silicic acid and 1147.7 g of diammonium phosphate in the preparation process of the co-doped lithium manganese phosphate core.
[0912] Example II-1-26
[0913] The conditions of Example II-1-26 are the same as those of Example II-1-20, except that 368.3 g of lithium carbonate, 4.9 g of 60% by mass dilute sulfuric acid, 919.6 g of manganese carbonate, 224.8 g of ferrous carbonate, 3.7 g of vanadium dichloride, 2.5 g of magnesium carbonate and 1146.8 g of diammonium phosphate are used in the preparation process of the co-doped lithium manganese phosphate core in Example II-1-26.
[0914] Example II-1-27
[0915] The conditions of Example II-1-27 are the same as those of Example II-1-20, except that Example II-1-27 uses 367.9 g of lithium carbonate, 6.5 g of 60% dilute sulfuric acid and 1145.4 g of diammonium phosphate in the preparation process of the co-doped lithium manganese phosphate core.
[0916] Examples II-1-28 to II-1-33
[0917] Except that in Examples II-1-28 to II-1-33, 1034.5g of manganese carbonate, 108.9g of ferrous carbonate, 3.7g of vanadium dichloride and 2.5g of magnesium carbonate are used in the preparation process of the co-doped lithium manganese phosphate core, the amounts of lithium carbonate used are 367.6g, 367.2g, 366.8g, 366.4g, 366.0g and 332.4g, respectively, the amounts of diammonium dihydrogen phosphate used are 1144.5g, 1143.4g, 1142.2g, 1141.1g, 1139.9g and 1138.8g, respectively, and the amounts of 60% dilute sulfuric acid used are 8.2g, 9.8g, 11.4g, 13.1g, 14.7g and 16.3g, respectively. The conditions of Examples II-1-28 to II-1-33 are the same as those of Example II-1-20.
[0918] Example II-1-34
[0919] Kernel Li 1.1 Mn 0.6 Fe 0.393 Mg 0.007 P 0.9 Si0.1 Preparation of O4:
[0920] Preparation of Fe and Mg co-doped manganese oxalate: 689.5g manganese carbonate (in MnCO3, the same below), 455.2g ferrous carbonate (in FeCO3, the same below) and 5.90g magnesium carbonate (in MgCO3, the same below) are fully mixed in a mixer for 6 hours. The mixture is transferred to a reactor, and 5 liters of deionized water and 1260.6g dihydrated oxalic acid (in C2H2O4.2H2O, the same below) are added. The reactor is heated to 80°C and stirred at a speed of 600rpm for 6 hours until the reaction terminates (no bubbles are generated) to obtain a Fe and Mg co-doped manganese oxalate suspension. The suspension is then filtered, the filter cake is dried at 120°C, and then ground to obtain Fe and Mg co-doped dihydrated manganese oxalate particles with a median particle size Dv50 of 100nm.
[0921] Preparation of Fe, Mg and Si co-doped lithium manganese phosphate: Add the dihydrate manganese oxalate particles (1791.3 g) obtained in the previous step, 406.3 g lithium carbonate (in terms of Li2CO3, the same below), 7.8 g silicic acid (in terms of H2SiO3, the same below) and 1035.0 g diammonium phosphate (in terms of NH4H2PO4, the same below) to 20 liters of deionized water, and stir the mixture for 10 hours to mix it evenly to obtain a slurry. The slurry is transferred to a spray drying device for spray drying granulation, the drying temperature is set to 250°C, and dried for 4 hours to obtain a powder. In a nitrogen (90 volume %) + hydrogen (10 volume %) protective atmosphere, the above powder is sintered at 700°C for 4 hours to obtain 1574.0 g of Fe, Mg and Si co-doped lithium manganese phosphate.
[0922] The other conditions refer to Example II-1-1.
[0923] Example II-1-35
[0924] Core LiMn 0.50 Fe 0.50 P 0.995 N 0.005 Preparation of O4.
[0925] Preparation of Fe-doped manganese oxalate: 574.7 g of manganese carbonate (in terms of MnCO3, the same below) and 579.27 g of ferrous carbonate (in terms of FeCO3, the same below) were fully mixed in a mixer for 6 hours. The mixture was transferred to a reactor, and 5 liters of deionized water and 1260.6 g of oxalic acid dihydrate (in terms of C2H2O4.2H2O, the same below) were added. The reactor was heated to 80°C and stirred at a speed of 600 rpm for 6 hours until the reaction terminated (no bubbles were generated) to obtain a Fe-doped manganese oxalate suspension. The suspension was then filtered, the filter cake was dried at 120°C, and then ground to obtain Fe-doped manganese oxalate dihydrate particles with a median particle size Dv50 of 100 nm.
[0926] Preparation of Fe and N co-doped lithium manganese phosphate: Add the dihydrate manganese oxalate particles (1794.4 g) obtained in the previous step, 369.4 g lithium carbonate (calculated as Li2CO3, the same below), 5.25 g dilute nitric acid (calculated as 60% HNO3, the same below) and 1144.3 g diammonium phosphate (calculated as NH4H2PO4, the same below) to 20 liters of deionized water, and stir the mixture for 10 hours to mix it evenly to obtain a slurry. The slurry is transferred to a spray drying device for spray drying granulation, the drying temperature is set to 250°C, and dried for 4 hours to obtain a powder. In a nitrogen (90 volume %) + hydrogen (10 volume %) protective atmosphere, the above powder is sintered at 700°C for 4 hours to obtain 1572.2 g of Fe and N co-doped lithium manganese phosphate.
[0927] The other conditions refer to Example II-1-1.
[0928] Example II-1-36
[0929] Preparation of LiMn core 0.909 Fe 0.091 P 0.99 N 0.01 When O4, 1044.6g of manganese carbonate, 1138.5g of ammonium dihydrogen phosphate and 369.4g of lithium carbonate are used, and 105.4g of ferrous carbonate and 10.5g of dilute nitric acid (calculated as 60% HNO3, the same below) are additionally added. The rest is the same as Example II-1-1.
[0930] Example II-1-37
[0931] Preparation of LiMn core 0.091 Fe 0.909 P 0.995 N 0.005When O4, 104.5g of manganese carbonate, 1138.5g of ammonium dihydrogen phosphate and 371.3g of lithium carbonate are used, and 1052.8g of ferrous carbonate and 5.25g of dilute nitric acid (calculated as 60% HNO3, the same below) are additionally added. The rest is the same as Example II-1-1.
[0932] Example II-1-38
[0933] In the process of preparing lithium iron pyrophosphate and lithium iron phosphate and in the process of coating the first coating layer and the second coating layer, except that the raw materials used are adjusted according to the ratio of the coating amount shown in Table 4 to the coating amount corresponding to Example II-1-1, so that the amount of Li2FeP2O7 / LiFePO4 is 62.9g / 47.1g respectively, other conditions are the same as Example II-1-1.
[0934] Example II-1-39
[0935] In the preparation process of silver pyrophosphate, 463.4g of silver oxide (calculated as Ag2O, the same below) and 230.6g of phosphoric acid (calculated as 85% H3PO4, the same below) are fully mixed. It is heated to 450°C and stirred continuously for 2 hours to allow the reaction mixture to fully react. The reacted solution is then kept at 450°C for 4 hours to obtain a viscous paste containing Ag4P2O7, which eventually becomes a solid and is washed with deionized water. The resulting product is ground in a ball mill filled with ethanol for 4 hours, and the resulting product is dried under an infrared lamp to obtain Ag4P2O7 powder. The rest is the same as Example II-1-1.
[0936] Example II-1-40
[0937] Except that during the preparation of Fe, Co, V and S co-doped lithium manganese phosphate, the powder is sintered at 650°C for 43.5 hours in a protective atmosphere of nitrogen (90 volume %) + hydrogen (10 volume %), everything else is the same as Example II-1-21.
[0938] Example II-1-41
[0939] Core LiMn 0.999 Fe 0.001 P 0.995 N 0.005 Preparation of O4
[0940] Preparation of Fe-doped manganese oxalate: 1148.0g manganese carbonate (in terms of MnCO3, the same below) and 11.58g ferrous carbonate (in terms of FeCO3, the same below) were fully mixed in a mixer for 6 hours. The mixture was transferred to a reactor, and 5 liters of deionized water and 1260.6g oxalic acid dihydrate (in terms of C2H2O4.2H2O, the same below) were added. The reactor was heated to 80°C and stirred at a speed of 600rpm for 6 hours until the reaction terminated (no bubbles were generated) to obtain a Fe-doped manganese oxalate suspension. The suspension was then filtered, the filter cake was dried at 120°C, and then ground to obtain Fe-doped manganese oxalate dihydrate particles with a median particle size Dv50 of 100nm.
[0941] Preparation of Fe and N co-doped lithium manganese phosphate: Add the dihydrate manganese oxalate particles (1789.9 g) obtained in the previous step, 369.4 g lithium carbonate (calculated as Li2CO3, the same below), 5.25 g dilute nitric acid (calculated as 60% HNO3, the same below) and 1144.3 g diammonium phosphate (calculated as NH4H2PO4, the same below) to 20 liters of deionized water, and stir the mixture for 10 hours to mix it evenly to obtain a slurry. The slurry is transferred to a spray drying device for spray drying granulation, the drying temperature is set to 250°C, and dried for 4 hours to obtain a powder. In a nitrogen (90 volume %) + hydrogen (10 volume %) protective atmosphere, the above powder is sintered at 700°C for 4 hours to obtain 1567.7 g of Fe and N co-doped lithium manganese phosphate.
[0942] The other conditions of Example II-1-41 refer to those of Example II-1-1.
[0943] Example II-2-1
[0944] Except that in the preparation process of lithium iron pyrophosphate (Li2FeP2O7), the sintering temperature in the powder sintering step is 550°C and the sintering time is 1 hour to control the crystallinity of Li2FeP2O7 to 30%, and in the preparation process of lithium iron phosphate (LiFePO4), the sintering temperature in the coating sintering step is 650°C and the sintering time is 2 hours to control the crystallinity of LiFePO4 to 30%, other conditions are the same as those in Example II-1-1.
[0945] Example II-2-2
[0946] Except that in the preparation process of lithium iron pyrophosphate (Li2FeP2O7), the sintering temperature in the powder sintering step is 550°C and the sintering time is 2 hours to control the crystallinity of Li2FeP2O7 to 50%, and in the preparation process of lithium iron phosphate (LiFePO4), the sintering temperature in the coating sintering step is 650°C and the sintering time is 3 hours to control the crystallinity of LiFePO4 to 50%, other conditions are the same as those in Example II-1-1.
[0947] Example II-2-3
[0948] Except that in the preparation process of lithium iron pyrophosphate (Li2FeP2O7), the sintering temperature in the powder sintering step is 600°C and the sintering time is 3 hours to control the crystallinity of Li2FeP2O7 to 70%, and in the preparation process of lithium iron phosphate (LiFePO4), the sintering temperature in the coating sintering step is 650°C and the sintering time is 4 hours to control the crystallinity of LiFePO4 to 70%, other conditions are the same as Example II-1-1.
[0949] Example II-2-4
[0950] Except that in the preparation process of lithium iron pyrophosphate (Li2FeP2O7), the sintering temperature in the powder sintering step is 650°C and the sintering time is 4 hours to control the crystallinity of Li2FeP2O7 to 100%, and in the preparation process of lithium iron phosphate (LiFePO4), the sintering temperature in the coating sintering step is 700°C and the sintering time is 6 hours to control the crystallinity of LiFePO4 to 100%, other conditions are the same as those in Example II-1-1.
[0951] Examples II-3-1 to II-3-12
[0952] Except for the process of preparing Fe, Co and V co-doped manganese oxalate particles, the heating temperature / stirring time in the reactor of Example II-3-1 is 60°C / 120 minutes; the heating temperature / stirring time in the reactor of Example II-3-2 is 70°C / 120 minutes; the heating temperature / stirring time in the reactor of Example II-3-3 is 80°C / 120 minutes; the heating temperature / stirring time in the reactor of Example II-3-4 is 90°C / 120 minutes; the heating temperature / stirring time in the reactor of Example II-3-5 is 100°C / 120 minutes; the heating temperature / stirring time in the reactor of Example II-3-6 is 110°C / 120 minutes; and the heating temperature / stirring time in the reactor of Example II-3-7 is 110°C / 120 minutes. The heating temperature / stirring time in the reactor are 120°C / 120 minutes respectively; the heating temperature / stirring time in the reactor of Example II-3-8 are 130°C / 120 minutes respectively; the heating temperature / stirring time in the reactor of Example II-3-9 are 100°C / 60 minutes respectively; the heating temperature / stirring time in the reactor of Example II-3-10 are 100°C / 90 minutes respectively; the heating temperature / stirring time in the reactor of Example II-3-11 are 100°C / 150 minutes respectively; the heating temperature / stirring time in the reactor of Example II-3-12 are 100°C / 180 minutes respectively. Except that the heating temperature / stirring time in the reactor of Example II-3-12 are 100°C / 180 minutes respectively, the other conditions of Examples II-3-1 to II-3-12 are the same as those of Example II-1-1.
[0953] Examples II-4-1 to II-4-7
[0954] Examples II-4-1 to II-4-4: Except that in the preparation process of lithium iron pyrophosphate (Li2FeP2O7), the drying temperature / drying time in the drying step are 100℃ / 4h, 150℃ / 6h, 200℃ / 6h and 200℃ / 6h respectively; and the sintering temperature and sintering time in the sintering step in the preparation process of lithium iron pyrophosphate (Li2FeP2O7) are 700℃ / 6h, 700℃ / 6h, 700℃ / 6h and 600℃ / 6h respectively, the other conditions are the same as those in Example II-1-7.
[0955] Examples II-4-5 to II-4-7: Except that the drying temperature / drying time in the drying step during the coating process are 150℃ / 6h, 150℃ / 6h and 150℃ / 6h respectively; and the sintering temperature and sintering time in the sintering step during the coating process are 600℃ / 4h, 600℃ / 6h and 800℃ / 8h respectively, other conditions are the same as those of Example II-1-12.
[0956] Example II-5-1:
[0957] (1) Preparation of co-doped lithium manganese phosphate core: the same as the “Preparation of co-doped lithium manganese phosphate core” in Example II-1-1.
[0958] (2) Preparation of a suspension containing lithium iron pyrophosphate, aluminum oxide and sucrose:
[0959] Preparation of lithium iron pyrophosphate powder: 4.77g lithium carbonate, 7.47g ferrous carbonate, 14.84g ammonium dihydrogen phosphate and 1.3g oxalic acid dihydrate are dissolved in 50ml deionized water. The pH of the mixture is 5, and the reaction mixture is stirred for 2 hours to fully react. The reacted solution is then heated to 80°C and maintained at this temperature for 4 hours to obtain a suspension containing Li2FeP2O7. The suspension is filtered, washed with deionized water, and dried at 120°C for 4 hours to obtain a powder. The powder is sintered at 650°C in a nitrogen atmosphere for 8 hours, and ground after naturally cooling to room temperature to obtain Li2FeP2O7 powder.
[0960] Preparation of suspension containing aluminum oxide and sucrose: 47.1g of nano-Al2O3 (particle size about 20nm) and 74.6g of sucrose (C 12 H 22 O 11 The mixture was then stirred for 6 hours to fully mix the mixture. The resulting solution was heated to 120° C. and maintained at this temperature for 6 hours to obtain a suspension containing aluminum oxide and sucrose.
[0961] (3) Coating
[0962] 1572.1g of the above-mentioned Fe, Co, V and S co-doped lithium manganese phosphate and 15.72g of the above-mentioned lithium iron pyrophosphate (Li2FeP2O7) powder were added to the suspension containing aluminum oxide and sucrose prepared in the previous step, stirred and mixed evenly, and then transferred to a vacuum oven and dried at 150°C for 6 hours. The obtained product was then dispersed by sand milling. After dispersion, the obtained product was sintered at 700°C in a nitrogen atmosphere for 6 hours to obtain the target product, double-layer coated lithium manganese phosphate.
[0963] Example II-5-2
[0964] In the preparation process of the co-doped lithium manganese phosphate core, the preparation conditions of the lithium manganese phosphate core in Example II-5-2 are the same as those in Example II-5-1, except that vanadium dichloride and cobalt sulfate are not used, and 463.4 g of ferrous carbonate, 1.6 g of 60% concentration dilute sulfuric acid, 1148.9 g of ammonium dihydrogen phosphate and 369.0 g of lithium carbonate are used.
[0965] In addition, in the process of preparing lithium iron pyrophosphate and the suspension containing aluminum oxide and sucrose, and in the process of coating the first coating layer and the second coating layer, except that the raw materials used are adjusted according to the ratio of the coating amount shown in Table 24 to the coating amount corresponding to Example II-5-1, so that the amount of Li2FeP2O7 / Al2O3 in Example II-5-2 is 12.6g / 37.68g respectively, and the amount of sucrose in Example II-5-2 is 37.3g, other conditions are the same as Example II-5-1.
[0966] Example II-5-3
[0967] Step S1: Preparation of doped manganese oxalate
[0968] 1.3 mol MnSO4·H2O and 0.7 mol FeSO4·H2O were fully mixed in a mixer for 6 hours; the mixture was transferred to a reactor, 10 L of deionized water and 2 mol of dihydrated oxalic acid were added, heated to 80°C, and then stirred at 600 rpm for 6 hours, the reaction was terminated (no bubbles were generated), and a suspension of Fe-doped manganese oxalate was obtained; the suspension was filtered, the filter cake was dried at 120°C, and ground to obtain a particle size D v 50 is Fe-doped manganese oxalate particles of about 100 nm;
[0969] Step S2: Preparation of Li 0.994 Mo 0.001 Mn 0.65 Fe 0.35 P 0.999 Si 0.001 O 3.999 F 0.001 The kernel
[0970] 1 mol of Fe-doped manganese oxalate particles, 0.497 mol of lithium carbonate, 0.001 mol of Mo(SO4)3, 0.999 mol of phosphoric acid in a 85% aqueous solution, 0.001 mol of H4SiO4, 0.0005 mol of NH4HF2 and 0.005 mol of sucrose were added to 20 L of deionized water, and the mixture was transferred to a sand mill and fully ground and stirred for 10 hours to obtain a slurry; the slurry was transferred to a spray drying device for spray drying and granulation, the drying temperature was set to 250°C, and dried for 4 hours to obtain particles; the particles were sintered at 700°C for 10 hours in a nitrogen (90% v / v) + hydrogen (10% v / v) protective atmosphere to obtain a core material. The element content of the core material was detected by inductively coupled plasma emission spectroscopy (ICP), and the core chemical formula was as shown above.
[0971] Step S3: Preparation of lithium iron pyrophosphate powder
[0972] Dissolve 4.77g lithium carbonate, 7.47g ferrous carbonate, 14.84g ammonium dihydrogen phosphate and 1.3g oxalic acid dihydrate in 50ml deionized water. The pH of the mixture is 5, and the reaction mixture is stirred for 2 hours to fully react. Then the reacted solution is heated to 80°C and maintained at this temperature for 4 hours to obtain a suspension containing Li2FeP2O7. The suspension is filtered, washed with deionized water, and dried at 120°C for 4 hours to obtain a powder. The powder is sintered at 650°C in a nitrogen atmosphere for 8 hours, and ground after naturally cooling to room temperature to obtain Li2FeP2O7 powder.
[0973] Step S4: preparing a suspension containing aluminum oxide and sucrose
[0974] 4.71g of nano-Al2O3 (particle size about 20nm) and 3.73g of sucrose (in C 12 H 22 O 11 The mixture was heated to 120° C. and maintained at this temperature for 6 hours to obtain a suspension containing aluminum oxide and sucrose.
[0975] Step S5: Preparation of two coating layers
[0976] 157.21g of the above-mentioned core and 1.57g of the above-mentioned lithium iron pyrophosphate (Li2FeP2O7) powder are added to the suspension containing aluminum oxide and sucrose prepared in the previous step, stirred and mixed evenly, and then transferred to a vacuum oven and dried at 150°C for 6 hours, and then the product is dispersed by sand milling. After dispersion, the product is sintered at 700°C in a nitrogen atmosphere for 6 hours to obtain a double-layer coated lithium manganese phosphate.
[0977] Example II-5-4
[0978] Except that in step S3 of preparing lithium iron pyrophosphate (Li2FeP2O7) powder, the sintering temperature in the powder sintering step is 550°C and the sintering time is 1 h to control the crystallinity of Li2FeP2O7 to 30%, other conditions are the same as those in Example II-5-3.
[0979] Example II-5-5
[0980] Preparation of doped manganese oxalate:1.3 mol of MnSO4﹒H2O and 0.7 mol of FeSO4﹒H2O were fully mixed in a mixer for 6 hours. The mixture was transferred to a reactor, and 10 L of deionized water and 2 mol of dihydrated oxalic acid (calculated as oxalic acid) were added. The reactor was heated to 80°C and stirred at 600 rpm for 6 hours. The reaction was terminated (no bubbles were generated) to obtain a Fe-doped manganese oxalate suspension. The suspension was then filtered, and the filter cake was dried at 120°C and then ground to obtain a median particle size Dv 50 Fe-doped manganese oxalate particles with a size of about 100 nm.
[0981] Prepare the kernel: Take 1 mol of the above manganese oxalate particles, 0.497 mol of lithium carbonate, 0.001 mol of Mo(SO4)3, 0.999 mol of phosphoric acid in a 85% phosphoric acid aqueous solution, 0.001 mol of H4SiO4, 0.0005 mol of NH4HF2 and 0.005 mol of sucrose and add them to 20L of deionized water. Transfer the mixture to a sand mill and grind and stir it for 10 hours to obtain a slurry. Transfer the slurry to a spray drying equipment for spray drying and granulation, set the drying temperature to 250°C, dry it for 4 hours, and obtain particles. In a protective atmosphere of nitrogen (90 volume %) + hydrogen (10 volume %), sinter the above powder at 700°C for 10 hours to obtain a carbon-coated Li 0.994 Mo 0.001 Mn 0.65 Fe 0.35 P 0.999 Si 0.001 O 3.999 F 0.001 , i.e. the core. The element content can be detected by inductively coupled plasma emission spectroscopy (ICP).
[0982] Coating of the cladding layer: Aminoethylaminopropyl polydimethylsiloxane was dissolved in xylene to form a coating solution, and then the prepared core was added thereto and stirred to form a mixed slurry, and then the mixed slurry was placed in a wet bag machine and dried at 120° C. for 4 hours in a nitrogen atmosphere to obtain a positive electrode active material. The mass percentage of the polar functional groups (i.e., -CH2NH2 and -CH2NH-) of the aminoethylaminopropyl polydimethylsiloxane was 12%, the number average molecular weight was 3700, and the coating amount was 1% by weight, based on the weight of the prepared core.
[0983] The preparation of button cells and full cells is described in Example II-1-1.
[0984] Example II-5-6
[0985] Step S1: Preparation of Fe, Co, V and S co-doped manganese oxalate
[0986] 689.6g manganese carbonate, 455.27g ferrous carbonate, 4.65g cobalt sulfate, and 4.87g vanadium dichloride were added to a mixer and fully mixed for 6 hours. The obtained mixture was then transferred to a reactor, and 5L deionized water and 1260.6g oxalic acid dihydrate were added, heated to 80°C, and stirred at a speed of 500rpm for 6 hours, mixed evenly, until the reaction terminated without bubble generation, to obtain a Fe, Co, and V co-doped manganese oxalate suspension. The suspension was then filtered, dried at 120°C, and sand-milled to obtain manganese oxalate particles with a particle size of 100nm.
[0987] Step S2: Preparation of inner core Li 0.997 Mn 0.60 Fe 0.393 V 0.004 Co 0.003 P 0.997 S 0.003 O4
[0988] Take 1793.1g of manganese oxalate prepared in (1), 368.3g of lithium carbonate, 1146.6g of ammonium dihydrogen phosphate and 4.9g of dilute sulfuric acid, add them into 20L of deionized water, stir them thoroughly, and evenly mix and react at 80°C for 10 hours to obtain a slurry. The slurry is transferred to a spray drying device for spray drying and granulation, and dried at a temperature of 250°C to obtain a powder. In a protective atmosphere (90% nitrogen and 10% hydrogen), the powder is sintered in a roller kiln at 700°C for 4 hours to obtain the above-mentioned core material.
[0989] Step S3: Preparation of the first coating layer suspension
[0990] To prepare Li2FeP2O7 solution, 7.4 g lithium carbonate, 11.6 g ferrous carbonate, 23.0 g ammonium dihydrogen phosphate and 12.6 g oxalic acid dihydrate were dissolved in 500 mL deionized water, the pH was controlled to 5, and then stirred and reacted at room temperature for 2 hours to obtain a solution, and then the solution was heated to 80°C and maintained at this temperature for 4 hours to obtain a first coating layer suspension.
[0991] Step S4: Coating of the first coating layer
[0992] The doped 1571.9 g lithium manganese phosphate core material obtained in step S2 is added to the first coating layer suspension (coating material content is 15.7 g) obtained in step S3, and the mixture is stirred and mixed for 6 hours. After mixing evenly, the mixture is transferred to a 120° C. oven and dried for 6 hours, and then sintered at 650° C. for 6 hours to obtain a pyrophosphate-coated material.
[0993] Step S5: Preparation of the second coating layer suspension
[0994] 3.7 g of lithium carbonate, 11.6 g of ferrous carbonate, 11.5 g of ammonium dihydrogen phosphate and 12.6 g of oxalic acid dihydrate were dissolved in 1500 mL of deionized water, and then stirred and reacted for 6 hours to obtain a solution, and then the solution was heated to 120° C. and maintained at this temperature for 6 hours to obtain a second coating layer suspension.
[0995] Step S6: Coating of the second coating layer
[0996] 1586.8 g of the pyrophosphate-coated material obtained in step S4 was added to the second coating layer suspension (coating material content was 47.1 g) obtained in step S5, and the mixture was stirred and mixed for 6 hours. After being evenly mixed, the mixture was transferred to a 120°C oven and dried for 6 hours, and then sintered at 700°C for 8 hours to obtain a two-layer coated material.
[0997] Step S7: Preparation of the third coating layer aqueous solution
[0998] 37.3 g of sucrose was dissolved in 500 g of deionized water, and then stirred and fully dissolved to obtain a sucrose aqueous solution.
[0999] Step S8: Coating of the third coating layer
[1000] 1633.9 g of the two-layer coated material obtained in step S6 was added to the sucrose solution obtained in step S7, and stirred and mixed together for 6 hours. After being evenly mixed, it was transferred to a 150°C oven for drying for 6 hours, and then sintered at 700°C for 10 hours to obtain a three-layer coated material.
[1001] Step S9: Coating of the fourth coating layer
[1002] The terminal hydroxyl polydimethylsiloxane is dissolved in xylene to form a fourth coating liquid, and then the three-layer coated material obtained in step S8 is added thereto and stirred evenly to form a mixed slurry, and then the mixed slurry is placed in a wet bag machine and dried at 120° C. in a nitrogen atmosphere for 4 hours to obtain a four-layer coated positive electrode active material. Among them, the mass percentage of the polar functional group (i.e. -OH) of the terminal hydroxyl polydimethylsiloxane is 3.4%, the number average molecular weight is 1000, and the coating amount is 1% by weight, based on the weight of the three-layer coated material obtained in step S8.
[1003] The preparation of button cells and full cells is described in Example II-1-1.
[1004] Example II-5-7
[1005] Preparation of doped manganese oxalate:1.3 mol of MnSO4﹒H2O and 0.7 mol of FeSO4﹒H2O were fully mixed in a mixer for 6 hours. The mixture was transferred to a reactor, and 10 L of deionized water and 2 mol of dihydrated oxalic acid (calculated as oxalic acid) were added. The reactor was heated to 80°C and stirred at 600 rpm for 6 hours. The reaction was terminated (no bubbles were generated) to obtain a Fe-doped manganese oxalate suspension. The suspension was then filtered, and the filter cake was dried at 120°C and then ground to obtain a median particle size Dv 50 Fe-doped manganese oxalate particles with a size of about 100 nm.
[1006] Prepare the kernel: Take 1 mol of the above manganese oxalate particles, 0.497 mol of lithium carbonate, 0.001 mol of Mo(SO4)3, 0.999 mol of phosphoric acid in a 85% phosphoric acid aqueous solution, 0.001 mol of H4SiO4, 0.0005 mol of NH4HF2 and 0.005 mol of sucrose and add them to 20L of deionized water. Transfer the mixture to a sand mill and grind and stir it for 10 hours to obtain a slurry. Transfer the slurry to a spray drying equipment for spray drying and granulation, set the drying temperature to 250°C, dry it for 4 hours, and obtain particles. In a protective atmosphere of nitrogen (90 volume %) + hydrogen (10 volume %), sinter the above powder at 700°C for 10 hours to obtain a carbon-coated Li 0.994 Mo 0.001 Mn 0.65 Fe 0.35 P 0.999 Si 0.001 O 3.999 F 0.001 , i.e. the core. The element content can be detected by inductively coupled plasma emission spectroscopy (ICP).
[1007] Coating of the cladding layer: The carboxymethyl chitosan was dissolved in deionized water to form a coating solution, and then the core material was added thereto and stirred to form a mixed slurry, and then the mixed slurry was placed in a wet bag machine and dried at 120° C. for 4 hours in a nitrogen atmosphere to obtain a positive electrode active material. The mass percentage of the substituent attached to the sugar unit in the carboxymethyl chitosan was 60.2%, the number average molecular weight was 26000, and the coating amount was 1% by weight based on the weight of the core.
[1008] The preparation of button cells and full cells is described in Example II-1-1.
[1009] Comparative Example II-1
[1010] Preparation of manganese oxalate: 1149.3 g of manganese carbonate was added to a reactor, and 5 liters of deionized water and 1260.6 g of oxalic acid dihydrate (calculated as C2H2O4·2H2O, the same below) were added. The reactor was heated to 80° C. and stirred at a speed of 600 rpm for 6 hours until the reaction was terminated (no bubbles were generated) to obtain a manganese oxalate suspension, which was then filtered, and the filter cake was dried at 120° C. and then ground to obtain manganese oxalate dihydrate particles with a median particle size Dv50 of 100 nm.
[1011] Preparation of carbon-coated lithium manganese phosphate: 1789.6 g of the above-obtained dihydrate manganese oxalate particles, 369.4 g of lithium carbonate (in terms of Li2CO3, the same below), 1150.1 g of diammonium phosphate (in terms of NH4H2PO4, the same below) and 31 g of sucrose (in terms of C 12 H 22 O 11 The slurry was transferred to a spray drying device for spray drying and granulation, and the drying temperature was set at 250° C. and dried for 4 hours to obtain a powder. The powder was sintered at 700° C. for 4 hours in a nitrogen (90 volume %) + hydrogen (10 volume %) protective atmosphere to obtain carbon-coated lithium manganese phosphate.
[1012] Comparative Example II-2
[1013] Except for using 689.5 g of manganese carbonate and additionally adding 463.3 g of ferrous carbonate, other conditions of Comparative Example II-2 were the same as those of Comparative Example II-1.
[1014] Comparative Example II-3
[1015] Except for using 1148.9 g of ammonium dihydrogen phosphate and 369.0 g of lithium carbonate, and additionally adding 1.6 g of 60% strength dilute sulfuric acid, other conditions of Comparative Example II-3 are the same as those of Comparative Example II-1.
[1016] Comparative Example II-4
[1017] Except for using 689.5 g of manganese carbonate, 1148.9 g of ammonium dihydrogen phosphate and 369.0 g of lithium carbonate, and additionally adding 463.3 g of ferrous carbonate and 1.6 g of 60% concentrated dilute sulfuric acid, other conditions of Comparative Example II-4 are the same as those of Comparative Example II-1.
[1018] Comparative Example II-5
[1019] In addition, the following steps are added: Preparation of lithium iron pyrophosphate powder: 9.52g of lithium carbonate, 29.9g of ferrous carbonate, 29.6g of ammonium dihydrogen phosphate and 32.5g of oxalic acid dihydrate are dissolved in 50ml of deionized water. The pH of the mixture is 5, and the reaction mixture is stirred for 2 hours to fully react. The reacted solution is then heated to 80°C and maintained at this temperature for 4 hours to obtain a suspension containing Li2FeP2O7, which is filtered, washed with deionized water, and dried at 120°C for 4h to obtain a powder. The powder is sintered at 500°C in a nitrogen atmosphere for 4 hours, and ground after naturally cooling to room temperature. The crystallinity of Li2FeP2O7 is controlled to be 5%. When preparing carbon-coated materials, the amount of Li2FeP2O7 is 62.8g, and the other conditions of Comparative Example II-5 are the same as those of Comparative Example II-4.
[1020] Comparative Example II-6
[1021] In addition, the following steps are added: Preparation of lithium iron phosphate suspension: 14.7g lithium carbonate, 46.1g ferrous carbonate, 45.8g ammonium dihydrogen phosphate and 50.2g oxalic acid dihydrate are dissolved in 500ml deionized water, and then stirred for 6 hours to allow the mixture to react fully. Then the reacted solution is heated to 120°C and maintained at this temperature for 6 hours to obtain a suspension containing LiFePO4. In the preparation process of lithium iron phosphate (LiFePO4), the sintering temperature in the coating sintering step is 600°C, and the sintering time is 4h to control the crystallinity of LiFePO4 to 8%. When preparing the carbon-coated material, the amount of LiFePO4 is 62.8g. The other conditions of Comparative Example II-6 are the same as those of Comparative Example II-4.
[1022] Comparative Example II-7
[1023] Preparation of lithium iron pyrophosphate powder: Dissolve 2.38g of lithium carbonate, 7.5g of ferrous carbonate, 7.4g of ammonium dihydrogen phosphate and 8.1g of oxalic acid dihydrate in 50ml of deionized water. The pH of the mixture is 5, and the reaction mixture is stirred for 2 hours to allow the reaction mixture to react fully. The reacted solution is then heated to 80°C and maintained at this temperature for 4 hours to obtain a suspension containing Li2FeP2O7, which is filtered, washed with deionized water, and dried at 120°C for 4 hours to obtain a powder. The powder is sintered at 500°C in a nitrogen atmosphere for 4 hours, and ground after naturally cooling to room temperature to control the crystallinity of Li2FeP2O7 to 5%.
[1024] Preparation of lithium iron phosphate suspension: 11.1 g lithium carbonate, 34.7 g ferrous carbonate, 34.4 g ammonium dihydrogen phosphate, 37.7 g oxalic acid dihydrate and 37.3 g sucrose (C 12 H 22 O 11The mixture was stirred for 6 hours to allow the mixture to react fully. The solution after the reaction was heated to 120° C. and maintained at this temperature for 6 hours to obtain a suspension containing LiFePO4.
[1025] 15.7 g of the obtained lithium iron pyrophosphate powder was added to the above-mentioned lithium iron phosphate (LiFePO4) and sucrose suspension. During the preparation process, the sintering temperature in the coating sintering step was 600°C, and the sintering time was 4 hours to control the crystallinity of LiFePO4 to 8%. The other conditions of Comparative Example II-7 were the same as those of Comparative Example II-4, and amorphous lithium iron pyrophosphate, amorphous lithium iron phosphate, and carbon-coated positive electrode active materials were obtained.
[1026] Comparative Examples II-8 to II-11
[1027] In addition to the drying temperature / drying time in the drying step during the preparation of lithium iron pyrophosphate (Li2FeP2O7), which are 80°C / 3h, 80°C / 3h, and 80°C / 3h in Comparative Examples II-8 to II-10, respectively; the sintering temperature and sintering time in the sintering step during the preparation of lithium iron pyrophosphate (Li2FeP2O7) are 400°C / 3h, 400°C / 3h, and 350°C / 3h in Comparative Examples II-8 to II-10, respectively. / 2h, in the preparation process of lithium iron phosphate (LiFePO4) in comparative example II-11, the drying temperature / drying time in the drying step is 80℃ / 3h; and in comparative examples II-8 to II-11, the amounts of Li2FeP2O7 / LiFePO4 are 47.2g / 15.7g, 15.7g / 47.2g, 62.8g / 0g, and 0g / 62.8g respectively, and the other conditions are the same as those in example II-1-7.
[1028] The preparation of the positive electrode sheet, the preparation of the negative electrode sheet, the preparation of the electrolyte, the preparation of the isolation membrane and the battery in the above-mentioned embodiments and comparative examples are the same as the process of Example II-1-1.
[1029]
Preparation of three-layer coated positive electrode active materials and batteries
[1030] Example III-1:
[1031] Step 1: Preparation of positive electrode active materials
[1032] Step S1: Preparation of Fe, Co, V and S co-doped manganese oxalate
[1033] 689.6g of manganese carbonate, 455.27g of ferrous carbonate, 4.65g of cobalt sulfate, and 4.87g of vanadium dichloride were added to a mixer and mixed thoroughly for 6h. The obtained mixture was then transferred to a reactor, and 5L of deionized water and 1260.6g of oxalic acid dihydrate were added, heated to 80°C, and stirred at a speed of 500rpm for 6h, mixed evenly, until the reaction was terminated and no bubbles were generated, to obtain a Fe, Co, and V co-doped manganese oxalate suspension. The suspension was then filtered, dried at 120°C, and sand-milled to obtain manganese oxalate particles with a particle size of 100nm.
[1034] Step S2: Preparation of inner core Li 0.997 Mn 0.60 Fe 0.393 V 0.004 Co 0.003 P 0.997 S 0.003 O4
[1035] Take 1793.1g of manganese oxalate prepared in (1), 368.3g of lithium carbonate, 1146.6g of ammonium dihydrogen phosphate and 4.9g of dilute sulfuric acid, add them to 20L of deionized water, stir them thoroughly, and evenly mix and react at 80°C for 10h to obtain a slurry. Transfer the slurry to a spray drying device for spray drying and granulation, and dry it at a temperature of 250°C to obtain a powder. In a protective atmosphere (90% nitrogen and 10% hydrogen), sinter the powder in a roller kiln at 700°C for 4h to obtain the above-mentioned core material.
[1036] Step S3: Preparation of the first coating layer suspension
[1037] To prepare Li2FeP2O7 solution, 7.4 g lithium carbonate, 11.6 g ferrous carbonate, 23.0 g ammonium dihydrogen phosphate and 12.6 g oxalic acid dihydrate were dissolved in 500 mL deionized water, the pH was controlled to 5, and then stirred and reacted at room temperature for 2 h to obtain a solution, and then the solution was heated to 80 ° C and maintained at this temperature for 4 h to obtain a first coating layer suspension.
[1038] Step S4: Coating of the first coating layer
[1039] The doped 1571.9 g lithium manganese phosphate core material obtained in step S2 was added to the first coating layer suspension (coating material content was 15.7 g) obtained in step S3, and the mixture was stirred and mixed for 6 h. After mixing evenly, the mixture was transferred to a 120° C. oven and dried for 6 h, and then sintered at 650° C. for 6 h to obtain the pyrophosphate-coated material.
[1040] Step S5: Preparation of the second coating layer suspension
[1041] 3.7 g of lithium carbonate, 11.6 g of ferrous carbonate, 11.5 g of ammonium dihydrogen phosphate and 12.6 g of oxalic acid dihydrate were dissolved in 1500 mL of deionized water, and then stirred and reacted for 6 hours to obtain a solution, and then the solution was heated to 120° C. and maintained at this temperature for 6 hours to obtain a second coating layer suspension.
[1042] Step S6: Coating of the second coating layer
[1043] 1586.8 g of the pyrophosphate-coated material obtained in step S4 was added to the second coating layer suspension (coating material content was 47.1 g) obtained in step S5, and the mixture was stirred and mixed for 6 hours. After mixing evenly, the mixture was transferred to a 120°C oven and dried for 6 hours, and then sintered at 700°C for 8 hours to obtain a two-layer coated material.
[1044] Step S7: Preparation of the third coating layer aqueous solution
[1045] 37.3 g of sucrose was dissolved in 500 g of deionized water, and then stirred and fully dissolved to obtain a sucrose aqueous solution.
[1046] Step S8: Coating of the third coating layer
[1047] 1633.9 g of the two-layer coated material obtained in step S6 was added to the sucrose solution obtained in step S7, and stirred and mixed together for 6 hours. After mixing evenly, it was transferred to a 150°C oven for drying for 6 hours, and then sintered at 700°C for 10 hours to obtain a three-layer coated material.
[1048] Step 2: Preparation of positive electrode
[1049] The three-layer coated positive electrode active material, conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) prepared above were added to N-methylpyrrolidone (NMP) at a weight ratio of 97.0:1.2:1.8, and stirred to mix evenly to obtain positive electrode slurry. Then, the positive electrode slurry was heated to 0.280 g / 1540.25 mm 2 It is evenly coated on aluminum foil, dried, cold pressed and cut to obtain the positive electrode sheet.
[1050] Step 3: Preparation of negative electrode
[1051] The negative electrode active material artificial graphite, hard carbon, conductive agent acetylene black, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) were dissolved in deionized water according to a weight ratio of 90:5:2:2:1, and stirred and mixed to prepare the negative electrode slurry. 2 It is evenly coated on the negative electrode current collector copper foil, and after drying, cold pressing and slitting, the negative electrode sheet is obtained.
[1052] Step 4: Preparation of electrolyte
[1053] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), organic solvents ethylene carbonate (EC) / ethyl methyl carbonate (EMC) were mixed in a volume ratio of 3 / 7, 12.5 wt% (based on the weight of the ethylene carbonate / ethyl methyl carbonate solvent) of LiPF6 was added and dissolved in the above organic solvent, and stirred evenly to obtain an electrolyte.
[1054] Step 5: Preparation of isolation membrane
[1055] A commercially available PP-PE copolymer microporous film (from Zhuogao Electronic Technology Co., Ltd., Model 20) with a thickness of 20 μm and an average pore size of 80 nm was used.
[1056] Step 6: Preparation of the full battery
[1057] The positive electrode sheet, separator, and negative electrode sheet obtained above are stacked in order, with the separator placed between the positive and negative electrodes to play a role of isolation, and then wound to obtain a bare cell. The bare cell is placed in an outer package, injected with the above electrolyte and packaged to obtain a full battery (hereinafter also referred to as "full battery").
[1058] (Preparation of button cell)
[1059] The positive electrode active material, polyvinylidene fluoride (PVDF) and acetylene black prepared above were added to N-methylpyrrolidone (NMP) at a weight ratio of 90:5:5, and stirred in a drying room to form a slurry. The slurry was coated on aluminum foil, dried and cold pressed to form a positive electrode sheet. The coating amount was 0.2 g / cm 2 , compacted density is 2.0g / cm 3 .
[1060] A lithium sheet was used as the negative electrode, and a solution of 1 mol / L LiPF6 in ethylene carbonate (EC), diethyl carbonate (DEC) and dimethyl carbonate (DMC) in a volume ratio of 1:1:1 was used as the electrolyte. Together with the positive electrode sheet prepared above, they were assembled into a button battery (hereinafter also referred to as "button battery") in a button box.
[1061] Examples III-2 to III-53 and Comparative Examples III-1 to III-17
[1062] The positive electrode active materials and batteries in Examples III-2 to III-53 and Comparative Examples III-1 to III-17 were prepared in a manner similar to Example III-1. The differences in the preparation of the positive electrode active materials are shown in Tables 1-6, wherein Comparative Examples III-1 to III-2, Comparative Examples III-4 to III-10 and Comparative Example III-12 were not coated with the first layer, and therefore did not have steps S3 and S4; Comparative Examples III-1 to III-11 were not coated with the second layer, and therefore did not have steps S5-S6.
[1063] Note: In all embodiments and comparative examples of the present application, if not specified, the first coating layer material and / or the second coating layer material used are assumed to be crystalline.
[1064] Table 1: Raw materials for preparation of kernel
[1065]
[1066]
[1067]
[1068]
[1069]
[1070] *For detailed measurement methods, please refer to the “Material Performance Test” section below.
[1071] Table 2: Preparation of the first coating layer suspension (step S3)
[1072]
[1073] *For detailed determination methods, please refer to the “Material Performance Test” section below;
[1074] **When the mass of the coating material of the first coating layer increases or decreases, the mass of the raw materials used for the suspension of the first coating layer increases or decreases by the same multiple.
[1075] Table 3: Coating of the first coating layer (step S4)
[1076]
[1077]
[1078]
[1079]
[1080] *For detailed measurement methods, please refer to the “Material Performance Test” section below.
[1081] Table 4: Preparation of the second coating layer suspension (step S5)
[1082]
[1083] *For detailed determination methods, please refer to the “Material Performance Test” section below;
[1084] **When the mass of the second coating layer material increases or decreases, the mass of the raw materials used for the second coating layer suspension increases or decreases by the same multiple.
[1085] Table 5: Coating of the second coating layer (step S6)
[1086]
[1087]
[1088]
[1089]
[1090]
[1091] *For detailed measurement methods, please refer to the “Material Performance Test” section below.
[1092] Table 6: Coating of the third coating layer (step S8)
[1093]
[1094]
[1095]
[1096]
[1097]
[1098]
[1099]
[1100] Examples III-30 to III-42: Investigation of other coating materials
[1101] Examples III-30 to III-42 were carried out in a manner similar to that of Example III-1, except for the differences shown in Tables 7-8 below.
[1102] Table 7: Investigation of the first coating layer material
[1103]
[1104]
[1105] Table 8: Investigation of the second coating layer material
[1106]
[1107]
[1108] Examples III-2-1 to III-2-24
[1109] The sintering temperature and sintering time in steps S4, S6 and S8 were changed, and the rest were the same as Example III-1, see Table 30 for details.
[1110] Examples III-3-1 to III-3-20
[1111] The reaction temperature and reaction time in the preparation of the inner core were changed, and the rest were the same as Example III-1, as shown in Table 31 for details.
[1112] Example III-4-1
[1113] Step S1: Preparation of Fe, Co, V and S co-doped manganese oxalate
[1114] 689.6g of manganese carbonate, 455.27g of ferrous carbonate, 4.65g of cobalt sulfate, and 4.87g of vanadium dichloride were added to a mixer and mixed thoroughly for 6h. The obtained mixture was then transferred to a reactor, and 5L of deionized water and 1260.6g of oxalic acid dihydrate were added, heated to 80°C, and stirred at a speed of 500rpm for 6h, mixed evenly, until the reaction was terminated and no bubbles were generated, to obtain a Fe, Co, and V co-doped manganese oxalate suspension. The suspension was then filtered, dried at 120°C, and sand-milled to obtain manganese oxalate particles with a particle size of 100nm.
[1115] Step S2: Preparation of inner core Li 0.997 Mn 0.60 Fe 0.393 V 0.004 Co 0.003 P 0.997 S 0.003 O4
[1116] Take 1793.1g of manganese oxalate prepared in (1), 368.3g of lithium carbonate, 1146.6g of ammonium dihydrogen phosphate and 4.9g of dilute sulfuric acid, add them to 20L of deionized water, stir thoroughly, and evenly mix and react at 80°C for 10 hours to obtain a slurry. Transfer the slurry to a spray drying device for spray drying and granulation, and dry it at a temperature of 250°C to obtain a powder. In a protective atmosphere (90% nitrogen and 10% hydrogen), sinter the powder in a roller kiln at 700°C for 4 hours to obtain a core material. The element content of the core material is detected by inductively coupled plasma emission spectroscopy (ICP), and the core chemical formula is shown above.
[1117] Step S3: Preparation of the first coating layer suspension
[1118] Preparation of Li2FeP2O7 solution: 7.4 g lithium carbonate, 11.6 g ferrous carbonate, 23.0 g ammonium dihydrogen phosphate and 12.6 g oxalic acid dihydrate were dissolved in 500 mL deionized water, the pH was controlled to 5, and then stirred and reacted at room temperature for 2 h to obtain a solution, and then the solution was heated to 80 ° C and maintained at this temperature for 4 h to obtain a first coating layer suspension.
[1119] Step S4: Coating of the first coating layer
[1120] The doped 1571.9 g lithium manganese phosphate core material obtained in step S2 was added to the first coating layer suspension (coating material content was 15.7 g) obtained in step S3, and the mixture was stirred and mixed for 6 h. After mixing evenly, the mixture was transferred to a 120° C. oven and dried for 6 h, and then sintered at 650° C. for 6 h to obtain the pyrophosphate-coated material.
[1121] Step S5: Preparation of the second coating layer suspension
[1122] 47.1 g of nano-sized Al2O3 (particle size of about 20 nm) was dissolved in 1500 mL of deionized water and stirred for 2 h to obtain a second coating layer suspension.
[1123] Step S6: Coating of the second coating layer
[1124] 1586.8 g of the pyrophosphate-coated material obtained in step S4 was added to the second coating layer suspension (coating material content was 47.1 g) obtained in step S5, and the mixture was stirred and mixed for 6 hours. After mixing evenly, the mixture was transferred to a 120°C oven and dried for 6 hours, and then sintered at 700°C for 8 hours to obtain a two-layer coated material.
[1125] Step S7: Preparation of the third coating layer aqueous solution
[1126] 37.3 g of sucrose was dissolved in 500 g of deionized water, and then stirred and fully dissolved to obtain a sucrose aqueous solution.
[1127] Step S8: Coating of the third coating layer
[1128] 1633.9 g of the two-layer coated material obtained in step S6 was added to the sucrose solution obtained in step S7, and stirred and mixed together for 6 hours. After mixing evenly, it was transferred to a 150°C oven for drying for 6 hours, and then sintered at 700°C for 10 hours to obtain a three-layer coated material.
[1129] Core: Li 0.997 Mn 0.60 Fe 0.393 V 0.004 Co 0.003 P 0.997 S 0.003 O4; the first coating layer is 1% crystalline Li2FeP2O7; the second coating layer is 3% crystalline Al2O3; the third coating layer is 1% carbon, and the molar ratio of SP2 to SP3 is 2.2.
[1130] Example III-4-2
[1131] Except that the amount of sucrose in step S8 is 111.9 g and the sintering is performed at 600° C. for 9 hours, the rest is the same as Example III-4-1.
[1132] The inner core, the first coating layer and the second coating layer are the same as those in Example III-4-1; the third coating layer is 3% carbon, and the molar ratio of SP2 to SP3 is 2.3.
[1133] Example III-4-3
[1134] Step S1: Preparation of doped manganese oxalate
[1135] 1.3 mol MnSO4·H2O and 0.7 mol FeSO4·H2O were fully mixed in a mixer for 6 hours; the mixture was transferred to a reactor, 10 L of deionized water and 2 mol of dihydrated oxalic acid were added, heated to 80°C, and then stirred at 600 rpm for 6 hours, the reaction was terminated (no bubbles were generated), and a suspension of Fe-doped manganese oxalate was obtained; the suspension was filtered, the filter cake was dried at 120°C, and ground to obtain a particle size Dv 50 Fe-doped manganese oxalate particles of about 100 nm;
[1136] Step S2: Preparation of Li 0.994 Mo 0.001 Mn 0.65 Fe 0.35 P 0.999 Si 0.001 O3.999 F 0.001 The kernel
[1137] 1 mol of Fe-doped manganese oxalate particles, 0.497 mol of lithium carbonate, 0.001 mol of Mo(SO4)3, 0.999 mol of phosphoric acid in a 85% aqueous solution, 0.001 mol of H4SiO4, 0.0005 mol of NH4HF2 and 0.005 mol of sucrose were added to 20 L of deionized water, and the mixture was transferred to a sand mill and fully ground and stirred for 10 hours to obtain a slurry; the slurry was transferred to a spray drying device for spray drying and granulation, the drying temperature was set to 250°C, and dried for 4 hours to obtain particles; the particles were sintered at 700°C for 10 hours in a nitrogen (90% v / v) + hydrogen (10% v / v) protective atmosphere to obtain a core material. The element content of the core material was detected by inductively coupled plasma emission spectroscopy (ICP), and the core chemical formula was as shown above.
[1138] Step S3: Preparation of the first coating layer suspension
[1139] Preparation of Li2FeP2O7 solution: 7.4 g lithium carbonate, 11.6 g ferrous carbonate, 23.0 g ammonium dihydrogen phosphate and 12.6 g oxalic acid dihydrate were dissolved in 500 mL deionized water, the pH was controlled to 5, and then stirred and reacted at room temperature for 2 h to obtain a solution, and then the solution was heated to 80 ° C and maintained at this temperature for 4 h to obtain a first coating layer suspension.
[1140] Step S4: Coating of the first coating layer
[1141] The doped 157.2 g lithium manganese phosphate core material obtained in step S2 was added to the first coating layer suspension (coating material content was 1.572 g) obtained in step S3, and the mixture was stirred and mixed for 6 h. After mixing evenly, the mixture was transferred to a 120° C. oven and dried for 6 h, and then sintered at 650° C. for 6 h to obtain the pyrophosphate-coated material.
[1142] Step S5: Preparation of the second coating layer suspension
[1143] 4.71 g of nano-Al2O3 (particle size of about 20 nm) was dissolved in 1500 mL of deionized water and stirred for 2 h to obtain a second coating layer suspension.
[1144] Step S6: Coating of the second coating layer
[1145] Add 158.772 g of the pyrophosphate-coated material obtained in step S4 to the second coating layer suspension (coating material content is 4.71 g) obtained in step S5, stir and mix thoroughly for 6 hours, and after mixing evenly, transfer to a 120°C oven and dry for 6 hours, and then sinter at 700°C for 8 hours to obtain a two-layer coated material.
[1146] Step S7: Preparation of the third coating layer aqueous solution
[1147] 37.3 g of sucrose was dissolved in 500 g of deionized water, and then stirred and fully dissolved to obtain a sucrose aqueous solution.
[1148] Step S8: Coating of the third coating layer
[1149] 1633.9 g of the two-layer coated material obtained in step S6 was added to the sucrose solution obtained in step S7, and stirred and mixed together for 6 hours. After mixing evenly, it was transferred to a 150°C oven for drying for 6 hours, and then sintered at 700°C for 10 hours to obtain a three-layer coated material.
[1150] Core: Li 0.994 Mo 0.001 Mn 0.65 Fe 0.35 P 0.999 Si 0.001 O 3.999 F 0.001 ; The first coating layer is 1% crystalline Li2FeP2O7; the second coating layer is 3% crystalline Al2O3; the third coating layer is 1% carbon, and the molar ratio of SP2 to SP3 is 2.2.
[1151] Example III-4-4
[1152] Except for the following differences, the rest is the same as Example III-4-3:
[1153] Step S3: Dissolve 53.3 g of aluminum chloride, 34.5 g of ammonium dihydrogen phosphate and 18.9 g of oxalic acid dihydrate in 500 mL of deionized water, control the pH to 4, then stir and react at room temperature for 2 h to obtain a solution, then heat the solution to 80° C. and maintain this temperature for 4 h to obtain a first coating layer suspension.
[1154] Step S4: sinter at 680°C for 8h. The rest is the same as step S4 of Example III-4-3.
[1155] The inner core, the second coating layer and the third coating layer are the same as those in Example III-4-3; the first coating layer is 1% crystalline Al4(P2O7)3.
[1156]
Mixed use of two positive electrode active materials and preparation of batteries
[1157] Example IV-1
[1158] The core material of Example I-1 and lithium nickel cobalt manganese oxide LiNi 0.5 Co 0.2 Mn 0.3 O2 was mixed in a mass ratio of 1:1 as the positive electrode active material.
[1159] Preparation of positive electrode sheet: The slurry of positive electrode active material is prepared at 0.019 g / cm 2 The coating amount is evenly coated on both sides of the current collector aluminum foil, vacuum dried at a high temperature of 100-120°C for 14 hours, and compacted by a roller press to obtain the positive electrode sheet P4.
[1160] Preparation of negative electrode sheets: The negative electrode active material artificial graphite, the conductive agent superconducting carbon black (Super-P), the binder styrene-butadiene rubber (SBR), and the thickener sodium carboxymethyl cellulose (CMC-Na) are dissolved in deionized water in a mass ratio of 95%: 1.5%: 1.8%: 1.7%, and after being fully stirred and mixed, a negative electrode slurry with a viscosity of 3000mPa.s and a solid content of 52% is obtained; the negative electrode slurry is coated on a 6μm negative electrode current collector copper foil, and then baked at 100°C for 4 hours to dry, and roll-pressed to obtain a negative electrode sheet with a compaction density of 1.75g / cm3.
[1161] Isolation film: Polypropylene film.
[1162] Preparation of electrolyte: Ethylene carbonate, dimethyl carbonate and 1,2-propylene carbonate are mixed in a volume ratio of 1:1:1, and then LiPF6 is uniformly dissolved in the above solution to obtain an electrolyte. In the electrolyte, the concentration of LiPF6 is 1 mol / L.
[1163] Preparation of a full battery: Using the above-mentioned positive electrode plate, in the order of negative electrode plate, diaphragm, and positive electrode plate, a bare cell is formed by a winding method, and aluminum tabs and copper tabs are punched out respectively to obtain a bare cell; the copper and copper tabs, and the aluminum and aluminum tabs of the two bare cells are welded to the battery top cover through a adapter, the bare cell is wrapped and insulated, and then the bare cell is loaded into an aluminum shell, the top cover and the aluminum shell are welded to form a dry cell, the dry cell is baked to remove water, and then the electrolyte is injected, the battery is formed and aged, and a full battery is obtained accordingly.
[1164] Preparation of button cell: Assemble the above-mentioned positive electrode plate together with the negative electrode and the electrolyte into a button cell (hereinafter also referred to as "button cell") in a button cell box.
[1165] Example IV-2
[1166] The core material of Example I-1 and lithium nickel cobalt aluminum oxide LiNi 0.33 Co0.33 Al 0.34 O2 was mixed in a mass ratio of 1:1 as the positive electrode active material.
[1167] The rest is the same as Example IV-1.
[1168] Battery Test
[1169] 1. Lattice change rate test method:
[1170] Under a constant temperature of 25°C, the positive electrode active material sample was placed in an XRD (model: Bruker D8 Discover), and the sample was tested at 1° / min. The test data was sorted and analyzed, and the lattice constants a0, b0, c0 and v0 were calculated with reference to the standard PDF card (a0, b0 and c0 represent the lengths of each aspect of the unit cell, and v0 represents the unit cell volume, which can be directly obtained through the XRD refinement results).
[1171] The positive electrode active material sample is prepared into a buckle battery using the buckle battery preparation method in the above embodiment, and the buckle battery is charged at a small rate of 0.05C until the current is reduced to 0.01C. The positive electrode plate in the buckle battery is then taken out and immersed in dimethyl carbonate (DMC) for 8 hours. It is then dried, powdered, and particles with a particle size of less than 500nm are screened out. Take a sample and calculate its unit cell volume v1 in the same way as the above-mentioned test of the fresh sample, and (v0-v1) / v0×100% is shown in the table as the lattice change rate (unit cell volume change rate) before and after complete lithium deintercalation.
[1172] 2. Li / Mn antisite defect concentration:
[1173] The XRD results tested in the "lattice change rate measurement method" are compared with the PDF (Powder Diffraction File) card of the standard crystal to obtain the Li / Mn antisite defect concentration. Specifically, the XRD results tested in the "lattice change rate measurement method" are imported into the General Structural Analysis System (GSAS) software to automatically obtain the refinement results, which include the occupancy of different atoms, and the Li / Mn antisite defect concentration is obtained by reading the refinement results.
[1174] 3. Compacted density:
[1175] 5 g of the prepared positive electrode active material powder was placed in a special compaction mold (American CARVER mold, model 13 mm), and then the mold was placed on a compaction density instrument. A pressure of 3 T was applied, and the thickness of the powder under pressure (thickness after pressure relief) was read on the instrument. The compaction density was calculated by ρ = m / v, where the area value used was the standard small picture area of 1540.25 mm 2.
[1176] 4.3C charging constant current ratio:
[1177] At a constant temperature of 25°C, let the fresh full batteries prepared in the above embodiments and comparative examples stand for 5 minutes, and discharge to 2.5V at 1 / 3C. Let stand for 5 minutes, charge to 4.3V at 1 / 3C, and then charge at a constant voltage at 4.3V until the current is less than or equal to 0.05mA. Let stand for 5 minutes, and record the charging capacity at this time as C0. Discharge to 2.5V at 1 / 3C, let stand for 5 minutes, and then charge to 4.3V at 3C, let stand for 5 minutes, and record the charging capacity at this time as C1. The 3C charging constant current ratio is C1 / C0×100%.
[1178] The higher the 3C charging constant current ratio, the better the rate performance of the secondary battery.
[1179] 5. Transition metal Mn (and Mn-doped Fe) dissolution test:
[1180] After cycling at 45°C until the capacity decayed to 80%, the full batteries prepared in the above embodiments and comparative examples were discharged at a rate of 0.1C to a cut-off voltage of 2.0V. Then the batteries were disassembled, the negative electrode sheets were taken out, and 30 unit areas (1540.25mm 2 ) discs were tested by inductively coupled plasma emission spectroscopy (ICP) using Agilent ICP-OES730. The amount of Fe (if the Mn position of the positive electrode active material is doped with Fe) and Mn was calculated based on the ICP results, thereby calculating the amount of Mn (and Fe doped at the Mn position) dissolved after cycling. The test standard is based on EPA-6010D-2014.
[1181] 6. Surface oxygen valence state:
[1182] Take 5g of the above-prepared positive electrode active material sample and prepare it into a buckle battery according to the buckle battery preparation method in the above embodiment. The buckle battery is charged at a small rate of 0.05C until the current is reduced to 0.01C. Then take out the positive electrode plate in the buckle battery and soak it in DMC for 8 hours. Then dry it, scrape the powder, and screen out the particles with a particle size of less than 500nm. The obtained particles are measured with an electron energy loss spectrum (EELS, the instrument model used is Talos F200S) to obtain the energy loss near-edge structure (ELNES), which reflects the state density and energy level distribution of the element. According to the state density and energy level distribution, the number of occupied electrons is calculated by integrating the valence band state density data, thereby inferring the valence state of the surface oxygen after charging.
[1183] 7. Measurement of manganese and phosphorus in positive electrode active materials:
[1184] 5 g of the positive electrode active material prepared above was dissolved in 100 ml of reverse aqua regia (concentrated hydrochloric acid: concentrated nitric acid = 1:3) (concentrated hydrochloric acid concentration ~37%, concentrated nitric acid concentration ~65%), the content of each element in the solution was tested by ICP, and then the content of manganese or phosphorus was measured and converted (100% × the amount of manganese or phosphorus / the amount of positive electrode active material) to obtain its weight ratio.
[1185] 8. Initial gram capacity measurement method of button cell:
[1186] At 2.5-4.3V, the button cells prepared in the above-mentioned Examples III and Comparative Examples III were charged to 4.3V at 0.1C, then charged at a constant voltage at 4.3V until the current was less than or equal to 0.05mA, allowed to stand for 5 minutes, and then discharged to 2.0V at 0.1C. The discharge capacity at this time was the initial gram capacity, recorded as D0.
[1187] 9. Full battery cell expansion test at 60°C for 30 days:
[1188] The full batteries prepared in each of the above-mentioned Examples III and Comparative Examples III were stored at 100% state of charge (SOC) at 60°C. The open circuit voltage (OCV) and AC internal resistance (IMP) of the battery cells were measured before, during and after storage to monitor the SOC, and the volume of the battery cells was measured. The full battery was taken out after every 48 hours of storage, and the open circuit voltage (OCV) and internal resistance (IMP) were tested after standing for 1 hour, and the volume of the battery cells was measured by the water displacement method after cooling to room temperature. The water displacement method is to first use a balance that automatically converts units using dial data to measure the gravity F1 of the battery cell alone, and then completely place the battery cell in deionized water (density is known to be 1g / cm 3 ), measure the gravity F2 of the battery cell at this time, and the buoyancy F 浮 That is F1-F2, and then according to Archimedean principle F 浮 =ρ×g×V 排 , the cell volume V = (F1-F2) / (ρ×g) is calculated.
[1189] From the OC...
Claims
1. A positive electrode active material, comprising a compound represented by formula (I), Li a A x Mr 1-y B y P 1-z C z Oh 4-n D n (I) in, The A comprises one or more elements selected from Group IA, Group IIA, Group IIIA, Group IIB, Group VB, and Group VIB, The B includes one or more elements selected from Group IA, Group IIA, Group IIIA, Group IV, Group VA, and Group IIB, The C comprises one or more elements selected from Group IIIA, Group IV, Group VA and Group VIA, The D comprises one or more elements selected from Group VIA and Group VIIA, The a is selected from the range of 0.85 to 1.15, the x is selected from the range of 0 to 0.1, the y is selected from the range of 0.001 to 0.999, the z is selected from the range of 0 to 0.5, and the n is selected from the range of 0 to 0.
5.
2. The positive electrode active material according to claim 1, wherein A comprises one or more elements selected from Rb, Cs, Be, Ca, Sr, Ba, Ga, In, Cd, V, Ta, Cr, Zn, Al, Na, K, Mg, Nb, Mo and W, and may be selected from one or more elements selected from Zn, Al, Na, K, Mg, Nb, Mo and W; and / or The B includes one or more elements selected from the group consisting of Rb, Cs, Be, Ca, Sr, Ba, In, Pb, Bi, Cd, Hf, Ta, Cr, Ru, Rh, Pd, Os, Ir, Pt, Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and may be selected from the group consisting of one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge; and / or, The C includes one or more elements selected from B (boron), S, Si and N; and / or, The D includes one or more elements selected from the group consisting of S, F, Cl and Br.
3. The positive electrode active material according to claim 1 or 2, wherein The A includes any one element selected from Mg and Nb; and / or, The B comprises one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge, and may be selected from at least two elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge, and may be selected from at least two elements selected from Fe, Ti, V, Ni, Co and Mg, and may be further selected from at least two elements selected from Fe, Ti, V, Co and Mg, and may be further selected from Fe and one or more elements selected from Ti, V, Co and Mg; and / or, The C includes any one element selected from B (boron), S, Si and N, and may be S; and / or, The D includes any one element selected from S, F, Cl and Br, and may be F.
4. The positive electrode active material according to any one of claims 1 to 3, wherein The a is selected from the range of 0.9 to 1.1, optionally selected from the range of 0.97 to 1.01; and / or, The x is selected from the range of 0 to 0.005, optionally selected from the range of 0.001 to 0.1; and / or, The y is selected from the range of 0.001 to 0.5, optionally selected from the range of 0.01 to 0.5, optionally selected from the range of 0.25 to 0.5; and / or, The z is selected from the range of 0 to 0.5, optionally from the range of 0.001 to 0.5, optionally from the range of 0.001 to 0.1, more optionally from the range of 0.001 to 0.005; and / or, Said n is selected from the range of 0 to 0.1, optionally selected from the range of 0.001 to 0.
1.
5. The positive electrode active material according to any one of claims 1 to 4, wherein The x is 0, the z is selected from the range of 0.001 to 0.5, and the n is selected from the range of 0.001 to 0.1; or, The x is selected from the range of 0.001 to 0.1, the z is 0, and the n is selected from the range of 0.001 to 0.1; or, The x is selected from the range of 0.001 to 0.1, the z is selected from the range of 0.001 to 0.5, and the n is 0; or, The x is 0, the z is 0, and the n is selected from the range of 0.001 to 0.1; or, The x is 0, the z is selected from the range of 0.001 to 0.5, and the n is 0; or, The x is selected from the range of 0.001 to 0.1, the z is selected from the range of 0.001 to 0.5, and the n is selected from the range of 0.001 to 0.
1.
6. The positive electrode active material according to any one of claims 1 to 5, wherein y:z is selected from the range of 0.002 to 999, optionally from the range of 0.025 to 999, and more optionally from the range of 0.2 to 600; and / or z:n is selected from the range of 0.002 to 500, can be selected from the range of 0.2 to 100, and can be further selected from the range of 0.2 to 50.
7. The positive electrode active material according to any one of claims 1 to 6, wherein A comprises one or more elements selected from Zn, Al, Na, K, Mg, Nb, Mo and W; The B includes one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge; The C includes one or more elements selected from B (boron), S, Si and N; Said D comprises one or more elements selected from S, F, Cl and Br; The a is selected from the range of 0.9 to 1.1, the x is selected from the range of 0.001 to 0.1, the y is selected from the range of 0.001 to 0.5, the z is selected from the range of 0.001 to 0.1, and the n is selected from the range of 0.001 to 0.
1.
8. The positive electrode active material according to any one of claims 1 to 6, wherein The B comprises one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and optionally one or more elements selected from Zn, Fe, Ti, V, Ni, Co and Mg; The C is one or more elements selected from B, Si, N and S; The a is selected from the range of 0.9 to 1.1, the x is 0, the y is selected from the range of 0.001 to 0.5, the z is selected from the range of 0.001 to 0.1, and the n is 0.
9. The positive electrode active material according to any one of claims 1 to 8, wherein The positive electrode active material includes a core and a shell covering the core, The core comprises the compound represented by formula I; The shell includes one or more coating layers; the coating layers have ion conductivity or electronic conductivity.
10. The positive electrode active material according to claim 9, wherein The one or more coating layers each independently include one or more selected from pyrophosphate, phosphate, carbon, doped carbon, oxide, boride and polymer.
11. The positive electrode active material according to claim 10, wherein The shell includes a coating; Optionally, the coating layer comprises one or more selected from pyrophosphate, phosphate, carbon, doped carbon, oxide, boride and polymer.
12. The positive electrode active material according to claim 9, wherein The shell includes a first coating layer covering the core and a second coating layer covering the first coating layer; Optionally, the first coating layer and the second coating layer each independently include one or more selected from pyrophosphate, phosphate, carbon, doped carbon, oxide, boride and polymer.
13. The positive electrode active material according to claim 12, wherein The first coating layer includes one or more selected from pyrophosphate, phosphate, oxide and boride, and the second coating layer includes one or more selected from carbon and doped carbon.
14. The positive electrode active material according to claim 9, wherein The shell includes a first coating layer covering the core, a second coating layer covering the first coating layer, and a third coating layer covering the second coating layer; Optionally, the first coating layer, the second coating layer and the third coating layer each independently include one or more selected from pyrophosphate, phosphate, carbon, doped carbon, oxide, boride and polymer.
15. The positive electrode active material according to claim 14, wherein The first coating layer includes pyrophosphate, the second coating layer includes one or more selected from phosphate, oxide and boride, and the third coating layer includes one or more selected from carbon and doped carbon.
16. The positive electrode active material according to any one of claims 1 to 15, wherein The lattice mismatch between the material of the core and the material of the shell is less than 10%.
17. The positive electrode active material according to any one of claims 1 to 16, wherein Based on the weight of the positive electrode active material, The manganese content is in the range of 10 wt% to 35 wt%, optionally in the range of 13.3 wt% to 33.2 wt%, more optionally in the range of 15 wt% to 30 wt%, further optionally in the range of 17 wt% to 20 wt%; and / or, The phosphorus content is in the range of 12 wt% to 25 wt%, optionally in the range of 15 wt% to 20 wt%, and more optionally in the range of 16.8 wt% to 19.5 wt%; and / or, The weight ratio of manganese element to phosphorus element ranges from 0.71 to 1.85, and can be selected from 0.90 to 1.25, and more preferably from 0.95 to 1.
20. 18 . The positive electrode active material according to claim 1 , wherein the surface of the positive electrode active material is coated with one or more of carbon and doped carbon; optionally, the surface of the positive electrode active material is coated with carbon.
19. The positive electrode active material according to claim 18, wherein The doping elements in the doped carbon include one or more selected from nitrogen, phosphorus, sulfur, boron and fluorine.
20. The positive electrode active material according to any one of claims 1 to 19, wherein In the compound represented by formula (I), (1-y): y is in the range of 0.1-999, optionally in the range of 0.1-10 or in the range of 0.67-999, more optionally in the range of 1 to 10, further optionally in the range of 1 to 4, and further optionally in the range of 1.5 to 3; and / or, a:x is in the range of 1 to 1200, and can be optionally in the range of 9 to 1100, and can be more optionally in the range of 190-998.
21. The positive electrode active material according to any one of claims 1 to 20, wherein In the compound represented by formula (I), the ratio of z to 1-z is 1:9 to 1:999, and can be optionally 1:499 to 1:
249.
22. The positive electrode active material according to any one of claims 9 to 21, wherein The coating amount of the shell is 0.1% to 6% based on the weight of the core.
23. The positive electrode active material according to any one of claims 9 to 22, wherein The shell is located on 40% to 90% of the surface of the inner core, optionally 60% to 80% of the surface.
24. The positive electrode active material according to any one of claims 9 to 23, wherein The shell has a thickness of 1-15 nm, and comprises a first coating layer and optionally a second to a third coating layer, in, The thickness of the first coating layer is 1-10 nm, and can be 2-10 nm; and / or, The thickness of the second coating layer is 2-25 nm, optionally 2-15 nm, more optionally 3-15 nm; and / or, The thickness of the third coating layer is 2-25 nm, and can be optionally 5-25 nm.
25. The positive electrode active material according to any one of claims 10 to 24, wherein The one or more coating layers included in the shell each independently include one or more selected from pyrophosphate, phosphate and oxide, and the one or more selected from the pyrophosphate, phosphate and oxide are crystalline; Optionally, the crystallinity of the pyrophosphate, the phosphate and the oxide is each independently 10% to 100%, more preferably 50% to 100%.
26. The positive electrode active material according to any one of claims 9 to 25, wherein The one or more coating layers each independently include carbon, and the carbon is a mixture of SP2 carbon and SP3 carbon; Optionally, in the carbon, the molar ratio of the SP2 carbon to the SP3 carbon is any value in the range of 0.07-13, more preferably any value in the range of 0.1-10, and further preferably any value in the range of 2.0-3.
0.
27. The positive electrode active material according to any one of claims 9 to 26, wherein The one or more coating layers each independently include doped carbon, and the mass content of the doping element in the doped carbon is less than 30%; optionally, the mass content of the doping element in the doped carbon is less than 20%, Optionally, the one or more coating layers each independently include doped carbon, in which: The doping element is nitrogen and / or sulfur, and the mass content of the doping element in the doped carbon is 1% to 15%; or, The doping element is phosphorus, boron and / or fluorine, and the mass content of the doping element in the doped carbon is 0.5% to 5%; Optionally, the doping element is nitrogen, phosphorus, sulfur, boron or fluorine.
28. The positive electrode active material according to any one of claims 9 to 27, wherein The one or more coating layers independently include pyrophosphate, the interplanar spacing of the pyrophosphate is in the range of 0.293-0.470nm, optionally 0.297-0.462nm or 0.293-0.326nm, more optionally 0.300-0.310nm, and the angle of the crystal direction (111) is in the range of 18.00°-32.57°, optionally 18.00°-32.00° or 26.41°-32.57°, more optionally 19.211°-30.846°, and further optionally 29.00°-30.00°; and / or, The one or more coating layers independently include phosphate, the interplanar spacing of the phosphate is in the range of 0.244-0.425 nm, optionally 0.345-0.358 nm, and the angle of the crystal direction (111) is in the range of 20.00°-37.00°, optionally 24.25°-26.45°; Optionally, the first coating layer or the second coating layer comprises phosphate.
29. The positive electrode active material according to any one of claims 1 to 28, wherein The positive electrode active material satisfies at least one of the following conditions: The lattice change rate before and after complete lithium deintercalation is 50% or less, optionally 9.8% or less, more optionally 8.1% or less, further optionally 7.5% or less, further optionally 6% or less, further optionally 4% or less, further optionally 3.8% or less, further optionally 2.0-3.8%; and / or The Li / Mn antisite defect concentration of the positive electrode active material is 5.3% or less, optionally 5.1% or less, more optionally 4% or less, further optionally 2.2% or less, further optionally 2% or less, further optionally 1.5%-2.2% or less than 0.5%; and / or the compaction density of the positive electrode active material at 3T is 1.89 g / cm 3 Above, optional 1.95g / cm 3 Above, 1.98g / cm2 is optional 3 Above, further optional 2.0g / cm 3 Above, further optional 2.2g / cm 3 Above, further optionally 2.2 g / cm 3 Above and 2.8g / cm 3 Below or 2.2g / cm 3 Above and 2.65g / cm 3 The following; and / or The surface oxygen valence state of the positive electrode active material is -1.55 or less, optionally -1.82 or less, more optionally -1.88 or less, further optionally -1.90 or less or -1.98 to -1.88, further optionally -1.98 to -1.89, further optionally -1.98 to -1.
90.
30. A positive electrode plate, comprising a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, the positive electrode film layer comprising a first positive electrode active material, and the first positive electrode active material is a positive electrode active material prepared by the method described in any one of claims 1 to 29; optionally, the content of the positive electrode active material in the positive electrode film layer is 90-99.5% by weight, and more optionally 95-99.5% by weight, based on the total weight of the positive electrode film layer. 31 . The positive electrode sheet according to claim 30 , further comprising a second positive electrode active material, wherein the second positive electrode active material is different from the first positive electrode active material.
32. The positive electrode sheet according to claim 30 or 31, wherein: The second positive electrode active material includes one or more selected from LiEtCosF(1-ts)O2, spinel lithium manganese oxide and spinel lithium titanate, wherein E includes one or more elements selected from Group VIII, F includes one or more elements selected from IIIA and VIIB, t is selected from the range of 0 to 0.9, and the sum of t and s is selected from the range of 0.3 to 1.
33. The positive electrode sheet according to claim 32, wherein: E includes one or more elements selected from Ni, Fe, Ru and Rh, and F includes one or more elements selected from Mn, Al, Ga and In.
34. The positive electrode sheet according to any one of claims 30 to 33, wherein: The second positive electrode active material includes one or more selected from LiNitCosMn(1-ts)O2, LiNitCosAl(1-ts)O2, LiCoO2, spinel lithium manganese oxide and spinel lithium titanate; wherein t is independently selected from 0.3-0.9, optionally 0.33-0.8, and the sum of t and s is independently selected from 0.3-0.9, optionally 0.66-0.
9.
35. The positive electrode sheet according to any one of claims 30 to 34, wherein: The mass ratio of the first active material to the second active material is 1:7-7:1, and can be optionally 1:4-4:
1.
36. The positive electrode sheet according to any one of claims 30 to 35, wherein: The sum of the mass of the first positive electrode active material and the second positive electrode active material accounts for 88% to 98.7% of the mass of the positive electrode sheet.
37. A secondary battery comprising the positive electrode material according to any one of claims 1 to 29, or the positive electrode sheet according to any one of claims 30 to 36.
38. A battery module comprising the secondary battery according to claim 37.
39. A battery pack comprising the battery module according to claim 38. 40 . An electrical device comprising at least one selected from the group consisting of the secondary battery of claim 37 , the battery module of claim 38 , and the battery pack of claim 39 .
Citation Information
Patent Citations
Fluorine and vanadium ion-doped lithium iron phosphate material and preparation method thereof
CN102583300A
Preparation method of phosphate potential boron-doped carbon-wrapped phosphoric acid iron-lithium material
CN103219516A
Cathode material of lithium ion battery and preparation method and application of cathode material
CN104577115A
Composite material containing lithium manganese ferric phosphate with core-shell structure and preparation method thereof
CN110416525A
Lithium iron manganese phosphate cathode material and preparation method and application thereof
CN111933915A
Cited By
Positive active material, preparation method thereof, positive pole piece, secondary battery, battery module, battery pack and electric device
CN117441241A
Lithium ion secondary battery, positive electrode active material, preparation method and electric equipment
CN121215860A